Landsat Instrument Suite (LandIS) sensor design for the Landsat 10 mission - Matthew Montanaro; Jeffrey Yee; Edmond Chung; Julie Montoya; Benjamin Turk; Eric Johnson; Andrew Pozo; Evan Haas; Steven Persh; Shawn Serbin; Thomas R. Holmes; Phillip W. Dabney; et al. (Remote Sensing of Environment, 2026)

Clinical and pathological assessment of the calystegines in Ipomoea carnea in a goat model - Daniel Cook; Bryan L. Stegelmeier; Dale R. Gardner; Franklin Riet-Correa; Clinton A. Stonecipher; Kevin D. Welch (Toxicon, 2026)

Pharmaceutical pollution in a wastewater-impacted coastal ecosystem - Raiko Rafeeq; Erinn K. Richmond; Wei Wen Wong; Daniel Cerveny; Tomas Brodin; Minna Saaristo; Michael R. Grace; Perran Cook; Bob B.M. Wong (Environmental Pollution, 2026)

Survey of management practices related to parasite control from ranched North American bison (Bison bison) in the southern United States - Kaylee R. Kipp; Joe L. Luksovsky; Christine M. Budke; Walter E. Cook; John S. Gilleard; Guilherme G. Verocai (Veterinary Parasitology, 2026)

Phenotypic plasticity of Durvillaea incurvata during suspended aquaculture in wave-sheltered conditions in Southern Chile (41°S) - L. Henríquez-Antipa; P. Leal; S. Cook; R. Altamirano; C. Valenzuela; A. Gutiérrez (Journal of Applied Phycology, 2026)

A climate services organization supporting coastal resilience: lessons from the Stone Living Lab - K. A. Dafforn; M. Borrelli; K. Bosma; J. E. K. Byrnes; L. Castro-Diaz; R. F. Chen; J. Christo; D. Cook; F. Peri; R. Shoer; M. Albert; K. Bradley; et al. (Climatic Change, 2026)
There is a growing recognition that effective climate adaptation requires organizations that can translate science into policy-relevant, place-based implementation. The Stone Living Lab (SLL) was established as a climate services organization to help bridge the gap between climate adaptation research and real-world application. In this paper, we present the Lab as a model for how universities and NGOs can partner with government agencies, Indigenous groups, and local communities to strengthen coastal resilience, highlighting the structures, guiding principles and lessons learned over the last five years. Four guiding principles shape and distinguish the Lab’s approach, extending beyond the traditional focus on science and engineering research to also include climate preparedness, education and outreach and policy engagement. These principles continue to evolve in response to experience, particularly in navigating complex partnerships and engaging with stakeholder networks, which require sustained coordination, clear communication, and intentional alignment of roles, expectations, and timelines. Other lessons highlight the importance of visible, place-based solutions, knowledge sharing and maintaining a clear mission focus while balancing short-term outcomes with long-term resilience goals. Our aim here is to provide practical insights for researchers, practitioners and managers seeking to design or strengthen similar climate services organizations.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

A systems modelling approach to predict biological responses to extreme heat - Daniel W.A. Noble; Margaret M. Mayfield; Ary A. Hoffmann; Zhong-Hua Chen; Steven J. Lade; Xuemei Bai; Danielle A. Way; Belinda E. Medlyn; Owen K. Atkin; Adrienne B. Nicotra; James M. Cook; Brajesh K. Singh; et al. (Trends in Ecology & Evolution, 2026)

Longitudinal patterns of urinary biomarkers of placental and renal function in pregnancy and associations with early pregnancy exposure to phthalates and replacements - Erin E. McNell; Danielle R. Stevens; Barrett M. Welch; Suzanne Fenton; Antonia M. Calafat; Julianne Cook Botelho; Elena Sinkovskaya; Ann Przybylska; George Saade; Alfred Abuhamad; Kelly K. Ferguson (Reproductive Toxicology, 2026)

American oak imports to Britain and Ireland in the 18th and early 19th centuries; The dendrochronological evidence - A. Crone; A. Arnold; R. Bale; M. Bridge; D. Brown; E. Cook; C. Griggs; R. Howard; D. Miles; C. Mills; N. Nayling; C. Tyers; et al. (Dendrochronologia, 2026)

Precision Forestry: Using Machine Learning and LiDAR to Inform Thinning in Pinus taeda Plantations – A Case Study - Erik Platt; David R. Carter; Amith Reddy; Timothy J. Albaugh; Rachel L. Cook; Otávio Campoe; Rafael Rubilar; Gunjan Barua; Matthew J. Sumnall (Journal of Forestry, 2026)
We demonstrate that the inputs and conceptual foundation needed for individual-tree-level precision thinning optimization algorithms are already available. As more resource managers adopt LiDAR-based inventories, precision thinning can become a value-added outcome of collecting these data. We use LiDAR to assess individual-tree stem volumes in Pinus taeda L. plantations in the southeast US. Rather than arbitrarily selecting starting rows in row thinning operations, we use field- and LiDAR-derived stem volume data to inform row selection. Among all three study sites, row-to-row tree volume variability was present, indicating that selecting rows to be removed deliberately could improve thinning outcomes. A machine learning model based on LiDAR-derived metrics was also accurate in estimating individual stem volume in the primary study site and LiDAR was accurate in measuring pre- and post-thinning stem counts, the data that would be needed to audit thins.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Leveraging additional VIIRS information to improve wildfire tracking in the western US - Shane R. Coffield; Tempest D. McCabe; Wilfrid Schroeder; Yang Chen; Rebecca C. Scholten; Elijah Orland; Tianjia Liu; Elizabeth Wiggins; James T. Randerson; Melanie Follette-Cook; Douglas C. Morton (Remote Sensing of Environment, 2026)

Bipolar volcanic ice-core synchronization of the entire last glacial period - Anders Svensson; Guido Vettoretti; Jia-mei Lin; Giulia Sinnl; Dorthe Dahl-Jensen; Jørgen Peder Steffensen; Sune Olander Rasmussen; Bo Vinther; Christine Hvidberg; Helle Astrid Kjær; Vasileios Gkinis; Eliza Cook; et al. (Quaternary Science Reviews, 2026)

From little things big things flow: the drivers of flood risk adaptation - Peter Kamstra; Nicholas Harrigan; Brian R. Cook (Journal of Hydrology, 2026)

Carbon fluxes and partitioning in Eucalyptus and Pinus plantations across a climatic gradient in Brazil - Fernanda Leite Cunha; Otávio Camargo Campoe; Cléber Rodrigo de Souza; Isaira Leite & Lopes; Yann Nouvellon; Timothy Albaugh; David R. Carter; Rafael Rubilar; Isabel Deliberari; Rachel Cook; Joannès Guillemot; Guerric Le Maire; et al. (Agricultural and Forest Meteorology, 2026)

Effect of long-term tillage practices on soil physical properties, corn and soybean yield, and nutrient balance - Amanda Weidhuner; Omid R. Zandvakili; Sowmya Koduru; Ronald Krausz; Rachel L. Cook; Anastasia Hanauer; Karen Jones; Amir Sadeghpour (Field Crops Research, 2026)

Collaborative evaluation of in silico predictions for high throughput toxicokinetics - John F. Wambaugh; Nisha S. Sipes; Gilberto Padilla Mercado; Jon A. Arnot; Linda Bertato; Trevor N. Brown; Nicola Chirico; Christopher Cook; Daniel E. Dawson; Sarah E. Davidson-Fritz; Stephen S. Ferguson; Michael-Rock Goldsmith; et al. (Toxicology in Vitro, 2026)

Learning, action, and behaviour change: effective Forum Theatre design for smallholder farmers - Kirt Hainzer; Nicholas Harrigan; Van Touch; Bonny Coombe; Caitlin Finlayson; Bunnarath Som; Chariya Korn; Lita Mom; Panhaleak Chay; Pherom Song; Sao Chen; Saroeut Yong; et al. (Journal of Environmental Management, 2026)

Associations of endocrine disrupting chemical biomarkers and their mixture with vitamin D biomarker concentrations in childhood: The HOME Study - Katherine M. Marquess; Jordan R. Kuiper; Taylor M. Etzel; Bruce P. Lanphear; Andrew N. Hoofnagle; Antonia M. Calafat; Julianne Cook Botelho; Maria Ospina; Andreas Sjodin; Lesliam Quirós-Alcalá; Kim M. Cecil; Aimin Chen; et al. (Environmental Research, 2026)

Adding value to imperfect long-term animal monitoring data for conservation insight - S.D. Sarre; E.J. Stringer; R. Brawata; E. Carlson; R. Colley; E. Cook; B. Croak; L.I. Doucette; M. Hoehn; B. Howland; W.S. Osborne; S. Pulsford; et al. (Biological Conservation, 2026)

Exploring Marine Mammal Cognition as a Conservation Tool - Gordon B. Bauer; Peter F. Cook; Heidi E. Harley; Jason Bruck; Mel Cosentino; Charles J. Deutsch; Nicola Erdsack; Wendi Fellner; Tabitha Gunnars; Heather Manitzas Hill; Sonia V. Kumar; Malin K. Lilley; et al. (Marine Mammal Science, 2026)
Cognition is an animal's real‐time adaptation system for responding to change. Rapid environmental change, often anthropogenic, is expanding the range and severity of challenges confronting wild animals. Effective conservation requires a multifaceted approach that includes animals' capacities. Large‐brained, long‐lived animals such as marine mammals often have extensive capability to adaptively modify their behavior due to their cognition, which comprises the mechanisms of information acquisition, processing, and flexible action. Consequently, current behavior need not be a final predictor of future behavior for these animals. This flexibility provides an underutilized and under examined point of leverage for humans interested in improving life outcomes for wild animals. In this team‐written, interdisciplinary paper, we argue that application of cognitive approaches may facilitate many conservation efforts directed toward marine mammals. Starting with a workshop on this topic at the 24th Biennial Conference on the Biology of Marine Mammals, scientists representing a wide range of disciplinary expertise addressed eight different conservation concerns for six marine mammal species and provided potential cognitive explanations of and interventions aimed at related behavior. Our treatment highlights the value of integrated laboratory and field research, and the importance of tight lines of communication between scientists and conservation managers.

Metabolic and survival responses of the carnivorous snail Acanthina monodon to extreme marine heatwaves - Paola A. Villanueva; Joseline A. Büchner-Miranda; Jorge M. Navarro; Sebastián Cook; Octavio Mercado-Peña; Paula Amador-Véliz; Gonzalo Donoso; Elisabeth Teca Oliva; Oscar R. Chaparro (Regional Studies in Marine Science, 2025)

Bridging extreme climate risks, financial precarity, and adaptation gaps: Advancing inclusive adaptation in rainfed agricultural systems - Van Touch; Ariane Utomo; De Li Liu; Nicholas Harrigan; Le-Anne Bannan; Panhaleak Chay; Caitlin Finlayson; Kirt Hainzer; Andrew McGregor; Katharine McKinnon; Lita Mom; Sophanara Phan; et al. (Global Environmental Change, 2025)

Rethinking adaptation interventions in agricultural systems for sustainability - Sechindra Vallury; Donald R Nelson; Nathan J Cook (Current Opinion in Environmental Sustainability, 2025)

The miRNomics of antiretroviral therapy-induced obesity - Niska Majumdar; Bishwa R. Pokharel; Abigail Dickerson; Andreea Cruceanu; Smit Rajput; Lok R. Pokhrel; Paul P. Cook; Shaw M. Akula (Functional & Integrative Genomics, 2025)
Human immunodeficiency virus (HIV) is a retrovirus that incorporates its genetic material into the host’s chromosome. The resulting diseases and related conditions constitute a global health problem as there are no treatments to eliminate HIV from an infected individual. However, the potent, complex, and active antiretroviral therapy (ART) strategies have been able to successfully inhibit HIV replication in patients. Unfortunately, obesity following ART is frequent among HIV-infected patients. The mechanism underlying ART-induced obesity is characterized based on expression of traditional markers such as genes and proteins. However, little is known about, yet another key component of molecular biology known as microRNAs (miRNAs). Micro-RNAs are ~ 22 base-long non-coding nucleotides capable of regulating more than 60% of all human protein-coding genes. The interest in miRNA molecules is increasing and their roles in HIV and obesity are beginning to be apparent. In this review, we provide an overview of HIV and its associated diseases, ART-induced obesity, and discuss the roles and plausible benefits of miRNAs in regulating obesity genes in HIV-infected patients. Understanding the roles of miRNAs in ART-induced obesity will aid in tracking the disease progression and designing beneficial therapeutic approaches.

Reshaping agricultural production systems: Trade-offs and implications for sustainable intensification and environment management - Van Touch; Ariane Utomo; Nicholas Harrigan; Caitlin Finlayson; Andrew McGregor; Katharine McKinnon; Thong Anh Tran; Le-Anne Bannan; Daniel K.Y. Tan; Phan Sophanara; Panhaleak Chay; Sophea Yous; et al. (Agricultural Systems, 2025)

The impacts of marine heatwaves on ecosystems and fisheries in Aotearoa New Zealand - Katie M. Cook; Matthew R. Dunn; Erik Behrens; Matt H. Pinkerton; Cliff S. Law; Vonda J. Cummings (New Zealand Journal of Marine and Freshwater Research, 2025)
Marine heatwaves (MHWs) are increasing in frequency and intensity globally, yet the impacts of such extreme events are not well understood. We review the effects of MHWs on the fisheries and ecosystems of Aotearoa‐New Zealand (NZ), an island nation with over 15,000 km of coastline, and 4 million km 2 of exclusive economic zone, that supports diverse marine communities and valuable commercial and recreational fisheries. Using Aotearoa‐NZ and global literature, we discuss the potential effects of MHWs on the physical environment and on species, populations and ecosystems. We review recorded national impacts with a fisheries focus, and systematically assess MHW effects on 32 commercially or culturally important Aotearoa‐NZ wild‐caught fishery or aquaculture species, classifying their vulnerabilities. We found records of MHW‐induced ecosystem shifts, with macroalgae community change, and out‐of‐range occurrences of warm‐water species. Of the 32 species examined, national MHW impacts were documented for three species (green‐lipped mussel, snapper, and Chinook salmon). We highlight the paucity of information for life‐stage specific impacts, and indirect impacts such as changes in predator‐prey interactions and biogenic habitat distributions. Assessing MHW impacts through a fisheries lens highlights the need for enhanced interdisciplinary research and monitoring, to develop sustainable management strategies under environmental change.

Precision forestry in actively managed loblolly pine plantations: Leaf area index response one growing season following a variable-rate fertilization - Chris W. Cohrs; Al Lyons; Timothy J. Albaugh; David R. Carter; Otávio C. Campoe; Rafael A. Rubilar; Matthew Sumnall; Andrew Trlica; Mark V. Corrao; Simerjeet Virk; Rex Lester; Rachel L. Cook (Forest Ecology and Management, 2025)

Molecular characterisation of a novel citrus-infecting emaravirus, citrus emaravirus 1 - R. Bester; C. Gill; J.H.J Breytenbach; C. Steyn; H.J. Maree; G. Cook (Archives of Virology, 2025)
The application of high-throughput sequencing (HTS) has accelerated the discovery of novel viruses and the genome sequencing of poorly characterised viruses in fruit crops, revealing a greater complexity of plant viromes than previously understood. Here, we report the identification and genomic characterisation of a novel emaravirus, tentatively named "citrus emaravirus 1" (CiEV1), from Citrus limon leaves collected in the North West Province of South Africa. HTS analysis identified contigs corresponding to the four conserved emaravirus genomic segments (RNA1-RNA4), each encoding characteristic proteins: RNA-dependent RNA polymerase, glycoprotein, nucleocapsid, and movement protein. Comparison of terminal sequences and phylogenetic analysis suggest placing CiEV1 within clade D of the genus Emaravirus (family Fimoviridae ). To date, no association with symptoms has been identified. This is the first report of an emaravirus detected in citrus, expanding the known host range of the genus and contributing to the growing evidence of viral diversity in citrus. Further investigation is required to determine the epidemiological significance of CiEV1 in citrus orchards.

The Properties of Individual Fire Events Are Essential for Understanding Global Fire Regimes - Adam L. Mahood; Ty Tuff; Megan E. Cattau; Virginia Iglesias; Thomas E. Hanson; Jilmarie Stephens; Nayani Ilangakoon; Maxwell C. Cook; R. Chelsea Nagy; David Barnard; E. Natasha Stavros; Amy DeCastro; et al. (Global Ecology and Biogeography, 2025)
Aim As fire activity changes globally, we need to better understand the spatial and temporal characteristics of the individual events that, when aggregated, constitute fire regimes. Most global studies analyze point detections of burned area, without delineating or considering the properties of individual events. Furthermore, there is a critical need to understand fire patterns within the context of the geopolitical boundaries within which fires are managed. Location Global. Time Period 2003–2020. Major Taxa Studied Fire. Methods We divided 241 countries by Köppen‐Geiger climate classifications and quantified four event‐based fire regime metrics: size, duration, and mean and maximum growth rate; and four area‐based metrics: burned area, number of fires, season length, and season peak. We examined the correlations among fire regime components, and between each fire regime component and climate normals. We quantified temporal trends, and used mixed models to analyze how climate and landcover change were associated with event‐based components of fire regimes. Results Event‐based metrics were weakly correlated with area‐based metrics. Countries with warmer and less variable climates had high burned area, more fire events, longer season lengths and shorter event durations. Countries with high annual temperature range and low precipitation tended to have fewer events but larger fires that were faster‐spreading and occurred later in the year. The growth rate and size of individual fire events are increasing in 18% and 21% of regions we analysed, respectively. Interannual variability in size and growth rate was associated with aridity increases in boreal areas, and landcover changes in arid areas. Main Conclusions Drivers of burned area and fire seasonality are well understood but largely unrelated to the properties of individual events. A more detailed understanding of the spatial and temporal aspects of fire events at broad scales will assist fire management efforts in preparing for a warmer future.

Characteristics of aqueous film forming foam (AFFF) sites impacted with per- and polyfluoroalkyl substances (PFAS): A 37-site study - Poonam R. Kulkarni; Nicolette E. Andrzejczyk; Arun Gavaskar; Abigail Cartwright; David T. Adamson; John Cook; Charles J. Newell (Water Research, 2025)

Predicting the yield of Pinus taeda (L.) using UAV LiDAR data in random forest and support vector machine models - Gunjan Barua; David R. Carter; Valerie A. Thomas; P. Corey Green; Phil Radtke; Thomas J. Pingel; Rachel L. Cook; Timothy J. Albaugh; Rafael Rubilar; Otavio Campoe; Matthew Sumnall (Forest Ecology and Management, 2025)

Quantifying above- and belowground biomass improved our understanding of site differences and demonstrated the importance of management decisions in sequestering carbon in Pinus taeda - Timothy J. Albaugh; Chris A. Maier; Otávio C. Campoe; Marshall A. Laviner; Timothy J. Shively; Vitor Aguiar; Kyle R. Peer; David R. Carter; Rachel L. Cook; Rafael A. Rubilar; Thomas R. Fox (Forest Ecology and Management, 2025)

A new digital cover photography dataset and processing tool for SMAPVEX19-22: How siting and sky condition impact plant area index retrievals in continuous measurement set-ups - Simon Kraatz; Michael H. Cosh; V. Kelly; Laura Bourgeau-Chavez; Jisung Geba Chang; Chris Cook; Victoria A. Walker; Paul R. Siqueira; Andreas Colliander (Agricultural and Forest Meteorology, 2025)

We Need the Largest Experiments on Earth to Achieve Our Climate Targets - Bronson W. Griscom; Susan C. Cook‐Patton; Erin Sills; Kelsey Jack; Thomas W. Crowther; Sebastien Costedoat; Christopher Field; David Hole; Lisa M. McCullough; Subhrendu K. Pattanayak; Sassan Saatchi; Will R. Turner (Global Change Biology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Rewetting alongside biochar and sulphate addition mitigates greenhouse gas emissions and retain carbon in degraded upland peatlands - Peduruhewa H. Jeewani; Robert W. Brown; Chris D. Evans; Jack Cook; Benjamin P. Roberts; Mariecia D. Fraser; David R. Chadwick; Davey L. Jones (Soil Biology and Biochemistry, 2025)

Ecosystem-wide PFAS characterization and environmental behavior at a heavily contaminated desert oasis in the southwestern U.S. - Jean-Luc E. Cartron; Chauncey R. Gadek; Jonathan L. Dunnum; Christopher C. Witt; Mariel L. Campbell; Samuel J. Romero; Andrew B. Johnson; Julie Kutz; Christopher Wolf; Sarah J. Choyke; Joseph A. Cook (Environmental Research, 2025)

Exposure to phthalates and replacements during pregnancy in association with gestational blood pressure and hypertensive disorders of pregnancy - Erin E. McNell; Danielle R. Stevens; Barrett M. Welch; Emma M. Rosen; Suzanne Fenton; Antonia M. Calafat; Julianne Cook Botelho; Elena Sinkovskaya; Ann Przybylska; George Saade; Alfred Abuhamad; Kelly K. Ferguson (Environmental Research, 2025)

Varying climate signals embedded in latewood blue intensity along an elevational gradient: A multi-species case study from the Great Basin, Nevada, USA - Karen E. King; Edward R. Cook; Paul J. Krusic; Daniel J. King (Dendrochronologia, 2025)

Marker trait association analysis identified a novel quantitative trait loci (QTL) for Fusarium wilt resistance in chickpea (Cicer arietinum L.) - Dagnachew Bekele; Kassahun Tesfaye; Asnake Fikre; Noelia C. Garcia; Peter L. Chang; Douglas R. Cook (Euphytica, 2025)

Evaluating individual tree metrics calculated from unmanned aerial vehicle laser scanning as input to a conventional growth and yield model - Matthew J. Sumnall; David R. Carter; Timothy J. Albaugh; Rachel L. Cook; Otávio C. Campoe; Rafael A. Rubilar (International Journal of Remote Sensing, 2025)

Corrigendum to article title: ‘Smallholder farmers’ challenges and opportunities: Implications for agricultural production, environment and food security’ [J. Environ. Manag., Volume: 370, Year: 2024, Pages: 122536] - Van Touch; Daniel K.Y. Tan; Brian R. Cook; De Li Liu; Rebecca Cross; Thong Anh Tran; Ariane Utomo; Sophea Yous; Clemens Grunbuhel; Annette Cowie (Journal of Environmental Management, 2025)

Prenatal per- and polyfluoroalkyl substance mixtures and weight for length from birth to 12 months: The New Hampshire Birth Cohort Study - Gyeyoon Yim; Caitlin G. Howe; Lisa G. Gallagher; Diane Gilbert-Diamond; Antonia M. Calafat; Julianne Cook Botelho; Margaret R. Karagas; Megan E. Romano (Science of The Total Environment, 2025)

Correcting the heartwood-sapwood transition in blue intensity measurements with change point detection methods - Hung T.T. Nguyen; Rory Abernethy; Rob Wilson; Daniel L. Druckenbrod; Kathryn J. Allen; Brendan M. Buckley; Edward R. Cook; Rosanne D’Arrigo; Jonathan G. Palmer (Dendrochronologia, 2025)

Dynamic cooling: Thermal and temporal effects on cognitive load and performance in office environments - Amelie Reitmayer; Sebastian Clark Koth; Kelly R Johnstone; Cassandra Madigan; Margaret M Cook (Building and Environment, 2025)

Native Australian seedlings exhibit novel strategies to acclimate to repeated heatwave events - Philippa R. Alvarez; Rosalie J. Harris; Alicia M. Cook; Verónica F. Briceño; Adrienne B. Nicotra; Andrea Leigh (Oecologia, 2025)
Heatwaves are becoming more intense and frequent. Plant photosystem thermal thresholds can vary with species, but also shift in response to environmental triggers. Both upper and lower thresholds can acclimate to repeated heatwaves through ecological stress memory, where prior exposure primes them for subsequent events. The extent to which acclimation to repeated heat stress events varies among environmental origin and/or species is unknown. Different acclimation strategies might reflect biome of origin, or may be species-specific. For 12 species from two contrasting biomes—extreme desert and benign coastal temperate—we investigated responses to two simulated heatwaves, via shifts in upper and lower critical temperatures of photosystem II, and the difference between these thresholds, thermal tolerance breadth (TTB). Biome of origin had no effect on thermal tolerance. Observed differences among species following heat events suggested two possible acclimatory strategies. In some cases, species increased thermal thresholds during the first heatwave, but at the cost of reduced thermal tolerance during the second heatwave, a sprinter strategy. Other species acclimated to the first heatwave and further increased thermal tolerance to a second heatwave, indicative of ecological stress memory, a marathoner strategy. Synthesis: these among-species responses to heatwaves could suggest distinct vulnerabilities and resilience to repeat heat stress events, with some species having limited capacity to tolerate consecutive heatwaves, possibly as the cost of acclimation is too great, with other species having the advantage of increased tolerance via stress memory, helping them survive future stress, at least in the short-term.

Correction to: Structural controls on cobalt mineralisation during regional metamorphism: an example from the Rajapalot area, Finland - Mohammad Sayab; Andrew Menzies; Richard M. Palin; Alan R. Butcher; Nick Cook; Jukka Kuva; Quentin Dehaine (Mineralium Deposita, 2025)

Correction to: Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2025)

Rhenium-osmium and oxygen isotope homogeneity during the 2022 Mauna Loa eruption and implications for basaltic magma storage - Emily A. Rhoads; Anton Kutyrev; Ilya N. Bindeman; Kendra J. Lynn; Frank A. Trusdell; Drew T. Downs; Hunter R. Edwards; Geoffrey W. Cook; James M. D. Day (Bulletin of Volcanology, 2025)
Mauna Loa is one of the largest and most active volcanoes on Earth. The most recent eruption of Mauna Loa started on 27 November 2022, lasted for 13 days, and was preceded by the longest repose time of 38 years in its modern history. In this contribution, new trace- and highly siderophile-element (HSE: Os, Ir, Ru, Pt, Pd, Re) abundances, 187 Re- 187 Os, and 18 O/ 16 O data are reported for the 2022 lavas. These lavas have a limited range of MgO (6.2 ± 0.1 wt.%) and Ni (83 ± 2 µg/g), with a broader range of Re (0.3 to 1.3 ng/g) and consistent Os (0.031 to 0.080 ng/g) contents. They have 187 Os/ 188 Os ratios (0.1345 to 0.1385) which are, on average, more radiogenic than Mauna Loa picrites (0.1331 to 0.1349) and are similar in composition to more differentiated Mauna Loa tholeiite lavas (0.1340 to 0.1381). The oxygen isotope compositions of glassy samples are 5.35 ± 0.15‰ ( n = 13) and span a range in δ 18 O of + 5.0 to + 5.5‰, with an average composition 0.2 to 0.3‰ lower than MORB. The δD value is − 81 ± 11‰ ( n = 5) at very low (0.03 ± 0.015 wt.%) H 2 O concentrations. The 2022 Mauna Loa eruption is similar in terms of δ 18 O but contrasts in terms of 187 Os/ 188 Os variability, with the recent longer-lived eruptions on La Palma (Canary Islands; 85 days) in 2021 and on the Reykjanes Peninsula (Iceland) that began in 2021 and are still ongoing. Initial lavas were more fractionated for both the Canary Islands and Iceland eruptions, producing more radiogenic Os isotope compositions than later erupted products. The 2022 Mauna Loa eruption showed no such trends. The limited range in isotope compositions of the 2022 Mauna Loa lavas and their strongly fractioned HSE patterns reflect long-term storage, crystal fractionation, and assimilation of related basaltic volcanic edifice materials by the parent magma beneath the volcano prior to eruption triggering. Eruption of differentiated and homogeneous tholeiite lavas at the summit caldera and high on the volcano’s flank, with emplacement of accumulative picrites lower on the volcano, are consistent with neutral buoyancy arguments.

Canine proliferative sparganosis: a case report and review of larval cestodiasis in dogs - Varvara Semenova; Heather D.S. Walden; Kelsey Bollenback; James R. Cook; Robert J. Ossiboff (Journal of Comparative Pathology, 2025)

Prenatal per- and polyfluoroalkyl substances and blood pressure trajectories in the New Hampshire Birth Cohort Study - Yuting Wang; Elizabeth C. Anderson; Caitlin G. Howe; Jiang Gui; Lisa G. Gallagher; Brianna Heggeseth; Julianne Cook Botelho; Antonia M. Calafat; Margaret R. Karagas; Megan E. Romano (International Journal of Hygiene and Environmental Health, 2025)

Cross-cultural evidence that intergroup conflict heightens preferences for dominant leaders: A 25-country study - Lasse Laustsen; Xiaotian Sheng; M. Ghufran Ahmad; Laith Al-Shawaf; Benjamin Banai; Irena Pavela Banai; Michael Barlev; Nicolas Bastardoz; Alexander Bor; Joey T. Cheng; Anna Chmielińska; Alexandra Cook; et al. (Evolution and Human Behavior, 2025)

Ecosystem Services Provided by Seaweed Cultivation: State of the Art, Knowledge Gaps, Constraints and Future Needs for Achieving Maximum Potential in Europe - Fricke A; Capuzzo E; Bermejo R; Hofmann LC; Hernández I; Pereira R; Van den Burg SWK; Pereira T; Buschmann AH; Cottier-Cook EJ (Reviews in Fisheries Science & Aquaculture, 2025)

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

DNA data (genome skims and metabarcodes) paired with chemical data demonstrate utility for retrospective analysis of forage linked to fatal poisoning of cattle - Daniel Cook; Brandon Kocurek; Clint Stonecipher; Kevin D. Welch; Dale R. Gardner; Mark Mammel; Elizabeth Reed; Padmini Ramachandran; David Erickson; Seth Commichaux; Andrea Ottesen (Toxicon, 2025)

Reversal of practical resistance in fall armyworm to Cry1F maize: a case report on the resistance to susceptibility in Bt crops from the southeastern USA - Tiago Silva; Gregory A. Sword; Andie Miller; Jawwad A. Qureshi; Graham P. Head; Dawson D. Kerns; Juan Luis Jurat-Fuentes; James Villegas; Tyler B. Towles; Xinzhi Ni; Francis P. F. Reay-Jones; Daniel Carrillo; et al. (Journal of Pest Science, 2025)

Crown complementarity rather than crown selection contributes to stem complementarity in genetic mixtures of Pinus taeda L - David R. Carter; Timothy J. Albaugh; Matthew Sumnall; Jake J. Grossman; Otávio C. Campoe; Rachel L. Cook; Rafael A. Rubilar; Chris A. Maier; T. Adam Coates; Julia DeFeo; Grady J. Boyle; Megan Van Spanje (Acta Oecologica, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Structural controls on cobalt mineralisation during regional metamorphism: an example from the Rajapalot area, Finland - Mohammad Sayab; Andrew Menzies; Richard M. Palin; Alan R. Butcher; Nick Cook; Jukka Kuva; Quentin Dehaine (Mineralium Deposita, 2025)
The Rajapalot area of Finnish Lapland hosts an unusually high-grade association of cobalt-only and gold–cobalt deposits (10.91 Mt @ 2.5 g/t Au + 0.044% Co total inferred resources) within multiply folded metasedimentary rocks of the Paleoproterozoic Svecofennian collisional orogeny. Through the integration of X-ray computed micro-tomography and micro-X-ray fluorescence raster imaging of drill-core samples, we produce a model of cobalt-bearing ore mineralisation, which reveals primary fluid transportation mechanisms and precipitation pathways. When combined with the deposit-scale, high-resolution ground-based magnetic geophysical data, we show that cobalt-bearing ores in the Rajapalot region occur mostly as saddle reefs located in dilated fold hinges, which formed by simultaneous synthetic and antithetic shearing along developing crenulation-cleavage planes and incompetent bedding layers, respectively. We suggest that multi-layered rock complexes with alternations of competent and incompetent layers deformed and metamorphosed to upper greenschist-lower amphibolite facies should represent focus regions for cobalt exploration targeting campaigns in orogenic belts. The non-destructive workflow presented in this study could be an integral part of an early stage of cobalt mineral processing and traceability before metallurgical treatment.

Loblolly Pine Growth and Competition Response to Varied Chemical Site Preparation and Release Treatments 14 Years After Establishment in the Piedmont of Virginia - Alexander Byers; David R. Carter; Rachel L. Cook; Brian Strahm; Jerre Creighton (Journal of Forestry, 2025)
We examined the 14-year effects of experimentally varied chemical site preparation and release treatments in a Pinus taeda L. plantation in Dillwyn, Virginia, US. The study examined the effects of timing (July, September, or October) for imazapyr site preparation, with or without the addition of sulfometuron methyl (SFM), year-one release from herbaceous weeds using SFM plus imazapyr, and year-two release treatment using imazapyr at a rate to control hardwoods. Chemical site preparation treatment applications exhibited a reduction in competition basal area ha -1 and an increase in pine volume compared to the check, however, application timing was the most influential factor in determining the effectiveness of the treatments. September 3rd and October 1st applications averaged less competing vegetation basal area than the year-two release and the check plots. At age 14-years, competing vegetation reduced individual pine tree volumes by 5.6% for every one m 2 of competing vegetation basal area.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Comparing efficiencies of population control methods for responding to introductions of transboundary animal diseases in wild pigs - Nathan P. Snow; Benjamin Smith; Michael J. Lavelle; Michael P. Glow; Kayleigh Chalkowski; Bruce R. Leland; Sarah Sherburne; Justin W. Fischer; Keely J. Kohen; Seth M. Cook; Hatton Smith; Kurt C. VerCauteren; et al. (Preventive Veterinary Medicine, 2024)

Growth trends of loblolly pine age five or less in relation to soil type and management intensity - Christen Beasley; David R. Carter; Timothy J. Albaugh; David Enemo; Daniel S. Hong; Rachel Cook; Otávio Campoe; Rafael Rubilar (Forest Ecology and Management, 2024)

Smallholder farmers’ challenges and opportunities: Implications for agricultural production, environment and food security - Van Touch; Daniel K.Y. Tan; Brian R. Cook; De Li Liu; Rebecca Cross; Thong Anh Tran; Ariane Utomo; Sophea Yous; Clemens Grunbuhel; Annette Cowie (Journal of Environmental Management, 2024)

Nature vs. nurture: Drivers of site productivity in loblolly pine (Pinus taeda L.) forests in the southeastern US - Vicent A. Ribas-Costa; Aitor Gastón; Sean A. Bloszies; Jesse D. Henderson; Andrew Trlica; David R. Carter; Rafael Rubilar; Timothy J. Albaugh; Rachel L. Cook (Forest Ecology and Management, 2024)

Threat assessment for Pacific sand lance (Ammodytes personatus) in the Salish Sea - Jacqueline R. Huard; Victoria Hemming; Matthew R. Baker; Jennifer Blancard; Ian Bruce; Sarah Cook; Gail K. Davoren; Phillip Dionne; Virginia East; J. Mark Hipfner; Nicola R. Houtman; Brian A. Koval; et al. (Frontiers in Marine Science, 2024)
Like many forage fish species, Pacific sand lance ( Ammodytes personatus ) play a key role in nearshore marine ecosystems as an important prey source for a diverse array of predators in the northeastern Pacific. However, the primary threats to Pacific sand lance and their habitat are poorly defined due to a lack of systematic data. Crucial information needed to assess their population status is also lacking including basic knowledge of their local and regional abundance and distribution. Sand lance are currently listed as ‘not evaluated’ under the IUCN red list and they have not been assessed by US and Canadian agencies. This hampers management and policy efforts focused on their conservation. To address this knowledge gap, we conducted a three-part, structured expert elicitation to assess the vulnerability of Salish Sea sand lance populations. Experts were asked to list and rank key threats to Salish Sea sand lance and/or their habitat, to further quantify the vulnerability of sand lance to identified threats using a vulnerability matrix, and to predict the population trajectory in 25 years from today. Impacts associated with climate change (e.g. sea level rise, sea temperature rise, ocean acidification, and extreme weather) consistently ranked high as threats of concern in the ranking exercise and quantified vulnerability scores. Nearly every expert predicted the population will have declined from current levels in 25 years. These results suggest sand lance face numerous threats and may be in decline under current conditions. This research provides vital information about which threats pose the greatest risk to the long-term health of sand lance populations and their habitat. Managers can use this information to prioritize which threats to address. Future research to reliably quantify population size, better understand the roles of natural and anthropogenic impacts, and to identify the most cost-effective actions to mitigate multiple threats, is recommended.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Intracerebral Administration of a Novel Self-Assembling Peptide Hydrogel Is Safe and Supports Cell Proliferation in Experimental Intracerebral Haemorrhage - Faye Bolan; Ben R. Dickie; James R. Cook; Josephine M. Thomas; Emmanuel Pinteaux; Stuart M. Allan; Alberto Saiani; Catherine B. Lawrence (Translational Stroke Research, 2024)
Intracerebral haemorrhage (ICH) is the deadliest form of stroke, but current treatment options are limited, meaning ICH survivors are often left with life-changing disabilities. The significant unmet clinical need and socioeconomic burden of ICH mean novel regenerative medicine approaches are gaining interest. To facilitate the regeneration of the ICH lesion, injectable biomimetic hydrogels are proposed as both scaffolds for endogenous repair and delivery platforms for pro-regenerative therapies. In this paper, the objective was to explore whether injection of a novel self-assembling peptide hydrogel (SAPH) Alpha2 was feasible, safe and could stimulate brain tissue regeneration, in a collagenase-induced ICH model in rats. Alpha2 was administered intracerebrally at 7 days post ICH and functional outcome measures, histological markers of damage and repair and RNA-sequencing were investigated for up to 8 weeks. The hydrogel Alpha2 was safe, well-tolerated and was retained in the lesion for several weeks, where it allowed infiltration of host cells. The hydrogel had a largely neutral effect on functional outcomes and expression of angiogenic and neurogenic markers but led to increased numbers of proliferating cells. RNAseq and pathway analysis showed that ICH altered genes related to inflammatory and phagocytic pathways, and these changes were also observed after administration of hydrogel. Overall, the results show that the novel hydrogel was safe when injected intracerebrally and had no negative effects on functional outcomes but increased cell proliferation. To elicit a regenerative effect, future studies could use a functionalised hydrogel or combine it with an adjunct therapy.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

The use of earwax to determine livestock exposure to teratogenic lupine - Clinton A. Stonecipher; Stephen T. Lee; Kevin D. Welch; Kristian R. Valles; Daniel Cook (Toxicon, 2024)

Comparison of the acute toxicity of zygacine versus zygadenine - Kevin D. Welch; Dale R. Gardner; Stephen T. Lee; Clint A. Stonecipher; Daniel Cook (Toxicon, 2024)

A new certified reference material IAEA-465 for radionuclides in Baltic Sea sediment - M.K. Pham; M.-O. Aust; J. Bartocci; O. Blinova; F.P. Carvalho; E. Chamizo; M. Cook; D. Degering; M. Fujak; C. Gascó; R. Gurriaran; V. Jobbágy; et al. (Journal of Environmental Radioactivity, 2024)

A 561-yr (1461-2022 CE) summer temperature reconstruction for Mid-Atlantic-Northeast USA shows connections to volcanic forcing and atmospheric circulation - Grant L. Harley; Justin T. Maxwell; Karen E. King; Shelly A. Rayback; Edward R. Cook; Christopher Hansen; R. Stockton Maxwell; Frederick Reinig; Jan Esper; Tsun Fung Au; Ellen V. Bergan; Katherine E. Brings; et al. (Climatic Change, 2024)
Contextualizing current increases in Northern Hemisphere temperatures is precluded by the short instrumental record of the past ca. 120 years and the dearth of temperature-sensitive proxy records, particularly at lower latitudes south of <50 °N. We develop a network of 29 blue intensity chronologies derived from tree rings of Tsuga canadensis (L.) Carrière and Picea rubens Sarg. trees distributed across the Mid-Atlantic and Northeast USA (MANE)—a region underrepresented by multi-centennial temperature records. We use this network to reconstruct mean March-September air temperatures back to 1461 CE based on a model that explains 62% of the instrumental temperature variance from 1901−1976 CE. Since 1998 CE, MANE summer temperatures are consistently the warmest within the context of the past 561 years exceeding the 1951−1980 mean of +1.3 °C. Cool summers across MANE were frequently volcanically forced, with significant ( p <0.05) temperature departures associated with 80% of the largest tropical ( n =13) and extratropical ( n =15) eruptions since 1461 CE. Yet, we find that more of the identified cool events in the record were likely unforced by volcanism and either related to stochastic variability or atmospheric circulation via significant associations ( p <0.05) to regional, coastal sea-surface temperatures, 500-hpa geopotential height, and 300-hpa meridional and zonal wind vectors. Expanding the MANE network to the west and south and combining it with existing temperature-sensitive proxies across North America is an important next step toward producing a gridded temperature reconstruction field for North America.

Evaluating the transferability of airborne laser scanning derived stem size prediction models for Pinus taeda L. stem size estimation to two different locations and acquisition specifications - Matthew J. Sumnall; David R. Carter; Timothy J. Albaugh; Erik Platt; Trevor Host; Rachel L. Cook; Otávio C. Campoe; Rafael A. Rubilar (International Journal of Remote Sensing, 2024)

Association of diet with per- and polyfluoroalkyl substances in plasma and human milk in the New Hampshire Birth Cohort Study - Yuting Wang; Jiang Gui; Caitlin G. Howe; Jennifer A. Emond; Rachel L. Criswell; Lisa G. Gallagher; Carin A. Huset; Lisa A. Peterson; Julianne Cook Botelho; Antonia M. Calafat; Brock Christensen; Margaret R. Karagas; et al. (Science of The Total Environment, 2024)

Combining wastewater surveillance and case data in estimating the time-varying effective reproduction number - Shihui Jin; Martin Tay; Lee Ching Ng; Judith Chui Ching Wong; Alex R. Cook (Science of The Total Environment, 2024)

An analysis of culture-based methods used for the detection and isolation of Salmonella spp., Escherichia coli, and Enterococcus spp. from surface water: A systematic review - Betty R. McConn; Autumn L. Kraft; Lisa M. Durso; Abasiofiok M. Ibekwe; Jonathan G. Frye; James E. Wells; Elizabeth M. Tobey; Stephanie Ritchie; Clinton F. Williams; Kimberly L. Cook; Manan Sharma (Science of The Total Environment, 2024)

Detrending tree-ring widths in closed-canopy forests for climate and disturbance history reconstructions - Daniel L. Druckenbrod; Edward R. Cook; Neil Pederson; Dario Martin-Benito (Dendrochronologia, 2024)

Correction to: Drought and deluge: the recurrence of hydroclimate extremes during the past 600 years in eastern Australia’s Natural Resource Management (NRM) clusters - Jonathan G. Palmer; Danielle Verdon‑Kidd; Kathryn J. Allen; Philippa Higgins; Benjamin I. Cook; Edward R. Cook; Christian S. M. Turney; Patrick J. Baker (Natural Hazards, 2024)

Search for source of invasive-range populations of a haplodiploid pest species reveals Wolbachia-driven mitochondrial selective sweep in native range - Alihan Katlav; Duong T. Nguyen; Asha Chhagan; Lisa Jamieson; Alexander R. Robertson; Jodie Cheesman; Stewart Learmonth; Piotr Trębicki; James M. Cook; Markus Riegler (Journal of Pest Science, 2024)

Seasonal trends in marine heatwaves highlight vulnerable coastal ecoregions and historic change points in New Zealand - Shinae Montie; François Thoral; Robert O. Smith; Felix Cook; Leigh W. Tait; Matthew H. Pinkerton; David R. Schiel; Mads S. Thomsen (New Zealand Journal of Marine and Freshwater Research, 2024)
Marine heatwaves (MHWs) have increased worldwide in intensity, frequency, and duration, often with severe impacts on ecologically and socio‐economically important coastal habitats. Most MHW studies have focused on summer events in specific regions or global open‐water analyses with little consideration to seasonality or spatial biogeography of the nearshore zone. We address this research gap by analysing changes to MHWs across seasons and ecoregions, within 12 nautical miles (NM) of New Zealand's coastline, an area with high biodiversity and endemism. We used season‐specific linear trend analysis with temporal breakpoints between 1982 and 2021 to identify the number of MHW events and MHW days, and mean, maximum, and cumulative intensity of MHWs for New Zealand coastal ecoregions. Across ecoregions, 69.5% of 200 trend analyses increased significantly whereas the remaining 30.5% were unaffected. For the significant increases, temporal breakpoints occurred between 1994 and 2012. We conclude that MHWs have become stronger, longer and more frequent across coastal New Zealand, but with some variability within and between regions. Our trend‐analyses could enable retrospective analyses of biological tipping‐points and inform management practices that may enhance the resilience of ecoregions yet to face MHW breakpoints or those in the initial stages of major climatic changes.

Plasma per- and polyfluoroalkyl substance mixtures during pregnancy and duration of breastfeeding in the New Hampshire birth cohort study - Megan E. Romano; Lisa G. Gallagher; George Price; Kathryn A. Crawford; Rachel Criswell; Emily Baker; Julianne Cook Botelho; Antonia M. Calafat; Margaret R. Karagas (International Journal of Hygiene and Environmental Health, 2024)

A tale of 3 dwarf planets: Ices and organics on Sedna, Gonggong, and Quaoar from JWST spectroscopy - J.P. Emery; I. Wong; R. Brunetto; J.C. Cook; N. Pinilla-Alonso; J.A. Stansberry; B.J. Holler; W.M. Grundy; S. Protopapa; A.C. Souza-Feliciano; E. Fernández-Valenzuela; J.I. Lunine; et al. (Icarus, 2024)

Extraordinary levels of per- and polyfluoroalkyl substances (PFAS) in vertebrate animals at a New Mexico desert oasis: Multiple pathways for wildlife and human exposure - Christopher C. Witt; Chauncey R. Gadek; Jean-Luc E. Cartron; Michael J. Andersen; Mariel L. Campbell; Marialejandra Castro-Farías; Ethan F. Gyllenhaal; Andrew B. Johnson; Jason L. Malaney; Kyana N. Montoya; Andrew Patterson; Nicholas T. Vinciguerra; et al. (Environmental Research, 2024)

Consequences of pollen defense compounds for pollinators and antagonists in a pollen‐rewarding plant - Sébastien Rivest; Stephen T. Lee; Daniel Cook; Jessica R. K. Forrest (Ecology, 2024)
Plants produce an array of defensive compounds with toxic or deterrent effects on insect herbivores. Pollen can contain relatively high concentrations of such defense compounds, but the causes and consequences of this enigmatic phenomenon remain mostly unknown. These compounds could potentially protect pollen against antagonists but could also reduce flower attractiveness to pollinators. We combined field observations of the pollen‐rewarding Lupinus argenteus with chemical analysis and laboratory assays to test three hypotheses for the presence of pollen defense compounds: (1) these compounds are the result of spillover from adjacent tissues, (2) they protect against pollen thieves, and (3) they act as antimicrobial compounds. We also tested whether pollen defense compounds affect pollinator behavior. We found a positive relationship between alkaloid concentrations in pollen and petals, supporting the idea that pollen defense compounds partly originate from spillover. However, pollen and petals exhibited quantitatively (but not qualitatively) distinct alkaloid profiles, suggesting that plants can adjust pollen alkaloid composition independently from that of adjacent tissues. We found no relationship between pollen alkaloid concentration and the abundance of pollen thieves in Lupinus flowers. However, pollen alkaloids were negatively associated with bacterial abundance. Finally, plants with more alkaloids in their pollen received more pollinator visits, but these visits were shorter, resulting in no change in the overall number of flowers visited. We propose that pollen defense compounds are partly the result of spillover from other tissues, while they also play an antimicrobial role. The absence of negative effects of these compounds on pollinator visitation likely allows their maintenance in pollen at relatively high concentrations. Taken together, our results suggest that pollen alkaloids affect and are mediated by the interplay of multiple interactions.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Mid-to Late Holocene East Antarctic ice-core tephrochronology: Implications for reconstructing volcanic eruptions and assessing their climatic impacts over the last 5,500 years - Peter M. Abbott; Joseph R. McConnell; Nathan J. Chellman; Sepp Kipfstuhl; Maria Hörhold; Johannes Freitag; Eliza Cook; William Hutchison; Michael Sigl (Quaternary Science Reviews, 2024)

Moderate D/H ratios in methane ice on Eris and Makemake as evidence of hydrothermal or metamorphic processes in their interiors: Geochemical analysis - Christopher R. Glein; William M. Grundy; Jonathan I. Lunine; Ian Wong; Silvia Protopapa; Noemi Pinilla-Alonso; John A. Stansberry; Bryan J. Holler; Jason C. Cook; Ana Carolina Souza-Feliciano (Icarus, 2024)

Altered vacuole membrane protein 1 (VMP1) expression is associated with increased NLRP3 inflammasome activation and mitochondrial dysfunction - Stephanie R. Zack; Meghana Venkatesan; Roman Nikolaienko; Ben Cook; Ronald Melki; Aleksey V. Zima; Edward M. Campbell (Inflammation Research, 2024)

Ruminant metabolism of zygacine, the major toxic alkaloid in foothill death camas (Zigadenus paniculatus) - Stephen T. Lee; Clinton A. Stonecipher; Benedict T. Green; Kevin D. Welch; Dale R. Gardner; Daniel Cook (Toxicon, 2024)

Measurement of D/H and 13C/12C ratios in methane ice on Eris and Makemake: Evidence for internal activity - W.M. Grundy; I. Wong; C.R. Glein; S. Protopapa; B.J. Holler; J.C. Cook; J.A. Stansberry; J.I. Lunine; A.H. Parker; H.B. Hammel; S.N. Milam; R. Brunetto; et al. (Icarus, 2024)

Forest soil classification for intensive pine plantation management: “Site Productivity Optimization for Trees” system - Rachel Cook; Thomas R. Fox; Howard Lee Allen; Chris W. Cohrs; Vicent Ribas-Costa; Andrew Trlica; Matthew Ricker; David R. Carter; Rafael Rubilar; Otávio Campoe; Timothy J. Albaugh; Pete Kleto; et al. (Forest Ecology and Management, 2024)

Effects of establishment fertilization on Landsat-assessed leaf area development of loblolly pine stands - Matthew N. House; Randolph H. Wynne; Valerie A. Thomas; Rachel L. Cook; David R. Carter; Jennifer H. Van Mullekom; Jim Rakestraw; Todd A. Schroeder (Forest Ecology and Management, 2024)

Drought and deluge: the recurrence of hydroclimate extremes during the past 600 years in eastern Australia’s Natural Resource Management (NRM) clusters - Jonathan G. Palmer; Danielle Verdon-Kidd; Kathryn J. Allen; Philippa Higgins; Benjamin I. Cook; Edward R. Cook; Christian S. M. Turney; Patrick J. Baker (Natural Hazards, 2024)
Recent extremes of flood and drought across Australia have raised questions about the recurrence of such rare events and highlighted the importance of understanding multi-decadal climate variability. However, instrumental records over the past century are too short to adequately characterise climate variability on multi-decadal and longer timescales or robustly determine extreme event frequencies and their duration. Palaeoclimate reconstructions can provide much-needed information to help address this problem. Here, we use the 600-year hydroclimate record captured in the eastern Australian and New Zealand Drought Atlas (ANZDA) to analyse drought and pluvial frequency trends for East Australian Natural Resource Management (NRM) clusters. This partitioning of the drought atlas grid points into recognised biophysical areas (i.e. NRM clusters) revealed their differences and similarities in drought intensity and pluvial events over time. We find sustained multi-decadal periods of a wet–dry geographic 'seesaw' between eastern to central and southern NRMs (e.g. 1550–1600 CE and 1700–1750 CE). In contrast, other periods reveal spatially consistent wetting (e.g. 1500–1550 CE) or drying (e.g. 1750–1800 CE). Emerging hot spot analysis further shows that some areas that appear naturally buffered from severe drought during the instrumental period have a greater exposure risk when the longer 600-year record is considered. These findings are particularly relevant to management plans when dealing with the impacts of climate extremes developed at regional scales. Our results demonstrate that integrating and extending instrumental records with palaeoclimate datasets will become increasingly important for developing robust and locally specific extreme event frequency information for managing water resources.

Transmission mode predicts coinfection patterns of insect‐specific viruses in field populations of the Queensland fruit fly - Stephen R. Sharpe; Jennifer L. Morrow; James M. Cook; Alexie Papanicolaou; Markus Riegler (Molecular Ecology, 2024)
Insect‐specific viruses (ISVs) can affect insect health and fitness, but can also interact with other insect‐associated microorganisms. Despite this, ISVs are often studied in isolation from each other, in laboratory populations. Consequently, their diversity, prevalence and associations with other viruses in field populations are less known, yet these parameters are important to understanding virus epidemiology. To help address this knowledge gap, we assessed the diversity, prevalence and coinfections of three ISVs (horizontally transmitted cripavirus, biparentally transmitted sigmavirus and maternally transmitted iflavirus) in 29 field populations of Queensland fruit fly, Australia's most significant horticultural pest, in the context of their different transmission modes. We detected new virus variant diversity. In contrast to the very high virus prevalence in laboratory populations, 46.8% of 293 field flies carried one virus and 4.8% had two viruses. Cripavirus and sigmavirus occurred in all regions, while iflavirus was restricted to subtropical and tropical regions. Cripavirus was most prevalent (37.5%), followed by sigmavirus (13.7%) and iflavirus (4.4%). Cripavirus coinfected some flies with either one of the two vertically transmitted viruses. However, sigmavirus did not coinfect individuals with iflavirus. Three different modelling approaches detected negative association patterns between sigmavirus and iflavirus, consistent with the absence of such coinfections in laboratory populations. This may be linked with their maternal transmission and the ineffective paternal transmission of sigmavirus. Furthermore, we found that, unlike sigmavirus and iflavirus, cripavirus load was higher in laboratory than field flies. Laboratory and mass‐rearing conditions may increase ISV prevalence and load due to increased transmission opportunities. We conclude that a combination of field and laboratory studies is needed to uncover ISV interactions and further our understanding of ISV epidemiology.

Visualization of radiographic mineral opacities in guinea pigs in the location of the bulbourethral glands may be underdiagnosed - Amanda D. Wong; Krista A. Keller; Anthony J. Cerreta; Kirstin Cook; Joanna K. Webb; Kenneth R. Welle; Martha A. Delaney; Audrey Billhymer (Journal of Exotic Pet Medicine, 2024)

Prospective cohort of pre- and post-diagnosis alcohol consumption and cigarette smoking on survival outcomes: an Alberta Endometrial Cancer Cohort Study - Renée L. Kokts-Porietis; Andria R. Morielli; Jessica McNeil; Jamie L. Benham; Kerry S. Courneya; Linda S. Cook; Christine M. Friedenreich (Cancer Causes & Control, 2024)

Horizon scanning of potential threats to high‐Arctic biodiversity, human health and the economy from marine invasive alien species: A Svalbard case study - Elizabeth J. Cottier‐Cook; Jude Bentley‐Abbot; Finlo R. Cottier; Dan Minchin; Sergej Olenin; Paul E. Renaud (Global Change Biology, 2024)
The high Arctic is considered a pristine environment compared with many other regions in the northern hemisphere. It is becoming increasingly vulnerable to invasion by invasive alien species (IAS), however, as climate change leads to rapid loss of sea ice, changes in ocean temperature and salinity, and enhanced human activities. These changes are likely to increase the incidence of arrival and the potential for establishment of IAS in the region. To predict the impact of IAS, a group of experts in taxonomy, invasion biology and Arctic ecology carried out a horizon scanning exercise using the Svalbard archipelago as a case study, to identify the species that present the highest risk to biodiversity, human health and the economy within the next 10 years. A total of 114 species, currently absent from Svalbard, recorded once and/or identified only from environmental DNA samples, were initially identified as relevant for review. Seven species were found to present a high invasion risk and to potentially cause a significant negative impact on biodiversity and five species had the potential to have an economic impact on Svalbard. Decapod crabs, ascidians and barnacles dominated the list of highest risk marine IAS. Potential pathways of invasion were also researched, the most common were found associated with vessel traffic. We recommend (i) use of this approach as a key tool within the application of biosecurity measures in the wider high Arctic, (ii) the addition of this tool to early warning systems for strengthening existing surveillance measures; and (iii) that this approach is used to identify high‐risk terrestrial and freshwater IAS to understand the overall threat facing the high Arctic. Without the application of biosecurity measures, including horizon scanning, there is a greater risk that marine IAS invasions will increase, leading to unforeseen changes in the environment and economy of the high Arctic.

A comparison of methods to detect low levels of Salmonella enterica in surface waters to support antimicrobial resistance surveillance efforts performed in multiple laboratories - Autumn L. Kraft; Jim E. Wells; Jonathan G. Frye; Abasiofiok M. Ibekwe; Lisa M. Durso; Lari Hiott; Cheryl East; Betty R. McConn; Alison M. Franklin; Laura A. Boczek; Jay L. Garland; Claudine Kabera; et al. (Science of The Total Environment, 2023)

Positive association of SARS-CoV-2 RNA concentrations in wastewater and reported COVID-19 cases in Singapore – A study across three populations - Yvonne Hui Min Wong; Jue Tao Lim; Jane Griffiths; Benjamin Lee; Dzulkhairul Maliki; Janelle Thompson; Michelle Wong; Sae-Rom Chae; Yee Leong Teoh; Zheng Jie Marc Ho; Vernon Lee; Alex R. Cook; et al. (Science of The Total Environment, 2023)

Examining the effects of soil entrainment during nuclear cloud rise on fallout predictions using a multiscale atmospheric modeling framework - Katherine A. Lundquist; Robert S. Arthur; Stephanie Neuscamman; Joseph P. Morris; Christian R. Scullard; Andrew W. Cook; Nathan G. Wimer; Peter Goldstein; Gregory D. Spriggs; Lee G. Glascoe; John S. Nasstrom (Journal of Environmental Radioactivity, 2023)

Dietary reconstruction based on stable isotopes and stature at Torre de Palma, a Late Roman/Late Antiquity site in southern Portugal - Mark R. Schurr; Mary Lucas Powell; Della Collins Cook; Michael MacKinnon; Maia M. Langley (Archaeological and Anthropological Sciences, 2023)

Neurodevelopmental outcomes in children and adults with Fetal Valproate Spectrum Disorder: A contribution from the ConcePTION project - M. Bluett-Duncan; D. Astill; R. Charbak; J. Clayton-Smith; S. Cole; P.A. Cook; J. Cozens; K. Keely; J. Morris; R. Mukherjee; E. Murphy; P. Turnpenny; et al. (Neurotoxicology and Teratology, 2023)

Drought conditioning of rhizosphere microbiome influences maize water use traits - Kelsey R. Carter; Abigael C. Nachtsheim; L. Turin Dickman; Eric R. Moore; Sangeeta Negi; John P. Heneghan; Anthony J. Sabella; Christina R. Steadman; Michaeline B. N. Albright; Christine M. Anderson-Cook; Louise H. Comas; Rose J. Harris; et al. (Plant and Soil, 2023)
Background and Aims Beneficial plant–microbe interactions can improve plant performance under drought; however, we know less about how drought-induced shifts in microbial communities affect plant traits. Methods We cultivated Zea mays in fritted clay with soil microbiomes originating from contrasting environments (agriculture or forest) under two irrigation treatments (well-watered or water limited). Using this design, we investigated whether water conditioning was carried forward through the microbiome to affect a subsequent plant cohort that was subjected to either a well-watered or water limited treatment. Results Regardless of the microbiome-origin, plants inoculated with a microbiome from a water limited legacy had traits that allowed them to avoid stress but conserve water. They produced longer roots to explore soil, generated greater soil dissolved organic carbon, potentially stimulating the microbiome, and slower soil water content loss during drought. A well-watered legacy resulted in plants that delayed permanent stomatal closure and higher photosynthetic nitrogen use efficiency. In plants with a forest-originated microbiome, a well-watered legacy and water treatment also resulted in higher rates of photosynthesis and stomatal conductance. Conclusion These results demonstrate that soil microbiomes can be developed to influence plant drought performance, impacting crop resilience, using short-term microbial conditioning.

Other Vegetables, Whole Fruit, Total Grains, and Sodium Intake Correlated to Vascular Responses from Butyrate - L. San Diego; H. Colleran; M. Cook; R. Claro Da Silva; T. Purdom; L. Toneygay (Journal of the Academy of Nutrition and Dietetics, 2023)

Development and Validation of an Abbreviated Child and Adult Food Security Scale for Use in Clinical and Research Settings in the United States - Ana Poblacion; Stephanie Ettinger de Cuba; Deborah A. Frank; Georgiana Esteves; Lindsey J. Rateau; Timothy C. Heeren; Sharon Coleman; Maureen M. Black; Diana B. Cutts; Félice Lê-Scherban; Eduardo R. Ochoa; Megan Sandel; et al. (Journal of the Academy of Nutrition and Dietetics, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

How do dynamic and time-dependent indoor temperature patterns impact on the health of office based workers? – A scoping review - Amelie Reitmayer; Kelly R. Johnstone; Cassandra Madigan; Margaret M. Cook; Sava Arsenijevic (Building and Environment, 2023)

Correction: Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2023)

Comparison of three reproductive management strategies for lactating dairy cows using combination of estrus detection or ovulation synchronization and Fixed-Timed Artificial Insemination - R. Vazquez Belandria; K. Denholm; P.T. Pepler; J.G. Cook; P. Pinho; F. Randi; L. Viora (Animal Reproduction Science, 2023)

The influence of complex matrices on method performance in extracting and monitoring for microplastics - Leah M. Thornton Hampton; Hannah De Frond; Kristine Gesulga; Syd Kotar; Wenjian Lao; Cindy Matuch; Stephen B. Weisberg; Charles S. Wong; Susanne Brander; Silke Christansen; Cayla R. Cook; Fangni Du; et al. (Chemosphere, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Adaptation constraints and prospects for future research priorities in lowland rice-based farming systems: learning experiences from Northwest Cambodia - Van Touch; Rebecca Cross; Clemens Grünbühel; Floris Van Ogtrop; Peter Ampt; Try Yorn; Robert John Martin; Brian R. Cook; Daniel K. Y. Tan (Environment, Development and Sustainability, 2023)
Sustainable agricultural development not only addresses global food insecurity but may also alleviate poverty by enriching the lives of millions of smallholder farmers. Improving the sustainability and profitability of agriculture where smallholders are dominant creates profound impacts because small landholding farmers produce approximately 70–80% of the global food. The need for a thorough understanding of the factors affecting farmers’ adoption of agricultural technologies and practices has been identified from extant literature as an important research gap. Responding to the research gap and need, this study examined the challenges that prevent farm households from adopting improved farming practices and/or technologies in Banteay Meanchey and Battambang provinces in Northwest Cambodia. A total of 524 rice producing farm household representatives were randomly selected from a household database maintained by the local government authorities. A mixed methods approach was used in the study including semi-structured interviews followed by in-depth interviews, field observations, and literature review. Farmers were found to be confronted with a range of challenges and concerns, including soil degradation, weeds, diseases, insect pests, high production costs, flooding, droughts, changing rainfall pattern, and unreliable rainfall distribution. The research findings demonstrate that improved crop production practices (e.g., adopting mechanised direct seeding methods of crop establishment, maintaining and improving soil health through crop residue retention, growing cover crops, etc.) and better resource use efficiency (e.g., reducing seeding rates to less than 100 kg/ha, being more strategic in the use of integrated nutrient, weed, and pest management strategies, etc.) can be a starting point for sustainable intensification of rice production. This transition towards intensifying paddy production sustainably may become even more effective through a clear understanding of local contexts, farm household characteristics, available resources, and the farm management practices and constraints. We observed that farmers and their associations have yet to be fully recognised as partners and actors in Cambodia. Instead, they tend to be viewed as beneficiaries and recipients of improved practices and technologies. We, therefore, propose that farmers and their associations be acknowledged and included in a process of co-creation of knowledge-practices. Such partnerships will enable the inclusion of factors (e.g., production costs, production risks, complexity and practicability of implementations, product market and prices, etc.) shown to influence farmers’ adoption of innovative farming practices and technologies. The original contribution of this article is a real-world account of the constraints and limitations experienced by smallholder rice farmers in Cambodia, which are connected to future research and development priorities in the region.

Metals and per- and polyfluoroalkyl substances mixtures and birth outcomes in the New Hampshire Birth Cohort Study: Beyond single-class mixture approaches - Gyeyoon Yim; Glen McGee; Lisa Gallagher; Emily Baker; Brian P. Jackson; Antonia M. Calafat; Julianne Cook Botelho; Diane Gilbert-Diamond; Margaret R. Karagas; Megan E. Romano; Caitlin G. Howe (Chemosphere, 2023)

Acute physiological responses to steady-state arm cycling ergometry with and without blood flow restriction - Mikaela L. Frechette; Brendan R. Scott; Ann-Maree Vallence; Summer B. Cook (European Journal of Applied Physiology, 2023)

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

Are we there yet? Management baselines and biodiversity indicators for the protection and restoration of subtidal bivalve shellfish habitats - Jose M. Fariñas-Franco; Robert L. Cook; Fiona R. Gell; Dan B. Harries; Natalie Hirst; Flora Kent; Rebecca MacPherson; Colin Moore; James M. Mair; Joanne S. Porter; William G. Sanderson (Science of The Total Environment, 2023)

Assay measurement of gaseous UF6 using femtosecond laser-induced breakdown spectroscopy in the 424.4 nm spectral region - Benjamin S. Jordan; Jason D. Readle; Jeffrey R. Cooper; Matthew Cook; Jason P. Hayward; J. Daniel Hartman; Dean Forrest; Howard L. Hall (Annals of Nuclear Energy, 2023)

The Diversity of Eucheumatoid Seaweed Cultivars in the Philippines - Richard V. Dumilag; Bea A. Crisostomo; Zae-Zae A. Aguinaldo; Lourie Ann R. Hinaloc; Lawrence M. Liao; Hilly Ann Roa-Quiaoit; Floredel Dangan-Galon; Giuseppe C. Zuccarello; Marie-Laure Guillemin; Juliet Brodie; Elizabeth J. Cottier-Cook; Michael Y. Roleda (Reviews in Fisheries Science & Aquaculture, 2023)

Estimation of individual stem volume and diameter from segmented UAV laser scanning datasets in Pinus taeda L. plantations - Matthew J. Sumnall; Timothy J. Albaugh; David R. Carter; Rachel L. Cook; W. Cully Hession; Otávio C. Campoe; Rafael A. Rubilar; Randolph H. Wynne; Valerie A. Thomas (International Journal of Remote Sensing, 2023)

Preclinical efficacy and safety of novel SNAT against SARS-CoV-2 using a hamster model - Lok R. Pokhrel; Frank Williams; Paul P. Cook; Dorcas O’Rourke; Gina Murray; Shaw M. Akula (Drug Delivery and Translational Research, 2022)

The contribution of respiratory and hearing protection use to psychological distress in the workplace: a scoping review - Richard Leung; Margaret M. Cook; Mike F. Capra; Kelly R. Johnstone (International Archives of Occupational and Environmental Health, 2022)
Objective Workers from various industries use personal protective equipment (PPE) including masks, respirators, and hearing protection to reduce their exposures to workplace hazards. Many studies have evaluated the physiological impacts of PPE use, but few have assessed the psychological impacts. The aim of the present study was to carry out a scoping review to compile existing evidence and determine the extent of knowledge on workplace mask, respirator or hearing protection use as a psychosocial hazard (stressor) that could result in a stress response and potentially lead to psychological injury. Methods The scoping review followed recognized methods and was conducted using Ovid Emcare, PubMed, Sage Journals, ScienceDirect, Scopus, SpringerLink, Google Scholar and preprint databases (OSF Preprints and medRxiv). Articles on the stressors associated with the use of masks, respirators, and hearing protection were included. The extracted data included author(s) name, year of publication, title of article, study design, population data, stressors assessed, and key findings. Results We retrieved 650 articles after removal of duplicates, of which 26 were deemed eligible for inclusion for review. Identified factors associated with PPE use that could potentially create a stress response were identified: communication impacts, physical impacts, psychological illness symptoms, cognitive impacts, and perceived PPE-related impacts. Evidence for respirators suggest that there may be psychological injury associated with their use. However, hearing protection appears to have a protective effect in reducing psychological symptoms such as anxiety, depression, and aggression. Conclusions Mask or respirator use may lead to an increase in work-related stress. Whereas hearing protection may have protective effects against psychological symptoms and improves speech intelligibility. More research is needed to better understand potential psychosocial impacts of mask, respirator and/or hearing protection use.

Grazing, egg production and carbon budgets for Calanus finmarchicus across the Fram Strait - Holly E. Jenkins; Florence Atherden; Kathryn B. Cook; Thomas R. Anderson; Barry Thornton; Elaine Mitchell; Elodie Jacob; Daniel J. Mayor (Frontiers in Marine Science, 2022)
Calanoid copepods comprise around 90% of Arctic zooplankton biomass and are fundamental to the ecological and biogeochemical functioning of high-latitude pelagic ecosystems. They accumulate lipid reserves during the productive months and represent an energy-rich food source for higher trophic levels. Rapidly changing climate in the Arctic may alter the quantity and composition of the food environment for one of the key copepod species, Calanus finmarchicus , with as yet unquantified effects on its production. Here we present rates of feeding and egg production in female C. finmarchicus exposed to the range of feeding conditions encountered across the Fram Strait in May/June 2018. Carbon (C) budgets were constructed and used to examine the relationship between feeding and growth (= egg production) in these animals. C-specific ingestion rates (mean ± standard deviation) were highly variable, ranging from 0.015 ± 0.004 to 0.645 ± 0.017 day -1 (mean = 0.295 ± 0.223 day -1 ), and were positively correlated with food availability. C-specific egg production rates ranged from 0.00 to 0.049 day -1 (mean = 0.012 ± 0.011) and were not correlated with either food availability or ingestion rate. Calculated gross growth efficiencies (GGE: growth/ingestion) were low, 0.12 ± 0.13 (range = 0.01 to 0.39). The assembled C budgets indicate that the average fraction of ingested food that was surplus to the requirements for egg production, respiration and losses to faecal pellets was 0.17 ± 0.42. We suggest that this excess occurred, at least in part, because many of the incubated females were still undergoing the energetically (C-) expensive process of gonad maturation at the time of sampling, an assertion that is supported by the relatively high C:N (nitrogen) ratios of the incubated females, the typically low egg production rates, and gonad maturation status. Ontogenetic development may thus explain the large variability seen in the relationship between egg production and ingestion. The apparently excessive ingestion rates may additionally indicate that recently moulted females must acquire additional N via ingestion to complete the maturation process and begin spawning. Our results highlight the need for improved fundamental understanding of the physiology of high-latitude copepods and its response to environmental change.

Influence of coating type, colour, and deployment timing on biofouling by native and non-native species in a marine renewable energy context - Christopher R. Nall; Marie-Lise Schläppy; Elizabeth J. Cottier-Cook; Andrew J. Guerin (Biofouling, 2022)

A Case Study of Large Floodplain River Restoration: Two Decades of Monitoring the Merwin Preserve and Lessons Learned through Water Level Fluctuations and Uncontrolled Reconnection to a Large River - Levi E. Solomon; Andrew F. Casper; Kristopher A. Maxson; James T. Lamer; Trent W. Ford; K. Douglass Blodgett; Tharran Hobson; Denim Perry; Nathan T. Grider; Rob B. Hilsabeck; Thad R. Cook; Kevin S. Irons; et al. (Wetlands, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Carbon and Lipid Contents of the Copepod Calanus finmarchicus Entering Diapause in the Fram Strait and Their Contribution to the Boreal and Arctic Lipid Pump - Geraint A. Tarling; Anna Belcher; Mayleen Blackwell; Claudia Castellani; Kathryn Barbara Cook; Finlo R. Cottier; Victoria Dewar-Fowler; Jennifer J. Freer; Laura Gerrish; Magnus L. Johnson; Kim S. Last; Penelope Kate Lindeque; et al. (Frontiers in Marine Science, 2022)
The boreal copepod Calanus finmarchicus sequesters substantial amounts of carbon (C) in the deep layers of the North Atlantic Ocean through their contribution to the “lipid pump.” This pump is driven by these zooplankton descending from the surface layers to spend prolonged periods at depth during which time they metabolise substantial lipid reserves and a fraction suffer mortality. C. finmarchicus is principally a boreal species but is expatriated by currents flowing northwards into Arctic regions such as the Fram Strait, where it is now able to complete its life cycle. We considered how this expansion to its distributional range adds to the estimated magnitude of the lipid pump. Field sampling in the Fram Strait found C. finmarchicus abundance to be spatially variable with high values, equivalent to those reported for core distributional areas further south, found mainly in the eastern region. Lipid reserve levels were sufficient for many individuals to survive the overwintering period and reproduce the following spring. In accordance with abundance patterns, lipid pump magnitude was greater in the Eastern Fram Strait (2.04 g C m −2 year −1 ) compared to the Western Fram Strait (0.33 g C m −2 year −1 ). At least for the eastern region, these rates are similar to those reported for this species elsewhere (average of 4.35 g C m −2 year −1 ). When extrapolated to the wider spatial area of the Fram Strait, the lipid pump generated by this species in this ocean sector amounts to 0.3 Mt C year −1 . Although constituting a modest proportion of the total C. finmarchicus lipid pump of 19.3 Mt C year −1 , it indicates that the continued northwards expansion of this species will act to increase the size of its lipid pump, which may counteract that lost through the northwards retreat of its Arctic congeners, Calanus glacialis and Calanus hyperboreus .

Biomass Turnover Rates in Metabolically Active and Inactive Marine Calanoid Copepods - Daniel J. Mayor; Kathryn B. Cook; Barry Thornton; Florence Atherden; Geraint A. Tarling; Thomas R. Anderson (Frontiers in Marine Science, 2022)
Lipid-storing copepods are fundamental to the functioning of marine ecosystems, transferring energy from primary producers to higher trophic levels and sequestering atmospheric carbon (C) in the deep ocean. Quantifying trophic transfer and biogeochemical cycling by copepods requires improved understanding of copepod metabolic rates in both surface waters and during lipid-fueled metabolism over winter. Here we present new biomass turnover rates of C and nitrogen (N) in Calanoides acutus , Calanoides natalis , Calanus glacialis and Calanus hyperboreus alongside published data for Calanus finmarchicus and Calanus pacificus . Turnover rates in metabolically active animals, normalised to 10°C, ranged between 0.007 – 0.105 d -1 and 0.004 – 0.065 d -1 for C and N, respectively. Turnover rates of C were typically faster than those for N, supporting the understanding that non-protein C, e.g. lipid, is catabolised faster than protein. Re-analysis of published data indicates that inactive, overwintering C. finmarchicus turn over wax ester lipids at a rate of 0.0016 d -1 . These and other basal rate data will facilitate the mechanistic representation of copepod physiology in global biogeochemical models, thereby reducing uncertainties in our predictions of future ocean ecosystem functioning and C sequestration.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

The Open-Ocean Gulf of Mexico After Deepwater Horizon: Synthesis of a Decade of Research - Tracey T. Sutton; Rosanna J. Milligan; Kendra Daly; Kevin M. Boswell; April B. Cook; Maëlle Cornic; Tamara Frank; Kaitlin Frasier; Daniel Hahn; Frank Hernandez; John Hildebrand; Chuanmin Hu; et al. (Frontiers in Marine Science, 2022)
The scale of the Deepwater Horizon disaster was and is unprecedented: geographic extent, pollutant amount, countermeasure scope, and of most relevance to this Research Topic issue, range of ecotypes affected. These ecotypes include coastal/nearshore, continental shelf, deep benthic, and open-ocean domains, the last of which is the subject of this synthesis. The open-ocean ecotype comprises ~90% of the volume of the Gulf of Mexico. The exact percentage of this ecotype contaminated with toxins is unknown due to its three-dimensional nature and dynamics, but estimates suggest that the footprint encompassed most of its eastern half. Further, interactions between the water column and the deep benthos may be persistent, making this synthesis one of time (a decade) rather than event conclusion. Here we examine key elements of the open-ocean ecosystem, with emphasis on vulnerability and resilience. Of paramount importance relative to the Gulf nearshore and shelf ecotypes, pre-disaster baseline data were lacking for most of the fauna. In such cases, inferences were drawn from post-disaster assessments. Both phytoplankton and mesozooplankton vulnerabilities were quite high, but resilience appeared equally so. The phytoplankton situation was a bit more complex in that toxin-imposed reductions may have been offset by nutrient injection via high freshwater discharge in 2010. Intermediate trophic levels exhibited population-level depressions, ostensibly due to high vulnerability and low resilience. Apex predator impacts were variable. Certain large epipelagic fishes may have avoided the highest concentrations of hydrocarbons/dispersant, and thus larval abundances returned to pre-disaster levels of variability and abundance within a few years after a steep initial decline. Oceanic cetaceans, particularly shallow-diving stenellid dolphins, did not appear to avoid oiled waters and exhibited strong declines in the northern Gulf. Given that population declines of many open-ocean taxa appear to be ongoing a decade later, we conclude that this largest of Gulf ecosystem components, like its deep-benthic counterpart, is as fragile as it is voluminous. This is particularly concerning given the rapid, and likely irreversible, shift to deeper waters by the US and Mexican oil industries in concert with the higher likelihood of accidents with increasing platform depth.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Rapid radiation of Southern Ocean shags in response to receding sea ice - Nicolas J. Rawlence; Alexander T. Salis; Hamish G. Spencer; Jonathan M. Waters; Lachie Scarsbrook; Kieren J. Mitchell; Richard A. Phillips; Luciano Calderón; Timothée R. Cook; Charles‐André Bost; Ludovic Dutoit; Tania M. King; et al. (Journal of Biogeography, 2022)
Aim Understanding how natural populations respond to climatic shifts is a fundamental goal of biological research in a fast‐changing world. The Southern Ocean represents a fascinating system for assessing large‐scale climate‐driven biological change, as it contains extremely isolated island groups within a predominantly westerly, circumpolar wind and current system. Blue‐eyed shags represent a paradoxical seabird radiation—a circumpolar distribution implies strong dispersal capacity yet their species‐rich nature suggests local adaptation and isolation. Here we attempt to resolve this paradox in light of the history of repeated cycles of climate change in the Southern Ocean. Location Southern Ocean. Taxa 16 species and subspecies of blue‐eyed shags (Phalacrocoracidae; Leucocarbo spp.). Methods We use mitochondrial and nuclear sequence data from individuals across the geographical range of the genus to conduct the first comprehensive, time‐calibrated phylogenetic analyses and ancestral‐range biogeographical reconstructions of the blue‐eyed shags. Results The origins of many island‐endemic lineages are remarkably recent, consistent with a recent high‐latitude circumpolar radiation in the Pliocene or Early Pleistocene. This recent sub‐Antarctic expansion contrasts with significantly deeper lineages detected in South America and, to a lesser extent, New Zealand. These regions, particularly South America, acted as glacial refugia and sources for multiple waves of post‐glacial dispersal. Main conclusions The blue‐eyed shag paradox is resolved, with at least two waves of dispersal, linked to interglacial cycles, explaining the current distribution and diversity. Descendants of a Pliocene or Early Pleistocene wave of dispersal out of South America survive in the New Zealand region. In contrast, taxa distributed on sub‐Antarctic islands originated much later, possibly since the Last Glacial Maximum. Blue‐eyed shags therefore represent a powerful model system—comprising several natural replicates—for studying the early stages of founder‐event speciation and adaptation in a Southern‐Ocean bird group.

Cooperative breeding and the emergence of multilevel societies in birds - Ettore Camerlenghi; Alexandra McQueen; Kaspar Delhey; Carly N. Cook; Sjouke A. Kingma; Damien R. Farine; Anne Peters (Ecology Letters, 2022)
Multilevel societies (MLSs), where social levels are hierarchically nested within each other, are considered one of the most complex forms of animal societies. Although thought to mainly occurs in mammals, it is suggested that MLSs could be under‐detected in birds. Here, we propose that the emergence of MLSs could be common in cooperatively breeding birds, as both systems are favoured by similar ecological and social drivers. We first investigate this proposition by systematically comparing evidence for multilevel social structure in cooperative and non‐cooperative birds in Australia and New Zealand, a global hotspot for cooperative breeding. We then analyse non‐breeding social networks of cooperatively breeding superb fairy‐wrens ( Malurus cyaneus ) to reveal their structured multilevel society, with three hierarchical social levels that are stable across years. Our results confirm recent predictions that MLSs are likely to be widespread in birds and suggest that these societies could be particularly common in cooperatively breeding birds.

Changing hydroclimate dynamics and the 19th to 20th century wetting trend in the English Channel region of northwest Europe - Serena R. Scholz; Richard Seager; Mingfang Ting; Yochanan Kushnir; Jason E. Smerdon; Benjamin I. Cook; Edward R. Cook; Seung Hun Baek (Climate Dynamics, 2022)

The Alberta moving beyond breast cancer (AMBER) cohort study: baseline description of the full cohort - Christine M. Friedenreich; Jeff K. Vallance; Margaret L. McNeely; S. Nicole Culos-Reed; Charles E. Matthews; Gordon J. Bell; John R. Mackey; Karen A. Kopciuk; Leanne Dickau; Qinggang Wang; Diane Cook; Stephanie Wharton; et al. (Cancer Causes & Control, 2022)
Purpose The Alberta Moving Beyond B r east Cancer (AMBER) Study is an ongoing prospective cohort study investigating how direct measures of physical activity (PA), sedentary behavior (SB), and health-related fitness (HRF) are associated with survival after breast cancer. Methods Women in Alberta with newly diagnosed stage I (≥ T1c) to IIIc breast cancer were recruited between 2012 and 2019. Baseline assessments were completed within 90 days of surgery. Measurements included accelerometers to measure PA and SB; a graded treadmill test with gas exchange analysis to measure cardiorespiratory fitness (VO 2peak ); upper and lower body muscular strength and endurance; dual-X-ray absorptiometry to measure body composition; and questionnaires to measure self-reported PA and SB. Results At baseline, the 1528 participants’ mean age was 56 ± 11 years, 59% were post-menopausal, 62% had overweight/obesity, and 55% were diagnosed with stage II or III disease. Based on device measurements, study participants spent 8.9 ± 1.7 h/day sedentary, 4.4 ± 1.2 h/day in light-intensity activity, 0.9 ± 0.5 h/day in moderate-intensity activity, and 0.2 ± 0.2 h/day in vigorous-intensity activity. For those participants who reached VO 2peak , the average aerobic fitness level was 26.6 ± 6 ml/kg/min. Average body fat was 43 ± 7.1%. Conclusion We have established a unique cohort of breast cancer survivors with a wealth of data on PA, SB, and HRF obtained through both direct and self-reported measurements. Study participants are being followed for at least ten years to assess all outcomes after breast cancer. These data will inform clinical and public health guidelines on PA, SB, and HRF for improving breast cancer outcomes.

Can a key boreal Calanus copepod species now complete its life-cycle in the Arctic? Evidence and implications for Arctic food-webs - Geraint A. Tarling; Jennifer J. Freer; Neil S. Banas; Anna Belcher; Mayleen Blackwell; Claudia Castellani; Kathryn B. Cook; Finlo R. Cottier; Malin Daase; Magnus L. Johnson; Kim S. Last; Penelope K. Lindeque; et al. (Ambio, 2022)
The changing Arctic environment is affecting zooplankton that support its abundant wildlife. We examined how these changes are influencing a key zooplankton species, Calanus finmarchicus , principally found in the North Atlantic but expatriated to the Arctic. Close to the ice-edge in the Fram Strait, we identified areas that, since the 1980s, are increasingly favourable to C. finmarchicus . Field-sampling revealed part of the population there to be capable of amassing enough reserves to overwinter. Early developmental stages were also present in early summer, suggesting successful local recruitment. This extension to suitable C. finmarchicus habitat is most likely facilitated by the long-term retreat of the ice-edge, allowing phytoplankton to bloom earlier and for longer and through higher temperatures increasing copepod developmental rates. The increased capacity for this species to complete its life-cycle and prosper in the Fram Strait can change community structure, with large consequences to regional food-webs.

Effect of varied unmanned aerial vehicle laser scanning pulse density on accurately quantifying forest structure - Matthew J. Sumnall; Timothy J. Albaugh; David R. Carter; Rachel L. Cook; W. Cully Hession; Otávio C. Campoe; Rafael A. Rubilar; Randolph H. Wynne; Valerie A. Thomas (International Journal of Remote Sensing, 2022)

Eucalyptus grandis Response to Calcium Fertilization in Colombia - Zach S Grover; Rachel L Cook; Marcela Zapata; J Byron Urrego; Timothy J Albaugh; Ariel Zelaya; Tomasz Ozyhar; Rafael Rubilar; David R Carter; Otávio C Campoe (Forest Science, 2021)
Calcium (Ca) is a critical plant nutrient typically applied at the time of planting in intensive Eucalyptus plantations in South America. At two sites in Colombia, we examined (1) calcium source by comparing growth after application of 100 kg ha−1 elemental Ca as lime or as pelletized highly reactive calcium fertilizer (HRCF) compared to a no application control, and (2) Ca rate by applying 0, 100, 200, and 400 kg ha−1 elemental Ca as HRCF with the addition of nitrogen, phosphorus, potassium, sulfur, and boron (NPKSB). We assessed height, diameter, and volume after 12 and 24 months. There were no growth differences from Ca source at the 100 kg ha−1 rate. We found increased volume after 24 months at the “Popayan” site with 200 and 400 kg ha−1 Ca HRCF+NPKSB treatments (112 and 113 m3 ha−1, respectively) compared to control (92 m3 ha−1), a 22% increase. In contrast, volume did not differ after 24 months at the “Darien” site, ranging from 114 m3 ha−1 in the 0 kg ha−1 Ca HRCF+NPKSB treatment to 98 m3 ha−1 in the control. Differences in response are likely due to soil characteristics, such as organic matter, emphasizing the importance of identifying site-specific nutrient deficiencies.

Financial Returns for Biomass on Short-Rotation Loblolly Pine Plantations in the Southeastern United States - Andrew Trlica; Rachel L Cook; Timothy J Albaugh; Rajan Parajuli; David R Carter; Rafael A Rubilar (Forest Science, 2021)
Rising demand for renewable energy has created a potential market for biomass from short-rotation pine plantations in the southeastern United States. Site preparation, competition control, fertilization, and enhanced seedling genotypes offer the landowner several variables for managing productivity, but their combined effects on financial returns are unclear. This study estimated returns from a hypothetical 10-year biomass harvest in loblolly pine plantation using field studies in the Coastal Plain of North Carolina and the Virginia Piedmont testing combinations of tree genotype, planting density, and silviculture. Although enhanced varietal genotypes could yield more biomass, open-pollinated seedlings at 1,236–1,853 trees ha−1 under operational silviculture had the greatest returns at both sites, with mean whole-tree internal rates of return of 8.3%–9.9% assuming stumpage equal to current pulpwood prices. At a 5% discount rate, break-even whole-tree stumpage at the two sites in the optimal treatments was $8.72–$9.92 Mg−1, and break-even yield was 175–177 Mg ha−1 (roughly 18 Mg ha−1 yr−1 productivity), although stumpage and yield floors were higher if only stem biomass was treated as salable. Dedicated short-rotation loblolly biomass plantations in the region are more likely to be financially attractive when site establishment and maintenance costs are minimized.

Geographic variation of mercury in breeding tidal marsh sparrows of the northeastern United States - Christopher J. Sayers; Mackenzie R. Roeder; Lindsay M. Forrette; Daniel Roche; Gaetan L. B. Dupont; Sam E. Apgar; Alison R. Kocek; Alexandra M. Cook; W. Gregory Shriver; Chris S. Elphick; Brian Olsen; David N. Bonter (Ecotoxicology, 2021)

Trace Element Patterns in Otoliths: The Role of Biomineralization - Karin Hüssy; Karin E. Limburg; Hélène de Pontual; Oliver R. B. Thomas; Philip K. Cook; Yvette Heimbrand; Martina Blass; Anna M. Sturrock (Reviews in Fisheries Science & Aquaculture, 2021)

Complement activation in IgA nephropathy - Nicholas R. Medjeral-Thomas; H. Terence Cook; Matthew C. Pickering (Seminars in Immunopathology, 2021)
IgA nephropathy pathogenesis is incompletely understood, and this limits the development of disease-specific biomarkers and effective therapies. Evidence of complement activity in IgA nephropathy is well established. However, a growing body of research indicates complement activity is an important contributor to IgA nephropathy pathology. In particular, multiple associations have been identified between complement alternative, lectin and terminal pathway proteins and IgA nephropathy severity. Recently, we have also gained insight into possible mechanisms that could link glomerular IgA deposition, complement activity, glomerular inflammation and disease severity. Ongoing clinical trials of therapeutic complement inhibitors will provide insight into the importance of complement activity to IgA nephropathy pathogenesis. Further research into mechanisms of complement activity is essential to improving our understanding and management of patients with IgA nephropathy.

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Seaweed aquaculture: a preliminary assessment of biosecurity measures for controlling the ice-ice syndrome and pest outbreaks of a Kappaphycus farm - Cicilia S. B. Kambey; Iona Campbell; Elizabeth J. Cottier-Cook; Adibi R. M. Nor; Azhar Kassim; Ahemad Sade; Phaik E. Lim (Journal of Applied Phycology, 2021)
The application of biosecurity in seaweed aquaculture plays an important role in reducing the impact of disease and pest outbreaks. The continuous occurrence of seaweed pests including the macroalgal epiphytes, epi-endophytic filamentous algae and biofilms on Kappaphycus farms may also potentially induce further incidences of the ice-ice syndrome. In this study, on-farm biosecurity management measures were tested on the commercially grown seaweeds Kappaphycus malesianus and Kappaphycus alvarezii during peak ice-ice season at Gallam-Gallam Village, Sabah, Malaysia. The investigation was focused on preventative control measures including the early detection of the ice-ice syndrome and pests through propagule health checks, regular cleaning of the crop thallus and associated long-line ropes and monitoring of the environment. Farm procedures and practices were also assessed in terms of their biosecurity ‘risk’ using the hazard analysis and critical control point (HCCAP) approach. Observations were replicated in two different farm management systems; one system adopted routine biosecurity measures and the other had no biosecurity measures. The results showed that the ice-ice syndrome and pest outbreak was significantly decreased by 60–75% for K. malesianus and 29–71% for K. alvarezii at the farm which adopted the routine biosecurity measures compared with the no biosecurity treatment. The biosecurity measures also significantly improved growth rate and seaweed quality. The infection levels of the epi-endophyte Melanothamnus sp. contributed to the ice-ice syndrome in K. malesianus , whilst the epiphyte coverage was correlated to the ice-ice incidence in K. alvarezii . This study provides the first evidence of biosecurity management measures significantly decreasing the incidence of the ice-ice syndrome and pests on a commercial seaweed farm.

Megadroughts and pluvials in southwest Australia: 1350–2017 CE - Alison J. O’Donnell; W. Lachlan McCaw; Edward R. Cook; Pauline F. Grierson (Climate Dynamics, 2021)
Declining winter rainfall coupled with recent prolonged drought poses significant risks to water resources and agriculture across southern Australia. While rainfall declines over recent decades are largely consistent with modelled climate change scenarios, particularly for southwest Australia, the significance of these declines is yet to be assessed within the context of long-term hydroclimatic variability. Here, we present a new 668-year (1350–2017 CE) tree-ring reconstruction of autumn–winter rainfall over inland southwest Australia. This record reveals that a recent decline in rainfall over inland southwest Australia (since 2000 CE) is not unusual in terms of either magnitude or duration relative to rainfall variability over the last seven centuries. Drought periods of greater magnitude and duration than those in the instrumental record occurred prior to 1900 CE, including two ‘megadroughts’ of > 30 years duration in the eighteenth and nineteenth centuries. By contrast, the wettest > decadal periods of the last seven centuries occurred after 1900 CE, making the twentieth century the wettest of the last seven centuries. We conclude that the instrumental rainfall record (since ~ 1900 CE) does not capture the full scale of natural hydroclimatic variability for inland southwest Australia and that the risk of prolonged droughts in the region is likely much higher than currently estimated.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Correction to: Biodiversity and Health in the Urban Environment - Melissa R. Marselle; Sarah J. Lindley; Penny A. Cook; Aletta Bonn (Current Environmental Health Reports, 2021)

Cardiac response to adrenergic stress differs by sex and across the lifespan - Aykhan Yusifov; Vikram E. Chhatre; Jacob M. Zumo; Ross F. Cook; Benjamin D. McNair; Emily E. Schmitt; Kathleen C. Woulfe; Danielle R. Bruns (GeroScience, 2021)

Novel Application of Photogrammetry to Quantify Fascicle Orientations of Female Cadaveric Pelvic Floor Muscles - Megan R. Routzong; Mark S. Cook; William Barone; Steven D. Abramowitch; Marianna Alperin (Annals of Biomedical Engineering, 2021)

Phosphate solubilization and multiple plant growth promoting properties of Mesorhizobium species nodulating chickpea from acidic soils of Ethiopia - Atsede Muleta; Kassahun Tesfaye; Tekle Haimanot Haile Selassie; Douglas R. Cook; Fassil Assefa (Archives of Microbiology, 2021)

Biodiversity and Health in the Urban Environment - Melissa R. Marselle; Sarah J. Lindley; Penny A. Cook; Aletta Bonn (Current Environmental Health Reports, 2021)
Purpose of review Biodiversity underpins urban ecosystem functions that are essential for human health and well-being. Understanding how biodiversity relates to human health is a developing frontier for science, policy and practice. This article describes the beneficial, as well as harmful, aspects of biodiversity to human health in urban environments. Recent findings Recent research shows that contact with biodiversity of natural environments within towns and cities can be both positive and negative to human physical, mental and social health and well-being. For example, while viruses or pollen can be seriously harmful to human health, biodiverse ecosystems can promote positive health and well-being. On balance, these influences are positive. As biodiversity is declining at an unprecedented rate, research suggests that its loss could threaten the quality of life of all humans. Summary A key research gap is to understand—and evidence—the specific causal pathways through which biodiversity affects human health. A mechanistic understanding of pathways linking biodiversity to human health can facilitate the application of nature-based solutions in public health and influence policy. Research integration as well as cross-sector urban policy and planning development should harness opportunities to better identify linkages between biodiversity, climate and human health. Given its importance for human health, urban biodiversity conservation should be considered as public health investment.

The extent and association of chickpea Fusarium wilt and root rot disease pressure with major biophysical factors in Ethiopia - Dagnachew Bekele; Kassahun Tesfaye; Asnake Fikre; Douglas R. Cook (Journal of Plant Pathology, 2021)

A 50-Year Retrospective of the Forest Productivity Cooperative in the Southeastern United States: Regionwide Trials - David R Carter; H Lee Allen; Thomas R Fox; Timothy J Albaugh; Rafael A Rubilar; Otávio C Campoe; Rachel L Cook (Journal of Forestry, 2021)
In 2019, the Forest Productivity Cooperative (FPC) celebrated its 50th anniversary. The mission of the FPC is and has been creating innovative solutions to enhance forest productivity and value through the sustainable management of site resources. This industry-government-university partnership has generated seminal research with sweeping implications for increasing productivity throughout the southeastern United States and Latin America. To commemorate this semicentennial, we highlighted some of the pivotal findings in the southeastern United States from the past 50 years derived from our large, regional experiments: regionwide trials.

Characteristics of Transgender Patient Cases Managed by a Toxicologist: an Analysis of the Toxicology Investigator’s Consortium (ToxIC) Registry: January 2017–June 2019 - Ryan M. Surmaitis; Marna Rayl Greenberg; Natalie E. Ebeling-Koning; Phillip M. Grenz; Cody R. McWhirter; Beth A. Careyva; Judith N. Sabino; Matthew D. Cook; Robert D. Cannon; Andrew L. Koons; Kenneth D. Katz; Hope Kincaid; et al. (Journal of Medical Toxicology, 2021)

A Multidisciplinary Approach to Investigate Deep-Pelagic Ecosystem Dynamics in the Gulf of Mexico Following Deepwater Horizon - April B. Cook; Andrea M. Bernard; Kevin M. Boswell; Heather Bracken-Grissom; Marta D’Elia; Sergio deRada; Cole G. Easson; David English; Ron I. Eytan; Tamara Frank; Chuanmin Hu; Matthew W. Johnston; et al. (Frontiers in Marine Science, 2020)
The pelagic Gulf of Mexico (GoM) is a complex system of dynamic physical oceanography (western boundary current, mesoscale eddies), high biological diversity, and community integration via diel vertical migration and lateral advection. Humans also heavily utilize this system, including its deep-sea components, for resource extraction, shipping, tourism, and other commercial activity. This utilization has had impacts, some with disastrous consequences. The Deepwater Horizon oil spill (DWHOS) occurred at a depth of ∼1500 m (Macondo wellhead), creating a persistent and toxic mixture of hydrocarbons and dispersant in the deep-pelagic (water column below 200 m depth) habitat. In order to assess the impacts of the DWHOS on this habitat, two large-scale research programs, described herein, were designed and executed. These programs, ONSAP and DEEPEND, aimed to quantitatively characterize the oceanic ecosystem of the northern GoM and to establish a time-series with which natural and anthropogenic changes could be detected. The approach was multi-disciplinary in nature and included in situ sampling, acoustic sensing, water column profiling and sampling, satellite remote sensing, AUV sensing, numerical modeling, genetic sequencing, and biogeochemical analyses. The synergy of these methodologies has provided new and unprecedented perspectives of an oceanic ecosystem with respect to composition, connectivity, drivers, and variability.

A little SNP of this, a little SNP of that: The discovery of 116 single nucleotide polymorphism markers to enable the rapid identification of individual Pacific walrus (Odobenus rosmarus divergens) - Geoffrey M. Cook; Daniel J. Prince; Sean M. O’Rourke; Timothy L. King; Michael R. Miller; Cara J. Lewis; Michael S. Eackles; Patrick R. Lemons; Suresh A. Sethi; Jeffrey B. Olsen; John K. Wenburg (Conservation Genetics Resources, 2020)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Visualisation of cholesterol and ganglioside GM1 in zebrafish models of Niemann–Pick type C disease and Smith–Lemli–Opitz syndrome using light sheet microscopy - Sophie R. Cook; Cerys Bladen; Johanna Smith; Emily Maguire; Jordan Copner; Gareth D. Fenn; Kim Wager; Helen Waller-Evans; Emyr Lloyd-Evans (Histochemistry and Cell Biology, 2020)
Lysosomal storage diseases are the most common cause of neurodegeneration in children. They are characterised at the cellular level by the accumulation of storage material within lysosomes. There are very limited therapeutic options, and the search for novel therapies has been hampered as few good small animal models are available. Here, we describe the use of light sheet microscopy to assess lipid storage in drug and morpholino induced zebrafish models of two diseases of cholesterol homeostasis with lysosomal dysfunction: First, Niemann–Pick type C disease (NPC), caused by mutations in the lysosomal transmembrane protein NPC1, characterised by intralysosomal accumulation of cholesterol and several other lipids. Second, Smith–Lemli–Opitz syndrome (SLOS), caused by mutations in 7-dehydrocholesterol reductase, which catalyses the last step of cholesterol biosynthesis and is characterised by intralysosomal accumulation of dietary cholesterol. This is the first description of a zebrafish SLOS model. We find that zebrafish accurately model lysosomal storage and disease-specific phenotypes in both diseases. Increased cholesterol and ganglioside GM1 were observed in sections taken from NPC model fish, and decreased cholesterol in SLOS model fish, but these are of limited value as resolution is poor, and accurate anatomical comparisons difficult. Using light sheet microscopy, we were able to observe lipid changes in much greater detail and identified an unexpected accumulation of ganglioside GM1 in SLOS model fish. Our data demonstrate, for the first time in zebrafish, the immense potential that light sheet microscopy has in aiding the resolution of studies involving lysosomal and lipid disorders.

Racial and ethnic differences in risk of second primary cancers among prostate cancer survivors - Diana R. Withrow; Sara J. Schonfeld; Rochelle E. Curtis; Lindsay M. Morton; Michael B. Cook; Eboneé N. Butler; Amy Berrington de González (Cancer Causes & Control, 2020)

Taxon pulse dynamics, episodic dispersal and host colonization across Beringia drive diversification of a Holarctic tapeworm assemblage - Genevieve M. S. Haas; Eric P. Hoberg; Joseph A. Cook; Heikki Henttonen; Arseny A. Makarikov; Sarah R. Gallagher; Nikolai E. Dokuchaev; Kurt E. Galbreath (Journal of Biogeography, 2020)
Aim We test the predictions of the Stockholm Paradigm, a synthesis of eco‐evolutionary theory explaining the nature of faunal assembly, host range and parasite diversification. Faunal diversification and assembly, manifested in patterns of host colonization, co‐adaptation and parasite speciation, are predicted to emerge as a consequence of alternating episodes of ecological disruption and stability. Specifically, for a diverse cestode genus ( Arostrilepis ), we evaluate the number and direction of Pleistocene dispersal events across Beringia, the number and relative timing of host colonization events and the relationship between host and parasite biogeographic histories and associations through time. Location Beringia and adjacent temperate to arctic biomes in North America and Eurasia. Taxon Arostrilepis (Cyclophyllidea: Hymenolepididae) and its rodent hosts. Methods Multi‐locus phylogenetic reconstruction and biogeographic ancestral range estimation. Results Arostrilepis lineages crossed Beringia eastward into North America a minimum of four times and westward into Asia twice in association with temporally disjunct geographic expansions of three major tribes of cricetid rodents (Arvicolini, Myodini, Lemmini). Inferences of ancestral host associations support at least nine instances of host colonization involving shifts from one rodent tribe or family to another. Several previously unrecognized lineages of Arostrilepis are revealed. Main conclusions Consistent with expectations of the Stockholm Paradigm, episodes of intercontinental dispersal were both frequent in the history of Arostrilepis and preceded a majority of inferred host‐colonization events. Events of historical geographic expansion created numerous opportunities for development of novel host–parasite associations through ecological fitting, as parasites tracked historically conserved resources available across diverse host taxa. Beringia played a major role in shaping rodent/parasite assemblages by mediating dispersal between the northern continents during glacial episodes of the Pleistocene, rather than by serving as a zone of refugial isolation.

Regional environmental drivers of Kemp’s ridley sea turtle somatic growth variation - Matthew D. Ramirez; Larisa Avens; Lisa R. Goshe; Melissa L. Snover; Melissa Cook; Heather L. Haas; Selina S. Heppell (Marine Biology, 2020)

An analysis of the current status and future of biosecurity frameworks for the Indonesian seaweed industry - Cicilia S. B. Kambey; Iona Campbell; Calvyn F. A. Sondak; Adibi R. M. Nor; Phaik E. Lim; Elizabeth J. Cottier-Cook (Journal of Applied Phycology, 2020)
Indonesia is the world largest producer of the red seaweeds Kappaphycus and Eucheuma ; however, this country is facing significant challenges such as disease outbreaks, epiphyte infestations and a loss in seedling quality. Biosecurity practices have been widely adopted in other aquaculture sectors and when enforced can help to limit the introduction and spread of diseases and pests. To assess current capacity for biosecurity in seaweed aquaculture in Indonesia, a systematic analysis of policy frameworks including legislation, regulatory tools, and national standards was conducted. Biosecurity themes and risks were used to evaluate current national biosecurity content. The results identified major challenges faced by the industry in order to implement biosecurity policies in practice. Barriers to implementation included unspecific reference to the seaweed aquaculture sector, limited variety of approaches to biosecurity, limited use of up-to-date scientific evidence, insufficient guidance for the use of precaution and insufficient inclusion of specific biosecurity hazards. In general, although national regulations are currently under revision, current policies indicate a lack of clarity where biosecurity is included. Six recommendations are suggested to incorporate proactive biosecurity actions into current frameworks, with the aim of improving the health and sustainability of the seaweed aquaculture sector in Indonesia.

Effect of blast-related mTBI on the working memory system: a resting state fMRI study - Kathleen F. Pagulayan; Eric C. Petrie; David G. Cook; Rebecca C. Hendrickson; Holly Rau; Melissa Reilly; Cindy Mayer; James S. Meabon; Murray A. Raskind; Elaine R. Peskind; Natalia Kleinhans (Brain Imaging and Behavior, 2020)

Accelerated Forced Degradation of Therapeutic Peptides in Levitated Microdroplets - Yangjie Li; Yanyang Hu; David L. Logsdon; Yong Liu; Yuejie Zhao; R. Graham Cooks (Pharmaceutical Research, 2020)

Rapid Assessment of Wetland Condition Reflects Amphibian Community Composition - Kari Dupler; Michelle Guidugli-Cook; David R. Brown; Stephen C. Richter (Wetlands, 2020)

Regional Variation in Kemp’s Ridley Sea Turtle Diet Composition and Its Potential Relationship With Somatic Growth - Matthew D. Ramirez; Larisa Avens; Lisa R. Goshe; Melissa L. Snover; Melissa Cook; Selina S. Heppell (Frontiers in Marine Science, 2020)

Correction to: Ancestral Folate Promotes Neuronal Regeneration in Serial Generations of Progeny - Nirav J. Patel; Kirk J. Hogan; Elias Rizk; Krista Stewart; Andy Madrid; Sivan Vadakkadath Meethal; Reid Alisch; Laura Borth; Ligia A. Papale; Solomon Ondoma; Logan R. Gorges; Kara Weber; et al. (Molecular Neurobiology, 2020)

Ancestral Folate Promotes Neuronal Regeneration in Serial Generations of Progeny - Nirav J. Patel; Kirk J. Hogan; Elias Rizk; Krista Stewart; Andy Madrid; Sivan Vadakkadath Meethal; Reid Alisch; Laura Borth; Ligia A. Papale; Solomon Ondoma; Logan R. Gorges; Kara Weber; et al. (Molecular Neurobiology, 2020)

Numerical modelling of rare earth element fractionation trends in garnet: a tool to monitor skarn evolution - Jing Xu; Cristiana L. Ciobanu; Nigel J. Cook; Youye Zheng; Xiaofeng Li; Benjamin P. Wade; Max R. Verdugo-Ihl; Wenyuan Gao; Qiaoqiao Zhu (Contributions to Mineralogy and Petrology, 2020)

Resilience of pond communities to extreme thermal regime shifts: an alpine–montane reciprocal transplant experiment - Mitchell A. Johnsen; Blake R. Stuparyk; Jenna Cook; Rolf D. Vinebrooke (Aquatic Sciences, 2020)

Defining early stages of IOCG systems: evidence from iron oxides in the outer shell of the Olympic Dam deposit, South Australia - Max R. Verdugo-Ihl; Cristiana L. Ciobanu; Nigel J. Cook; Kathy J. Ehrig; Liam Courtney-Davies (Mineralium Deposita, 2020)

Crown architecture, crown leaf area distribution, and individual tree growth efficiency vary across site, genetic entry, and planting density - Timothy J. Albaugh; Chris A. Maier; Otávio C. Campoe; Marco A. Yáñez; Eric D. Carbaugh; David R. Carter; Rachel L. Cook; Rafael A. Rubilar; Thomas R. Fox (Trees, 2020)

The European Russia Drought Atlas (1400–2016 CE) - Edward R. Cook; Olga Solomina; Vladimir Matskovsky; Benjamin I. Cook; Leonid Agafonov; Alina Berdnikova; Ekaterina Dolgova; Aleksey Karpukhin; Natallia Knysh; Marina Kulakova; Veronika Kuznetsova; Tomáš Kyncl; et al. (Climate Dynamics, 2020)

Case–control study of endogenous sex steroid hormones and risk of endometrial cancer - Christine M. Friedenreich; Jeroen W. G. Derksen; Thomas Speidel; Darren R. Brenner; Emily Heer; Kerry S. Courneya; Linda S. Cook (Cancer Causes & Control, 2020)

Concordance of chemically inferred and assayed nutrient limitation of phytoplankton along a depth gradient of alpine lakes in the Canadian Rockies - Jenna Cook; Blake R. Stuparyk; Mitchell A. Johnsen; Rolf D. Vinebrooke (Aquatic Sciences, 2020)

The global Microcystis interactome - Katherine V. Cook; Chuang Li; Haiyuan Cai; Lee R. Krumholz; K. David Hambright; Hans W. Paerl; Morgan M. Steffen; Alan E. Wilson; Michele A. Burford; Hans‐Peter Grossart; David P. Hamilton; Helong Jiang; et al. (Limnology and Oceanography, 2020)
Bacteria play key roles in the function and diversity of aquatic systems, but aside from study of specific bloom systems, little is known about the diversity or biogeography of bacteria associated with harmful cyanobacterial blooms (cyanoHABs). CyanoHAB species are known to shape bacterial community composition and to rely on functions provided by the associated bacteria, leading to the hypothesized cyanoHAB interactome, a coevolved community of synergistic and interacting bacteria species, each necessary for the success of the others. Here, we surveyed the microbiome associated with Microcystis aeruginosa during blooms in 12 lakes spanning four continents as an initial test of the hypothesized Microcystis interactome. We predicted that microbiome composition and functional potential would be similar across blooms globally. Our results, as revealed by 16S rRNA sequence similarity, indicate that M. aeruginosa is cosmopolitan in lakes across a 280° longitudinal and 90° latitudinal gradient. The microbiome communities were represented by a wide range of operational taxonomic units and relative abundances. Highly abundant taxa were more related and shared across most sites and did not vary with geographic distance, thus, like Microcystis , revealing no evidence for dispersal limitation. High phylogenetic relatedness, both within and across lakes, indicates that microbiome bacteria with similar functional potential were associated with all blooms. While Microcystis and the microbiome bacteria shared many genes, whole‐community metagenomic analysis revealed a suite of biochemical pathways that could be considered complementary. Our results demonstrate a high degree of similarity across global Microcystis blooms, thereby providing initial support for the hypothesized Microcystis interactome.

Origin and age of The Hillocks and implications for post‐glacial landscape development in the upper Lake Wakatipu catchment, New Zealand - Samuel T. McColl; Simon J. Cook; Timothy Stahl; Timothy R. H. Davies (Journal of Quaternary Science, 2019)
Ambiguous landscape histories can arise from equivocal or incomplete geomorphological, sedimentological or geochronological evidence. In this study, we apply quantitative analyses to robustly assess the origin and age of a field of rounded mounds, known as ‘The Hillocks’. Using clast analysis, the sediment is shown to be consistent with a landslide origin but inconsistent with other glacial sediments in the region. Cosmogenic 10 Be exposure age dating suggests The Hillocks formed ~8 ka. Ground‐penetrating radar reveals that the deposit rests upon deltaic foreset beds; combined with topographical data, we calculate a deposit volume of ~15–27 M m 3 , consistent with the estimated volume of the proposed source area. Overall, our data support a rock avalanche origin, indicating that by 8 ka the valley was ice‐free at The Hillocks’ location, and the level of Lake Wakatipu was lower than 340 m asl by this time. The Dart River delta shoreline was situated somewhere between The Hillocks and the present day shoreline at that time, and has prograded at a maximum average rate of 1 m a −1 since ~8 ka. These findings are significant given the lack of landforms by which to constrain glacial or post‐glacial landscape histories in this region of New Zealand. Copyright © 2019 John Wiley & Sons, Ltd.

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Foundations and Frontiers of Ecosystem Science: Legacy of a Classic Paper (Odum 1969) - Jessica R. Corman; Scott L. Collins; Elizabeth M. Cook; Xiaoli Dong; Laureano A. Gherardi; Nancy B. Grimm; Rebecca L. Hale; Tao Lin; Jorge Ramos; Lara G. Reichmann; Osvaldo E. Sala (Ecosystems, 2019)

The state of Western Australia’s coral reefs - James P. Gilmour; Kylie L. Cook; Nicole M. Ryan; Marjetta L. Puotinen; Rebecca H. Green; George Shedrawi; Jean-Paul A. Hobbs; Damian P. Thomson; Russell C. Babcock; Joanna Buckee; Taryn Foster; Zoe T. Richards; et al. (Coral Reefs, 2019)

A Euro-Mediterranean tree-ring reconstruction of the winter NAO index since 910 C.E. - Edward R. Cook; Yochanan Kushnir; Jason E. Smerdon; A. Park Williams; Kevin J. Anchukaitis; Eugene R. Wahl (Climate Dynamics, 2019)

Tree-ring reconstructions of cool season temperature for far southeastern Australia, 1731–2007 - K. J. Allen; K. J. Anchukaitis; M. G. Grose; G. Lee; E. R. Cook; J. S. Risbey; T. J. O’Kane; D. Monselesan; A. O’Grady; S. Larsen; P. J. Baker (Climate Dynamics, 2019)

Implementation of a Systematic Tumor Screening Program for Lynch Syndrome in an Integrated Health Care Setting - Elizabeth V. Clarke; Kristin R. Muessig; Jamilyn Zepp; Jessica E. Hunter; Sapna Syngal; Louise S. Acheson; Georgia L. Wiesner; Susan K. Peterson; Kellene M. Bergen; Elizabeth Shuster; James V. Davis; Jennifer L. Schneider; et al. (Familial Cancer, 2019)

Forest Fertilizer Applications in the Southeastern United States from 1969 to 2016 - Timothy J Albaugh; Thomas R Fox; Rachel L Cook; Jay E Raymond; Rafael A Rubilar; Otávio C Campoe (Forest Science, 2019)

Cable bacteria promote DNRA through iron sulfide dissolution - Adam J. Kessler; Michaela Wawryk; Ugo Marzocchi; Keryn L. Roberts; Wei Wen Wong; Nils Risgaard‐Petersen; Filip J. R. Meysman; Ronnie N. Glud; Perran L. M. Cook (Limnology and Oceanography, 2019)
Cable bacteria represent a newly discovered group of filamentous microorganisms, which are capable of spatially separating the oxidative and reductive half‐reactions of their sulfide‐oxidizing metabolisms over centimeter distances. We investigated three ways that cable bacteria might interact with the nitrogen (N) cycle: (1) by reducing nitrate through denitrification or dissimilatory nitrate reduction to ammonium (DNRA) within their cathodic cells; (2) by nitrifying ammonium within their anodic cells; and (3) by indirectly affecting denitrification and/or DNRA by changing the Fe 2+ concentration in the surrounding sediment. We performed 15 N labeling laboratory experiments to measure these three processes using cable bacteria containing sediments from the Yarra River, Australia, and from Vilhelmsborg Sø, Denmark. Our results revealed that in the targeted systems, cable bacteria themselves did not perform significant rates of denitrification, DNRA, or nitrification. However, cable bacteria exhibited an important indirect effect, whereby they increased the Fe 2+ pool through iron sulfide dissolution. This elevated availability of Fe 2+ significantly increased DNRA and in some cases decreased denitrification. Thus, cable bacteria presence may affect the relative importance of DNRA in sediments and thus the extent by which bioavailable nitrogen is lost from the system.

How do climate change experiments alter plot‐scale climate? - A. K. Ettinger; I. Chuine; B. I. Cook; J. S. Dukes; A. M. Ellison; M. R. Johnston; A. M. Panetta; C. R. Rollinson; Y. Vitasse; E. M. Wolkovich (Ecology Letters, 2019)
To understand and forecast biological responses to climate change, scientists frequently use field experiments that alter temperature and precipitation. Climate manipulations can manifest in complex ways, however, challenging interpretations of biological responses. We reviewed publications to compile a database of daily plot‐scale climate data from 15 active‐warming experiments. We find that the common practices of analysing treatments as mean or categorical changes (e.g. warmed vs. unwarmed) masks important variation in treatment effects over space and time. Our synthesis showed that measured mean warming, in plots with the same target warming within a study, differed by up to 1.6 C (63% of target), on average, across six studies with blocked designs. Variation was high across sites and designs: for example, plots differed by 1.1 C (47% of target) on average, for infrared studies with feedback control ( n = 3) vs. by 2.2 C (80% of target) on average for infrared with constant wattage designs ( n = 2). Warming treatments produce non‐temperature effects as well, such as soil drying. The combination of these direct and indirect effects is complex and can have important biological consequences. With a case study of plant phenology across five experiments in our database, we show how accounting for drier soils with warming tripled the estimated sensitivity of budburst to temperature. We provide recommendations for future analyses, experimental design, and data sharing to improve our mechanistic understanding from climate change experiments, and thus their utility to accurately forecast species’ responses.

Training Needs of Clinical and Research Professionals to Optimize Minority Recruitment and Retention in Cancer Clinical Trials - Soumya J. Niranjan; Raegan W. Durant; Jennifer A. Wenzel; Elise D. Cook; Mona N. Fouad; Selwyn M. Vickers; Badrinath R. Konety; Sarah B. Rutland; Zachary R. Simoni; Michelle Y. Martin (Journal of Cancer Education, 2019)

Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2018)

Semiochemical-based alternatives to synthetic toxicant insecticides for pollen beetle management - Alice L. Mauchline; Maxime R. Hervé; Samantha M. Cook (Arthropod-Plant Interactions, 2018)

Differential Morphological and Biochemical Recovery from Chemotherapy-Induced Peripheral Neuropathy Following Paclitaxel, Ixabepilone, or Eribulin Treatment in Mouse Sciatic Nerves - B. M. Cook; K. M. Wozniak; D. A. Proctor; R. B. Bromberg; Y. Wu; B. S. Slusher; B. A. Littlefield; M. A. Jordan; L. Wilson; Stuart C. Feinstein (Neurotoxicity Research, 2018)

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

Standardized reporting of the costs of management interventions for biodiversity conservation - Gwenllian D. Iacona; William J. Sutherland; Bonnie Mappin; Vanessa M. Adams; Paul R. Armsworth; Tim Coleshaw; Carly Cook; Ian Craigie; Lynn V. Dicks; James A. Fitzsimons; Jennifer McGowan; Andrew J. Plumptre; et al. (Conservation Biology, 2018)
Effective conservation management interventions must combat threats and deliver benefits at costs that can be achieved within limited budgets. Considerable effort has focused on measuring the potential benefits of conservation interventions, but explicit quantification of the financial costs of implementation is rare. Even when costs have been quantified, haphazard and inconsistent reporting means published values are difficult to interpret. This reporting deficiency hinders progress toward a collective understanding of the financial costs of management interventions across projects and thus limits the ability to identify efficient solutions to conservation problems or attract adequate funding. We devised a standardized approach to describing financial costs reported for conservation interventions. The standards call for researchers and practitioners to describe the objective and outcome, context and methods, and scale of costed interventions, and to state which categories of costs are included and the currency and date for reported costs. These standards aim to provide enough contextual information that readers and future users can interpret the cost data appropriately. We suggest these standards be adopted by major conservation organizations, conservation science institutions, and journals so that cost reporting is comparable among studies. This would support shared learning and enhance the ability to identify and perform cost‐effective conservation.

Persistence of Hepatitis A Virus in Fresh Produce and Production Environments, and the Effect of Disinfection Procedures: A Review - N. Cook; I. Bertrand; C. Gantzer; R. M. Pinto; A. Bosch (Food and Environmental Virology, 2018)

Under what circumstances does the capture and tagging of wild Atlantic salmon Salmo salar smolts affect probability of return as adults? - William D. Riley; Anton T. Ibbotson; Stephen D. Gregory; Ian C. Russell; Rasmus B. Lauridsen; William R. C. Beaumont; Alastair C. Cook; David L. Maxwell (Journal of Fish Biology, 2018)
Adult return rates for wild Atlantic salmon Salmo salar smolts captured in a rotary screw trap and tagged with coded wire (CW) tags were compared with a control group, using detections from passive integrated transponder (PIT) antennae systems over 7 years in a small chalk stream in southern England, U.K. Compared with control smolts, capture and CW‐tagging of experimental smolts affected detected return rates only under certain conditions, with a decreased return probability for smolts caught and tagged following mild winter river temperature anomalies and during the night. Similarly, analysis of the experimental smolts revealed that capture and CW‐tagging following mild winters decreased their probability of return as adults. There were also marginal positive effects of length at PIT‐tagging as parr and length at CW‐tagging as smolts, on individual probability of return as adult. The results support the hypothesis that the effect of procedures involving the capture and tagging of migrating wild S. salar smolts will vary with the circumstances under which they are performed. The implications of the findings are considered in the context of ongoing investigations to derive and report marine return rates for S. salar in support of national and international stock assessments and in developing best practice.

Can we increase smokers’ adherence to nicotine replacement therapy and does this help them quit? - Tanya R. Schlam; Jessica W. Cook; Timothy B. Baker; Todd Hayes-Birchler; Daniel M. Bolt; Stevens S. Smith; Michael C. Fiore; Megan E. Piper (Psychopharmacology, 2018)

Associations between riffle development and aquatic biota following lowhead dam removal - Danielle R. Cook; S. Mažeika P. Sullivan (Environmental Monitoring and Assessment, 2018)

Trends of two HPV-associated cancers in Massachusetts: cervical and oropharyngeal cancer - Erin E. Cook; Susan T. Gershman; Jane J. Kim; Rulla M. Tamimi; R. Monina Klevens; Michelle D. Holmes (Cancer Causes & Control, 2018)

Effects of group size on school structure and behaviour in yellow‐eyed mullet Aldrichetta forsteri - K. L. Middlemiss; D. G. Cook; A. R. Jerrett; W. Davison (Journal of Fish Biology, 2018)
Schooling behaviour in yellow‐eyed mullet Aldrichetta forsteri , a common fish species in New Zealand estuarine habitats, was investigated to identify interaction rules associated with group formation. Tank‐based three‐dimensional studies of three group sizes (15, 75 and 150 individuals) were carried out to measure the effects of these different group sizes on school structure during control, predation risk and foraging behavioural states. Increased group size positively correlated with nearest‐neighbour distance in control and foraging states. Swimming speed was the lowest in all three behavioural states in groups of 15 fish compared with 75 or 150. Immediate behavioural response following visual exposure to a simulated avian predator differed between groups resulting in loss of structure in larger groups. School shape was an oblong–oblate spheroid with a length, breadth and height ratio of 5:2:1 and the area of free space surrounding individual fish was spherical in shape with a high degree of spatial isotropy present in all size groups. These findings challenge traditional theories based on either local or global properties as key drivers of group structure. Instead, our results suggest that a more collaborative approach involving both group size and rules pertaining to nearest‐neighbour interactions affects collective behaviours in this species.

Population trends of bycatch species reflect improving status of target species - Robin M Cook; Michael R Heath (Fish and Fisheries, 2018)
Synthesis studies of fish stocks worldwide suggest improving status of mainly target species that are fully assessed. Other analyses, primarily based on catch data alone, but which include a wider range of species as well as bycatch, present a different view. Catch‐only analyses could be more robust if fishery‐independent data were used and discards accounted for. We develop a model that uses only survey biomass at length and landings data to estimate fishing mortality, spawning stock biomass ( SSB ) and discards. An analysis of species from the North Sea shows the model results compare well with most fully assessed stocks. When applied to bycatch species with limited data, trends in fishing mortality and SSB typically reflect those of the target species. In the last decade, mean fishing mortality rates have tended to decline, while mean SSB has increased. Despite increasing SSB , recent mean recruitment appears to have been lower than previously which may limit future biomass recovery. Species usually associated with more northerly distributions appear to show the greatest effect of weaker recruitment, which may be linked to climate. Estimated discards have tended to decline in magnitude as a result of reduced fishing mortality and associated lower total catches. The model offers a simple way to use both landings and survey data to obtain more detailed population trends for data limited species.

The role of catchment land use and tidal exchange in structuring estuarine fish assemblages - F. Y. Warry; P. Reich; P. L. M. Cook; R. Mac Nally; R. J. Woodland (Hydrobiologia, 2018)

Coagulase-negative staphylococci are associated to the mild inflammatory pattern of healthcare-associated meningitis: a retrospective study - S. Couffin; D. Lobo; F. Cook; P. H. Jost; V. Bitot; R. Birnbaum; B. Nebbad; B. Aït-Mamar; W. Lahiani; M. Martin; G. Dhonneur; R. Mounier (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Agro-morphological traits of Cicer reticulatum Ladizinsky in comparison to C. echinospermum P.H. Davis in terms of potential to improve cultivated chickpea (C. arietinum L.) - Mirlan Talip; Alper Adak; Abdullah Kahraman; Jens Berger; Duygu Sari; Hatice Sari; R. V. Penmetsa; E. J. von Wettberg; D. R. Cook; Cengiz Toker (Genetic Resources and Crop Evolution, 2018)

Advances in Silviculture of Intensively Managed Plantations - Rafael A. Rubilar; H. Lee Allen; Thomas R. Fox; Rachel L. Cook; Timothy J. Albaugh; Otávio C. Campoe (Current Forestry Reports, 2018)

First identification and characterization of Borrobol‐type tephra in the Greenland ice cores: new deposits and improved age estimates - Eliza Cook; Siwan M. Davies; Esther R. Guðmundsdóttir; Peter M. Abbott; Nicholas J. G. Pearce (Journal of Quaternary Science, 2018)
Contiguous sampling of ice spanning key intervals of the deglaciation from the Greenland ice cores of NGRIP, GRIP and NEEM has revealed three new silicic cryptotephra deposits that are geochemically similar to the well‐known Borrobol Tephra (BT). The BT is complex and confounded by the younger closely timed and compositionally similar Penifiler Tephra (PT). Two of the deposits found in the ice are in Greenland Interstadial 1e (GI‐1e) and an older deposit is found in Greenland Stadial 2.1 (GS‐2.1). Until now, the BT was confined to GI‐1‐equivalent lacustrine sequences in the British Isles, Sweden and Germany, and our discovery in Greenland ice extends its distribution and geochemical composition. However, the two cryptotephras that fall within GI‐1e ice cannot be separated on the basis of geochemistry and are dated to 14358 ± 177 a b2k and 14252 ± 173 a b2k, just 106 ± 3 years apart. The older deposit is consistent with BT age estimates derived from Scottish sites, while the younger deposit overlaps with both BT and PT age estimates. We suggest that either the BT in Northern European terrestrial sequences represents an amalgamation of tephra from both of the GI‐1e events identified in the ice‐cores or that it relates to just one of the ice‐core events. A firm correlation cannot be established at present due to their strong geochemical similarities. The older tephra horizon, found within all three ice‐cores and dated to 17326 ± 319 a b2k, can be correlated to a known layer within marine sediment cores from the North Iceland Shelf (ca. 17179‐16754 cal a BP). Despite showing similarities to the BT, this deposit can be distinguished on the basis of lower CaO and TiO 2 and is a valuable new tie‐point that could eventually be used in high‐resolution marine records to compare the climate signals from the ocean and atmosphere.

Survival estimates for the greater crested tern Thalasseus bergii in southern Africa - A Payo-Payo; A Sanz-Aguilar; D Gaglio; RB Sherley; TR Cook; R Altwegg; PG Ryan (African Journal of Marine Science, 2018)

Defining ecologically relevant scales for spatial protection with long‐term data on an endangered seabird and local prey availability - Richard B. Sherley; Philna Botha; Les G. Underhill; Peter G. Ryan; Danie van Zyl; Andrew C. Cockcroft; Robert J.M. Crawford; Bruce M. Dyer; Timothée R. Cook (Conservation Biology, 2017)
Human activities are important drivers of marine ecosystem functioning. However, separating the synergistic effects of fishing and environmental variability on the prey base of nontarget predators is difficult, often because prey availability estimates on appropriate scales are lacking. Understanding how prey abundance at different spatial scales links to population change can help integrate the needs of nontarget predators into fisheries management by defining ecologically relevant areas for spatial protection. We investigated the local population response (number of breeders) of the Bank Cormorant ( Phalacrocorax neglectus ), a range‐restricted endangered seabird, to the availability of its prey, the heavily fished west coast rock lobster ( Jasus lalandii ). Using Bayesian state‐space modeled cormorant counts at 3 colonies, 22 years of fisheries‐independent data on local lobster abundance, and generalized additive modeling, we determined the spatial scale pertinent to these relationships in areas with different lobster availability. Cormorant numbers responded positively to lobster availability in the regions with intermediate and high abundance but not where regime shifts and fishing pressure had depleted lobster stocks. The relationships were strongest when lobsters 20–30 km offshore of the colony were considered, a distance greater than the Bank Cormorant's foraging range when breeding, and may have been influenced by prey availability for nonbreeding birds, prey switching, or prey ecology. Our results highlight the importance of considering the scale of ecological relationships in marine spatial planning and suggest that designing spatial protection around focal species can benefit marine predators across their full life cycle. We propose the precautionary implementation of small‐scale marine protected areas, followed by robust assessment and adaptive‐management, to confirm population‐level benefits for the cormorants, their prey, and the wider ecosystem, without negative impacts on local fisheries.

Expansion of landscape characterisation methods within the Hydrogeological Landscape Framework: application in the Australian Capital Territory - A. L. Cowood; C. L. Moore; M. J. Cracknell; J. Young; R. Muller; A. T. Nicholson; A. C. Wooldridge; B. R. Jenkins; W. Cook (Australian Journal of Earth Sciences, 2017)

Field-based assessment of wetland condition, wetland extent, and the National Wetlands Inventory in Kentucky, USA - Michelle Guidugli-Cook; Stephen C. Richter; Barbara J. Scott; David R. Brown (Wetlands Ecology and Management, 2017)

Morphology and hydro-sensory role of superficial neuromasts in schooling behaviour of yellow-eyed mullet (Aldrichetta forsteri) - Karen L. Middlemiss; Denham G. Cook; Alistair R. Jerrett; William Davison (Journal of Comparative Physiology A, 2017)

Influence of oceanographic conditions on abundance and distribution of post‐larval and juvenile carangid fishes in the northern Gulf of Mexico - John A. Mohan; Tracey T. Sutton; April B. Cook; Kevin M. Boswell; R. J. David Wells (Fisheries Oceanography, 2017)
Relationships between abundance of post‐larval and juvenile carangid (jacks) fishes and physical oceanographic conditions were examined in the northern Gulf of Mexico (GoM) in 2011 with high freshwater input from the Mississippi River. Generalized additive models ( GAM s) were used to explore complex relationships between carangid abundance and physical oceanographic data of sea surface temperature ( SST ), sea surface height anomaly ( SSHA ) and salinity. The five most abundant carangid species collected were: Selene setapinnis (34%); Caranx crysos (30%); Caranx hippos (10%); Chloroscombrus chrysurus (9%) and Trachurus lathami (8%). Post‐larval carangids (median standard length [ SL ] = 10 mm) were less abundant during the spring and early summer, but more abundant during the late summer and fall, suggesting summer to fall spawning for most species. Juvenile carangid (median SL = 23 mm) abundance also increased between the mid‐summer and early fall. Most species showed increased abundance at lower salinities and higher temperatures, suggesting entrainment of post‐larval fishes or feeding aggregations of juveniles at frontal convergence zones between the expansive river plume and dynamic mesoscale eddy water masses. However, responses were species‐ and life‐stage specific, which may indicate fine‐scale habitat partitioning between species. Ordination methods also revealed higher carangid abundances at lower salinities for both post‐larval and juvenile life stages, with species‐ and life‐stage specific responses to SST and SSHA , further suggesting habitat separation between species. Results indicate strong links between physical oceanographic features and carangid distributions in the dynamic northern GoM.

Pseudocyst formation in the marine parasitic amoeba Neoparamoeba perurans : a short‐term survival strategy to abrupt salinity variation - P C Lima; R S Taylor; M Cook (Journal of Fish Diseases, 2017)

400 Years of summer hydroclimate from stable isotopes in Iberian trees - Laia Andreu-Hayles; Caroline C. Ummenhofer; Mariano Barriendos; Gerhard H. Schleser; Gerhard Helle; Markus Leuenberger; Emilia Gutiérrez; Edward R. Cook (Climate Dynamics, 2017)

Universal screening for Lynch syndrome among patients with colorectal cancer: patient perspectives on screening and sharing results with at-risk relatives - Jessica Ezzell Hunter; Kathleen A. Arnold; Jennifer E. Cook; Jamilyn Zepp; Marian J. Gilmore; Alan F. Rope; James V. Davis; Kellene M. Bergen; Elizabeth Esterberg; Kristin R. Muessig; Susan K. Peterson; Sapna Syngal; et al. (Familial Cancer, 2017)

Effects of Elevated CO2 on the Swainsonine Chemotypes of Astragalus lentiginosus and Astragalus mollissimus - Daniel Cook; Dale R. Gardner; James A. Pfister; Clinton A. Stonecipher; Joseph G. Robins; Jack A. Morgan (Journal of Chemical Ecology, 2017)

Virological Quality of Irrigation Water in Leafy Green Vegetables and Berry Fruits Production Chains - P. Kokkinos; I. Kozyra; S. Lazic; K. Söderberg; P. Vasickova; M. Bouwknegt; S. Rutjes; K. Willems; R. Moloney; A. M. de Roda Husman; A. Kaupke; E. Legaki; et al. (Food and Environmental Virology, 2017)

Spatial reconstruction of Scottish summer temperatures from tree rings - Miloš Rydval; Björn E. Gunnarson; Neil J. Loader; Edward R. Cook; Daniel L. Druckenbrod; Rob Wilson (International Journal of Climatology, 2017)
A detailed understanding of past temporal patterns and spatial expression of temperature variations is important to place recent anthropogenic climate change into a longer term context. In order to fill the current gap in our understanding of northwest European temperature variability, point‐by‐point principal component regression was used to reconstruct a spatial field of 0.5° temperature grids across Scotland. A sequence of reconstructions utilizing several combinations of detrending and disturbance correction procedures, and a selection of tree‐ring parameters [including ring width ( RW ), maximum latewood density ( MXD ) and blue intensity ( BI )] was used in an evaluation of reconstruction skill. The high resolution of the reconstructed field serves also as a diagnostic tool to spatially assess the temperature reconstruction potential of local chronologies. Best reconstruction results, reaching calibration r 2 = 65.8% and verification r 2 = 63.7% in central Scotland over the 1901–1976 period, were achieved using disturbance‐corrected and signal‐free detrended RW chronologies merged with BI data after low‐pass (high‐pass) filtering the RW ( BI ) chronologies. Calibration and verification r 2 > 50% was attained for central, north and east Scotland, >40% in west and northwest, and >30% in southern Scotland with verification of nearly all grids showing some reconstruction skill. However, the full calibration potential of reconstructions outside central Scotland was reduced either due to residual disturbance trends undetected by the disturbance correction procedure or due to other climatic or non‐climatic factors which may have adversely affected the strength of the climate signal.

Disease Progression Modeling: Key Concepts and Recent Developments - Sarah F. Cook; Robert R. Bies (Current Pharmacology Reports, 2016)

Size matters: experimental partitioning of the strength of fish herbivory on a fringing coral reef in M oorea, F rench P olynesia - Peggy Fong; Nicholas M. Frazier; Cameron Tompkins‐Cook; Ranjan Muthukrishnan; Caitlin R. Fong (Marine Ecology, 2016)
While the importance of top‐down control by grazers in maintaining tropical reef community structure is well known, the effect of ‘fishing down the food web’, which simultaneously changes the abundance and size of herbivorous fishes, has received less attention. As many fishing practices target the biggest fish and regulations often set minimum size limits, understanding size‐dependency of this controlling force is important. We evaluated the hypothesis that reduction in the abundance and size of fish, regardless of species identity, reduces the role of herbivory in controlling algal abundance on reefs and assessed variation in efficacy of this top‐down control on different types of common macroalgae. We quantified herbivory rates within cages of differing opening sizes on assemblages of four common algal species ( Padina boryana , Dictyota bartayresiana , Halimeda opuntia and Galaxaura fasciculata ) on two fringing reefs in Moorea, French Polynesia. Small acanthurids ( 50% in the largest opening cages (6 × 6 cm) where the maximum size fish entering was 12 cm in length (mean = 7.6, SE = 0.4). Fish entering medium (4.5 × 4.5 cm openings, maximum fish length = 8 cm, mean = 6.3, SE = 0.4) and small (3 × 3 cm openings, no fish observed entering) cages had herbivory rates approximately equal to the control treatment (1 × 1 cm openings). Consumption varied among algal species, with minimal consumption of physically and chemically defended algae and no pattern across treatments. Our results demonstrate a need for management plans to not only maintain the overall abundance of herbivorous fish but to protect the largest sizes for effective top‐down control of algal communities.

Cape cormorants decrease, move east and adapt foraging strategies following eastward displacement of their main prey - RJM Crawford; RM Randall; TR Cook; PG Ryan; BM Dyer; R Fox; D Geldenhuys; J Huisamen; C McGeorge; MK Smith; L Upfold; J Visagie; et al. (African Journal of Marine Science, 2016)

Identifying the physical features of marina infrastructure associated with the presence of non-native species in the UK - Victoria Foster; Rebecca J. Giesler; A. Meriwether W. Wilson; Christopher R. Nall; Elizabeth J. Cook (Marine Biology, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Much more give than take: South Africa as a major donor but infrequent recipient of invasive non‐native grasses - Vernon Visser; John R. U. Wilson; Lyn Fish; Carly Brown; Garry D. Cook; David M. Richardson (Global Ecology and Biogeography, 2016)
Aim Some regions donate more invaders from particular taxonomic and functional groups than they receive. We demonstrate a particularly striking donor–recipient asymmetry in invasion ecology in grasses. Specifically, we explore whether low numbers of invasive grasses in South Africa can be explained by sampling biases, introduction dynamics, species traits or invasibility of ecosystems. Location South Africa, Australia, Chile, Europe and the USA. Methods We tested for a donor–recipient asymmetry using lists of native and non‐native grasses in five regions across the globe. Then, using distribution, trait and environmental data, we tested whether regions differed in: (1) herbarium sampling effort; (2) introduction dynamics of non‐native grasses (primary uses, area of origin and minimum residence time of non‐native grasses); (3) traits of native and non‐native grasses (leaf size, height, life history, growth form, C 3 :C 4 ratio and taxonomic placement); and (4) fire frequency. Results South Africa has fewer invasive grasses, and fewer widespread invasive grasses, than other regions; while grasses native to South Africa are much more likely to be invasive elsewhere than other grasses. This asymmetry cannot be explained by sampling biases, historical trade links or minimum residence time. Rather it is likely to be due to a combination of: (1) the massive scale of the introduction of South African grasses around the world; (2) specific traits that make South African grasses successful competitors; and (3) the high fire frequency of many South African ecosystems to which many native grasses are adapted, but introduced grasses are not. Main conclusion South Africa has a high diversity of grasses that possess specific traits to cope with fire, grazing and disturbance. This makes them more competitive. Moreover, the high diversity of certain grass lineages in South Africa acts as a reservoir of potential invaders and possibly helps limit invasions in South Africa by promoting fire.

Mortality risk from comorbidities independent of triple-negative breast cancer status: NCI-SEER-based cohort analysis - Helen Swede; Amna Sarwar; Anil Magge; Dejana Braithwaite; Linda S. Cook; David I. Gregorio; Beth A. Jones; Jessica R. Hoag; Lou Gonsalves; Andrew L. Salner; Kristen Zarfos; Biree Andemariam; et al. (Cancer Causes & Control, 2016)

Involvement of contractile vacuoles in the osmoregulation process of the marine parasitic amoeba N eoparamoeba perurans - P C Lima; R S Taylor; M Cook (Journal of Fish Diseases, 2016)

Post-traumatic stress is associated with verbal learning, memory, and psychomotor speed in HIV-infected and HIV-uninfected women - Leah H. Rubin; Maria Pyra; Judith A. Cook; Kathleen M. Weber; Mardge H. Cohen; Eileen Martin; Victor Valcour; Joel Milam; Kathryn Anastos; Mary A. Young; Christine Alden; Deborah R. Gustafson; et al. (Journal of NeuroVirology, 2016)

Development and characterization of a synthetic infectious cDNA clone of the virulent Bucyrus strain of equine arteritis virus expressing mCherry (red fluorescent protein) - Shankar P. Mondal; R. Frank Cook; R. Lakshman Chelvarajan; Pamela J. Henney; Peter J. Timoney; Udeni B. R. Balasuriya (Archives of Virology, 2016)

Meta-studies in land use science: Current coverage and prospects - Jasper van Vliet; Nicholas R. Magliocca; Bianka Büchner; Elizabeth Cook; José M. Rey Benayas; Erle C. Ellis; Andreas Heinimann; Eric Keys; Tien Ming Lee; Jianguo Liu; Ole Mertz; Patrick Meyfroidt; et al. (Ambio, 2016)

Deep dynamic pools of phosphorus in the sediment of a temperate lagoon with recurring blooms of diazotrophic cyanobacteria - Todd R. Scicluna; Ryan J. Woodland; Yafei Zhu; Michael R. Grace; Perran L. M. Cook (Limnology and Oceanography, 2015)
The storage and release of phosphorus by sediments can act as an important control on the formation of noxious blooms of cyanobacteria in lakes and estuaries. Here we studied the uptake and release of phosphorus associated with iron oxides within sediments of a lagoon system affected by recurring summer blooms of the cyanobacterium Nodularia spumigena . Using an ascorbate extraction, we observed deep pools of iron oxide associated phosphorus (P) at concentrations of ∼5 μ mol g −1 dry sed to a depth of ∼20 cm. This pool rapidly decreased with the onset of water column anoxia, leading to an integrated release of ∼300 mmol of phosphorus m −2 of sediment over 3.5 months. Scaling this flux over the periodically anoxic area of the lake and over the period of an N. spumigena bloom (November–December 2011) gave a broad mass balance agreement with the increase in total phosphorus within the water column and exported from the lagoon. Over this period we estimated that P release from the sediment would have allowed ∼130–187 tonnes of nitrogen to be fixed which agrees with previous estimates of nitrogen fixation. Upon reoxygenation of the water column, a regeneration of the deep iron oxide associated phosphorus pool was observed. This deep dynamic pool of phosphorus was most likely mediated by the burrowing activity of the polychaete Capitella capitata which was observed at the study site. This study underscores the potential importance of sediments colonized by deeply irrigating fauna to become a significant source of phosphorus during water column anoxia.

Nitrogen loads explain primary productivity in estuaries at the ecosystem scale - Ryan J. Woodland; James R. Thomson; Ralph Mac Nally; Paul Reich; Victor Evrard; Fiona Y. Wary; Jeffrey P. Walker; Perran L. M. Cook (Limnology and Oceanography, 2015)
Increased nutrient loads stimulate estuary primary productivity and can alter the structure and function of biological communities within estuaries, particularly when producer groups respond differently to changes in nutrient availability. Here, the relative influence of riverine inputs of nitrogen and phosphorus were compared to determine their contribution to estuarine primary producers at large spatial scales. Indices of demersal (extent of macroalgae relative to other vegetation, total shallow water area vegetated) and planktonic (seasonally averaged chlorophyll concentration) primary producer communities were derived at whole‐of‐ecosystem scales in 14 estuaries dispersed across a longitudinal gradient using aerial imaging, underwater videography and in situ monitoring. A model selection framework was used to relate annual nutrient loads (total nitrogen [TN], dissolved inorganic nitrogen [DIN], total phosphorus [TP]), sediment loads (TSS), molar stoichiometric load ratios (TN M : TP M ), and estuary water residence times to the demersal and planktonic indices. Dissolved inorganic nitrogen was the best predictor of the extent of macroalgae, total vegetation coverage, and the concentration of planktonic chlorophyll. Rapid increases in all three indices occurred at inorganic nitrogen loads of ∼ 5–10 Mg km −2 yr −1 . There was some evidence that TN M : TP M , TP and TSS loads were informative model covariates. Relative to DIN loads, TP loads were a poor predictor of the macroalgal and planktonic indices. These findings underscore the critical role of catchment‐derived nitrogen in contributing to producer communities at the whole‐of‐ecosystem scale and support the growing consensus that nitrogen loads (in addition to phosphorus) must be managed to effectively alleviate eutrophication in estuaries.

The association of perceived stress and verbal memory is greater in HIV-infected versus HIV-uninfected women - Leah H. Rubin; Judith A. Cook; Kathleen M. Weber; Mardge H. Cohen; Eileen Martin; Victor Valcour; Joel Milam; Kathryn Anastos; Mary A. Young; Christine Alden; Deborah R. Gustafson; Pauline M. Maki (Journal of NeuroVirology, 2015)

Evidence of climate‐driven ecosystem reorganization in the Gulf of Mexico - Mandy Karnauskas; Michael J. Schirripa; J. K. Craig; Geoffrey S. Cook; Christopher R. Kelble; Juan J. Agar; Bryan A. Black; David B. Enfield; David Lindo‐Atichati; Barbara A. Muhling; Kevin M. Purcell; Paul M. Richards; et al. (Global Change Biology, 2015)
The Gulf of Mexico is one of the most ecologically and economically valuable marine ecosystems in the world and is affected by a variety of natural and anthropogenic phenomena including climate, hurricanes, coastal development, agricultural runoff, oil spills, and fishing. These complex and interacting stressors, together with the highly dynamic nature of this ecosystem, present challenges for the effective management of its resources. We analyze a compilation of over 100 indicators representing physical, biological, and economic aspects of the Gulf of Mexico and find that an ecosystem‐wide reorganization occurred in the mid‐1990s. Further analysis of fishery landings composition data indicates a major shift in the late 1970s coincident with the advent of US national fisheries management policy, as well as significant shifts in the mid‐1960s and the mid‐1990s. These latter shifts are aligned temporally with changes in a major climate mode in the Atlantic Ocean: the Atlantic Multidecadal Oscillation ( AMO ). We provide an explanation for how the AMO may drive physical changes in the Gulf of Mexico, thus altering higher‐level ecosystem dynamics. The hypotheses presented here should provide focus for further targeted studies, particularly in regard to whether and how management should adjust to different climate regimes or states of nature. Our study highlights the challenges in understanding the effects of climatic drivers against a background of multiple anthropogenic pressures, particularly in a system where these forces interact in complex and nonlinear ways.

A tree-ring field reconstruction of Fennoscandian summer hydroclimate variability for the last millennium - Kristina Seftigen; Jesper Björklund; Edward R. Cook; Hans W. Linderholm (Climate Dynamics, 2015)

Integrating physiological threshold experiments with climate modeling to project mangrove species’ range expansion - Kyle C. Cavanaugh; John D. Parker; Susan C. Cook‐Patton; Ilka C. Feller; A. Park Williams; James R. Kellner (Global Change Biology, 2015)
Predictions of climate‐related shifts in species ranges have largely been based on correlative models. Due to limitations of these models, there is a need for more integration of experimental approaches when studying impacts of climate change on species distributions. Here, we used controlled experiments to identify physiological thresholds that control poleward range limits of three species of mangroves found in North America. We found that all three species exhibited a threshold response to extreme cold, but freeze tolerance thresholds varied among species. From these experiments, we developed a climate metric, freeze degree days ( FDD ), which incorporates both the intensity and the frequency of freezes. When included in distribution models, FDD accurately predicted mangrove presence/absence. Using 28 years of satellite imagery, we linked FDD to observed changes in mangrove abundance in Florida, further exemplifying the importance of extreme cold. We then used downscaled climate projections of FDD to project that these range limits will move northward by 2.2–3.2 km yr −1 over the next 50 years.

Reconstruction of the springtime East Asian Subtropical Jet and Western Pacific pattern from a millennial-length Taiwanese tree-ring chronology - W. E. Wright; B. T. Guan; Y.-H. Tseng; E. R. Cook; K.-Y. Wei; S.-T. Chang (Climate Dynamics, 2015)

Quantifying the effects of light intensity on bioproduction and maintenance energy during photosynthetic growth of Rhodobacter sphaeroides - Saheed Imam; Colin M. Fitzgerald; Emily M. Cook; Timothy J. Donohue; Daniel R. Noguera (Photosynthesis Research, 2015)

Sex differences in ventricular–vascular coupling following endurance training - A. D. Lane; H. Yan; S. M. Ranadive; R. M. Kappus; P. Sun; M. D. Cook; I. Harvey; J. Woods; K. Wilund; B. Fernhall (European Journal of Applied Physiology, 2014)

Comparative analysis of LTR and structural genes in an equine infectious anemia virus strain isolated from a feral horse in Japan - Jianbao Dong; Frank R. Cook; Takeshi Haga; Yoichiro Horii; Junzo Norimine; Naoaki Misawa; Yoshitaka Goto; Wei Zhu (Archives of Virology, 2014)

Sources and fate of nitrate in a groundwater‐fed estuary elucidated using stable isotope ratios of nitrogen and oxygen - Wei Wen Wong; Michael R. Grace; Ian Cartwright; Perran L. M. Cook (Limnology and Oceanography, 2014)
We used δ 15 N‐nitrate (NO − 3 ) and δ 18 O‐NO − 3 to unravel the provenance and fate of NO − 3 in a groundwater‐fed estuary. A total of 13 monthly and two time series surveys were undertaken in the Werribee River estuary near Melbourne, Australia. The different survey timescales provided a comprehensive evaluation of the hydrological effects on the biogeochemistry of NO − 3 , which accounted for tidal variability and episodic runoff events. The distribution of δ 15 N and δ 18 O of the estuarine NO − 3 along a mixing line between shallow and deep groundwater provided strong evidence for the predominance of groundwater‐derived NO − 3 in the estuary. During dry periods when water residence time in the estuary was extended, shallow groundwater contributed 60% to 76% of the NO − 3 (calculated from δ 15 N‐NO − 3 and δ 18 O‐NO − 3 ) to the estuary, and assimilation removed ∼ 70% of this groundwater‐derived NO − 3 . During wet periods, deep groundwater provided more (62%) NO − 3 than shallow groundwater, and there was no indication of NO − 3 consumption. Occasional sources of NO − 3 , which were also reflected by their δ 15 N‐NO − 3 and δ 18 O‐NO − 3 values, included NO − 3 from nitrification and sewage‐derived NO − 3 particularly at the bay entrance to the estuary. Greater emphasis should be placed upon the role of groundwater as a substantial NO − 3 end member when assessing NO − 3 biogeochemistry using methods relying on the dual isotopic composition of NO − 3 .

Hydroacoustic tracking of the endangered Atlantic whitefish (Coregonus huntsmani); comparative analysis from wild and hatchery reared populations - A. M. Cook; R. G. Bradford; P. Bentzen (Environmental Biology of Fishes, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Temperature effects on metabolic rate and cardiorespiratory physiology of the spiny rock lobster (Jasus edwardsii) during rest, emersion and recovery - Leonard G. Forgan; Nicholas P. L. Tuckey; Denham G. Cook; Alistair R. Jerrett (Journal of Comparative Physiology B, 2014)

Turning passive detection systems into field experiments: an application using wetland fishes and enclosures to track fine-scale movement and habitat choice - J. S. Rehage; R. E. Boucek; E. A. Cline; M. I. Cook; R. M. Kobza; A. K. Saha (acta ethologica, 2014)

Characterising the distribution of near-shore submarine groundwater discharge along a coastline using 222 Rn and electrical conductivity - M. A. Short; S. Lamontagne; P. G. Cook; R. Cranswick (Australian Journal of Earth Sciences, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Effect of the duration of inoculum exposure on development of citrus canker symptoms on seedlings of Swingle citrumelo - Clive H. Bock; James H. Graham; Tim R. Gottwald; Amanda Z. Cook; Paul E. Parker (European Journal of Plant Pathology, 2014)

Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2014)
HIV-associated neurocognitive disorder (HAND), characterized by a wide spectrum of behavioral, cognitive, and motor dysfunctions, continues to affect approximately 50 % of HIV(+) patients despite the success of combination antiretroviral drug therapy (cART) in the periphery. Of note, potential toxicity of antiretroviral drugs in the central nervous system (CNS) remains remarkably underexplored and may contribute to the persistence of HAND in the cART era. Previous studies have shown antiretrovirals (ARVs) to be neurotoxic in the peripheral nervous system in vivo and in peripheral neurons in vitro. Alterations in lipid and protein metabolism, mitochondrial damage, and oxidative stress all play a role in peripheral ARV neurotoxicity. We hypothesized that ARVs also induce cellular stresses in the CNS, ultimately leading to neuronal damage and contributing to the changing clinical and pathological picture seen in HIV-positive patients in the cART era. In this report, we show that ARVs are neurotoxic in the CNS in both pigtail macaques and rats in vivo. Furthermore, in vitro, ARVs lead to accumulation of reactive oxygen species (ROS), and ultimately induction of neuronal damage and death. Whereas ARVs alone caused some activation of the endogenous antioxidant response in vitro, augmentation of this response by a fumaric acid ester, monomethyl fumarate (MMF), blocked ARV-induced ROS generation, and neuronal damage/death. These findings implicate oxidative stress as a contributor to the underlying mechanisms of ARV-induced neurotoxicity and will provide an access point for adjunctive therapies to complement ARV therapy and reduce neurotoxicity in this patient population.

Colony social structure in native and invasive populations of the social wasp Vespula pensylvanica - Cause Hanna; Erin D. Cook; Ariel R. Thompson; Lyndzey E. Dare; Amanda L. Palaski; David Foote; Michael A. D. Goodisman (Biological Invasions, 2014)

New data on gastrointestinal helminths in shags (Phalacrocorax verrucosus) at Kerguelen Archipelago - Frédéric Fonteneau; Timothée R. Cook (Polar Biology, 2013)

Genetic diversity and complementary sex determination (CSD) in Dolerus aeneus (Hymenoptera, Symphyta): implications for the conservation of an ecologically-important sawfly - N. Cook; S. F. Hubbard; A. J. Karley; J. R. Russell (Conservation Genetics, 2013)

Tree-ring reconstructed summer temperature anomalies for temperate East Asia since 800 C.E. - Edward R. Cook; Paul J. Krusic; Kevin J. Anchukaitis; Brendan M. Buckley; Takeshi Nakatsuka; Masaki Sano (Climate Dynamics, 2013)

Case–control study of lifetime alcohol consumption and endometrial cancer risk - Christine M. Friedenreich; Thomas P. Speidel; Heather K. Neilson; Annie R. Langley; Kerry S. Courneya; Anthony M. Magliocco; Linda S. Cook (Cancer Causes & Control, 2013)

Estimating the Cost and Carbon Impact of a Long Term Water Main Rehabilitation Strategy - D. J. Beale; D. R. Marlow; S. Cook (Water Resources Management, 2013)

An improved solution for the infiltration advance problem in irrigation hydraulics - F. J. Cook; J. H. Knight; R. C. Doble; S. R. Raine (Irrigation Science, 2013)

A revised look: EPA rulemaking processes - Jeffrey J. Cook; Sara R. Rinfret (Journal of Environmental Studies and Sciences, 2013)

Dynamics of groundwater‐derived nitrate and nitrous oxide in a tidal estuary from radon mass balance modeling - Wei Wen Wong; Michael R. Grace; Ian Cartwright; M. Bayani Cardenas; Peter B. Zamora; Perran L. M. Cook (Limnology and Oceanography, 2013)
We monitored submarine groundwater discharge (SGD) into the Werribee Estuary, Australia, using both chemical and physical methods. SGD occurred at hotspots where 222 Rn persisted through a 12 month survey period. A significant correlation between 222 Rn and ( r 2 = 0.8, p 222 Rn and N 2 O ( r 2 = 0.6, p 222 Rn hotspot, and much higher and N 2 O concentrations in groundwater relative to surface water suggest that elevated and N 2 O concentrations in the estuary were derived from SGD. Two sampling campaigns over 24 h revealed that variations of 222 Rn,, and N 2 O were controlled by tide‐induced hydraulic‐head gradient fluctuations and, possibly to a much lesser extent, by tidal pumping and density‐driven convection. A two‐box 222 Rn mass‐balance model was used to calculate the rate of SGD into two different layers across the pycnocline of the estuary. A higher total groundwater discharge rate of 0.12 ± 0.09 m d −1 was observed in the surface layer during ebb tide compared with 0.10 ± 0.08 m d −1 during flood tide. Fluxes of groundwater‐derived and N 2 O were higher than the riverine flux at baseflow by more than 30 fold and 20 fold, respectively. SGD derived fluxes exceeded the mean annual riverine and TN fluxes by a factor of ∼ 5 and ∼ 3 respectively. SGD‐derived N 2 O fluxes were 170 µmol m −2 d −1 , which are among the highest N 2 O fluxes observed in estuaries.

On the influence of tree size on the climate–growth relationship of New Zealand kauri (Agathis australis): insights from annual, monthly and daily growth patterns - Jan Wunder; Anthony M. Fowler; Edward R. Cook; Maryann Pirie; Shane P. J. McCloskey (Trees, 2013)

Reliability of individual and pooled test procedures for detecting the pathogenic agent for clinical infectious salmon anaemia - M Hall; I S Wallace; L A Munro; E S Munro; R McIntosh; P Cook; C E T Allan; A G Murray (Journal of Fish Diseases, 2013)

A comment on “What catch data can tell us about the status of global fisheries” (Froese et al. 2012) - R. M. Cook (Marine Biology, 2013)

A strong regional temperature signal in low‐elevation Huon pine - K. J. ALLEN; D. M. DREW; G. M. DOWNES; R. EVANS; E. R. COOK; M. BATTAGLIA; P. J. BAKER (Journal of Quaternary Science, 2013)
We have produced the first annually resolved, centennial‐length tree‐ring chronologies, based on tracheid radial diameter (TRD) and microfibril angle for south‐eastern Australia (SEA) from what would commonly be considered a dendroclimatically suboptimal site. The chronologies exhibit a strong regional temperature signal for the austral summer (nominally November–April) that extends across much of SEA. The strength and spatial extent of the temperature–TRD correlations surpass those between the iconic Tasmanian Mt Read ring‐width chronology and austral summer temperatures, and are more time‐stable. We demonstrate that the value of wood property chronologies for their ability to improve the both the quality and the quantity of highly climate‐sensitive series available for regional annual‐resolution climate reconstructions, in data‐sparse regions in Australasia and beyond, should be examined. In light of the ‘divergence debate’, the time‐stability of relationships with climate, relative to other tree‐ring proxies, also requires further investigation.

A comparison of culture-dependent and culture-independent techniques used to characterize bacterial communities on healthy and white plague-diseased corals of the Montastraea annularis species complex - G. M. Cook; J. P. Rothenberger; M. Sikaroodi; P. M. Gillevet; E. C. Peters; R. B. Jonas (Coral Reefs, 2013)

Alpine cushion plants inhibit the loss of phylogenetic diversity in severe environments - B. J. Butterfield; L. A. Cavieres; R. M. Callaway; B. J. Cook; Z. Kikvidze; C. J. Lortie; R. Michalet; F. I. Pugnaire; C. Schöb; S. Xiao; B. Zaitchek; F. Anthelme; et al. (Ecology Letters, 2013)
Biotic interactions can shape phylogenetic community structure (PCS). However, we do not know how the asymmetric effects of foundation species on communities extend to effects on PCS. We assessed PCS of alpine plant communities around the world, both within cushion plant foundation species and adjacent open ground, and compared the effects of foundation species and climate on alpha (within‐microsite), beta (between open and cushion) and gamma (open and cushion combined) PCS. In the open, alpha PCS shifted from highly related to distantly related with increasing potential productivity. However, we found no relationship between gamma PCS and climate, due to divergence in phylogenetic composition between cushion and open sub‐communities in severe environments, as demonstrated by increasing phylo‐beta diversity. Thus, foundation species functioned as micro‐refugia by facilitating less stress‐tolerant lineages in severe environments, erasing a global productivity – phylogenetic diversity relationship that would go undetected without accounting for this important biotic interaction.

Links between Indo-Pacific climate variability and drought in the Monsoon Asia Drought Atlas - Caroline C. Ummenhofer; Rosanne D. D’Arrigo; Kevin J. Anchukaitis; Brendan M. Buckley; Edward R. Cook (Climate Dynamics, 2013)

Amycolatopsis umgeniensis sp. nov., isolated from soil from the banks of the Umgeni River in South Africa - Gareth J. Everest; Marilize le Roes-Hill; Clifford Omorogie; Shuk-Kwan Cheung; Andrew E. Cook; Candice M. Goodwin; Paul R. Meyers (Antonie van Leeuwenhoek, 2013)

A high-throughput SNP marker system for parental polymorphism screening, and diversity analysis in common bean (Phaseolus vulgaris L.) - Matthew W. Blair; Andrés J. Cortés; R. Varma Penmetsa; Andrew Farmer; Noelia Carrasquilla-Garcia; Doug R. Cook (Theoretical and Applied Genetics, 2013)

Epidemiology of Helicobacter pylori infection in six Latin American countries (SWOG Trial S0701) - Carolina Porras; Jesse Nodora; Rachael Sexton; Catterina Ferreccio; Silvia Jimenez; Ricardo L. Dominguez; Paz Cook; Garnet Anderson; Douglas R. Morgan; Laurence H. Baker; E. Robert Greenberg; Rolando Herrero (Cancer Causes & Control, 2013)

Sensitivity of Spring Phenology to Warming Across Temporal and Spatial Climate Gradients in Two Independent Databases - Benjamin I. Cook; Elizabeth M. Wolkovich; T. Jonathan Davies; Toby R. Ault; Julio L. Betancourt; Jenica M. Allen; Kjell Bolmgren; Elsa E. Cleland; Theresa M. Crimmins; Nathan J. B. Kraft; Lesley T. Lancaster; Susan J. Mazer; et al. (Ecosystems, 2012)

Harmonised Investigation of the Occurrence of Human Enteric Viruses in the Leafy Green Vegetable Supply Chain in Three European Countries - P. Kokkinos; I. Kozyra; S. Lazic; M. Bouwknegt; S. Rutjes; K. Willems; R. Moloney; A. M. de Roda Husman; A. Kaupke; E. Legaki; M. D’Agostino; N. Cook; et al. (Food and Environmental Virology, 2012)

Parameter and uncertainty estimation for process‐oriented population and distribution models: data, statistics and the niche - Glenn Marion; Greg J. McInerny; Jörn Pagel; Stephen Catterall; Alex R. Cook; Florian Hartig; Robert B. O'Hara (Journal of Biogeography, 2012)
The spatial distribution of a species is determined by dynamic processes such as reproduction, mortality and dispersal. Conventional static species distribution models (SDMs) do not incorporate these processes explicitly. This limits their applicability, particularly for non‐equilibrium situations such as invasions or climate change. In this paper we show how dynamic SDMs can be formulated and fitted to data within a Bayesian framework. Our focus is on discrete state‐space Markov process models which provide a flexible framework to account for stochasticity in key demographic processes, including dispersal, growth and competition. We show how to construct likelihood functions for such models (both discrete and continuous time versions) and how these can be combined with suitable observation models to conduct Bayesian parameter inference using computational techniques such as Markov chain Monte Carlo. We illustrate the current state‐of‐the‐art with three contrasting examples using both simulated and empirical data. The use of simulated data allows the robustness of the methods to be tested with respect to deficiencies in both data and model. These examples show how mechanistic understanding of the processes that determine distribution and abundance can be combined with different sources of information at a range of spatial and temporal scales. Application of such techniques will enable more reliable inference and projections, e.g. under future climate change scenarios than is possible with purely correlative approaches. Conversely, confronting such process‐oriented niche models with abundance and distribution data will test current understanding and may ultimately feedback to improve underlying ecological theory.

Influences of the El Niño Southern Oscillation and the Pacific Decadal Oscillation on the timing of the North American spring - Gregory J. McCabe; Toby R. Ault; Benjamin I. Cook; Julio L. Betancourt; Mark D. Schwartz (International Journal of Climatology, 2012)
Detrended, modelled first leaf dates for 856 sites across North America for the period 1900–2008 are used to examine how the El Niño Southern Oscillation (ENSO) and the Pacific Decadal Oscillation (PDO) separately and together might influence the timing of spring. Although spring (mean March through April) ENSO and PDO signals are apparent in first leaf dates, the signals are not statistically significant (at a 95% confidence level ( p p

Development of a nested PCR assay to detect equine infectious anemia proviral DNA from peripheral blood of naturally infected horses - Jian-Bao Dong; Wei Zhu; Frank R. Cook; Yoshitaka Goto; Yoichiro Horii; Takeshi Haga (Archives of Virology, 2012)

An intra-specific consensus genetic map of pigeonpea [Cajanus cajan (L.) Millspaugh] derived from six mapping populations - Abhishek Bohra; Rachit K. Saxena; B. N. Gnanesh; Kulbhushan Saxena; M. Byregowda; Abhishek Rathore; P. B. KaviKishor; Douglas R. Cook; Rajeev K. Varshney (Theoretical and Applied Genetics, 2012)

The “salt wedge pump”: Convection‐driven pore‐water exchange as a source of dissolved organic and inorganic carbon and nitrogen to an estuary - Isaac R. Santos; Perran L. M. Cook; Louissa Rogers; Jason de Weys; Bradley D. Eyre (Limnology and Oceanography, 2012)
Hypoxia and anoxia in coastal waters have typically been explained by the respiration of sinking organic matter associated with nutrient over‐enrichment and phytoplankton blooms. Here, we assess whether submarine groundwater discharge and seawater recirculation in sediments can explain widespread chemical anomalies, including low dissolved oxygen, in salt wedge estuaries. We rely on high‐resolution radon (a natural groundwater and pore‐water tracer), and dissolved carbon concentrations and stable isotope observations in the Yarra River estuary in Melbourne, Australia. Radon was highly enriched within the salt wedge, demonstrating enhanced pore‐water exchange at this area. We use the term “salt wedge pump” to describe convection‐driven advective pore‐water exchange at the sediment–water interface during the upstream propagation of the salt wedge. Radon‐derived convection‐driven pore‐water exchange rates within the salt wedge were estimated at 2.8 cm d −1 , a value equivalent to 2.4% of the total river freshwater runoff to the estuary. Pore‐water exchange led to pulsed dissolved inorganic carbon (DIC) and ammonium fluxes ∼ 10‐fold higher than measured diffusive fluxes. In contrast, diffusive sediment oxygen uptake was 5‐fold higher than oxygen uptake related to advective pore‐water exchange. Estimated fluxes, associated with the nonconservative DIC, δ 13 C‐DIC, and ammonium behavior within the estuary support convective pore‐water exchange as a major source of DIC and ammonium to the estuary, but not of dissolved organic carbon, nitrate, dissolved organic nitrogen, and anoxia. Accounting for seawater recirculation in sediments may help reconcile unbalanced carbon and nitrogen budgets in several coastal systems.

Net ecosystem exchange modifies the relationship between the autotrophic and heterotrophic components of soil respiration with abiotic factors in prairie grasslands - Nuria Gomez‐Casanovas; Roser Matamala; David R. Cook; Miquel A. Gonzalez‐Meler (Global Change Biology, 2012)
We investigated the relationships of net ecosystem carbon exchange ( NEE ), soil temperature, and moisture with soil respiration rate and its components at a grassland ecosystem. Stable carbon isotopes were used to separate soil respiration into autotrophic and heterotrophic components within an eddy covariance footprint during the 2008 and 2009 growing seasons. After correction for self‐correlation, rates of soil respiration and its autotrophic and heterotrophic components for both years were found to be strongly influenced by variations in daytime NEE – the amount of C retained in the ecosystem during the daytime, as derived from NEE measurements when photosynthetically active radiation was above 0 μmol m −2 s −1 . The time scale for correlation of variations in daytime NEE with fluctuations in respiration was longer for heterotrophic respiration (36–42 days) than for autotrophic respiration (4–6 days). In addition to daytime NEE , autotrophic respiration was also sensitive to soil moisture but not soil temperature. In contrast, heterotrophic respiration from soils was sensitive to changes in soil temperature, soil moisture, and daytime NEE . Our results show that – as for forests – plant activity is an important driver of both components of soil respiration in this tallgrass prairie grassland ecosystem. Heterotrophic respiration had a slower coupling with plant activity than did autotrophic respiration. Our findings suggest that the frequently observed variations in the sensitivity of soil respiration to temperature or moisture may stem from variations in the proportions of autotrophic and heterotrophic components of soil respiration. Rates of photosynthesis at seasonal time scales should also be considered as a driver of both autotrophic and heterotrophic soil respiration for ecosystem flux modeling.

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Ubiquitous Brms1 expression is critical for mammary carcinoma metastasis suppression via promotion of apoptosis - Leah M. Cook; Xuemei Cao; Alexander E. Dowell; Michael T. Debies; Mick D. Edmonds; Benjamin H. Beck; Robert A. Kesterson; Renee A. Desmond; Andra R. Frost; Douglas R. Hurst; Danny R. Welch (Clinical & Experimental Metastasis, 2012)

Reconciling estimates of the contemporary North American carbon balance among terrestrial biosphere models, atmospheric inversions, and a new approach for estimating net ecosystem exchange from inventory‐based data - Daniel J. Hayes; David P. Turner; Graham Stinson; A. David McGuire; Yaxing Wei; Tristram O. West; Linda S. Heath; Bernardus de Jong; Brian G. McConkey; Richard A. Birdsey; Werner A. Kurz; Andrew R. Jacobson; et al. (Global Change Biology, 2012)
We develop an approach for estimating net ecosystem exchange ( NEE ) using inventory‐based information over North America ( NA ) for a recent 7‐year period (ca. 2000–2006). The approach notably retains information on the spatial distribution of NEE , or the vertical exchange between land and atmosphere of all non‐fossil fuel sources and sinks of CO 2 , while accounting for lateral transfers of forest and crop products as well as their eventual emissions. The total NEE estimate of a −327 ± 252 TgC yr −1 sink for NA was driven primarily by CO 2 uptake in the Forest Lands sector (−248 TgC yr −1 ), largely in the Northwest and Southeast regions of the US, and in the Crop Lands sector (−297 TgC yr −1 ), predominantly in the Midwest US states. These sinks are counteracted by the carbon source estimated for the Other Lands sector (+218 TgC yr −1 ), where much of the forest and crop products are assumed to be returned to the atmosphere (through livestock and human consumption). The ecosystems of Mexico are estimated to be a small net source (+18 TgC yr −1 ) due to land use change between 1993 and 2002. We compare these inventory‐based estimates with results from a suite of terrestrial biosphere and atmospheric inversion models, where the mean continental‐scale NEE estimate for each ensemble is −511 TgC yr −1 and −931 TgC yr −1 , respectively. In the modeling approaches, all sectors, including Other Lands, were generally estimated to be a carbon sink, driven in part by assumed CO 2 fertilization and/or lack of consideration of carbon sources from disturbances and product emissions. Additional fluxes not measured by the inventories, although highly uncertain, could add an additional −239 TgC yr −1 to the inventory‐based NA sink estimate, thus suggesting some convergence with the modeling approaches.

GPS and time-depth loggers reveal underwater foraging plasticity in a flying diver, the Cape Cormorant - Timothée R. Cook; Maike Hamann; Lorien Pichegru; Francesco Bonadonna; David Grémillet; Peter G. Ryan (Marine Biology, 2012)

Macronutrient regulation in the Rasberry crazy ant (Nylanderia sp. nr. pubens) - S. C. Cook; R. A. Wynalda; R. E. Gold; S. T. Behmer (Insectes Sociaux, 2012)

Influence of Phenological Stage on Swainsonine and Endophyte Concentrations in Oxytropis sericea - Daniel Cook; Lei Shi; Dale R. Gardner; James A. Pfister; Daniel Grum; Kevin D. Welch; Michael H. Ralphs (Journal of Chemical Ecology, 2012)

Sources and fate of nutrients in a subtropical reservoir - Michele A. Burford; Susanne A. Green; Andrew J. Cook; Suzanne A. Johnson; Jason G. Kerr; Katherine R. O’Brien (Aquatic Sciences, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

The potential to reconstruct broadscale climate indices associated with southeast Australian droughts from Athrotaxis species, Tasmania - K. J. Allen; J. Ogden; B. M. Buckley; E. R. Cook; P. J. Baker (Climate Dynamics, 2011)

Evaluation of the use of recN sequence analysis in the phylogeny of the genus Amycolatopsis - Gareth J. Everest; Andrew E. Cook; Bronwyn M. Kirby; Paul R. Meyers (Antonie van Leeuwenhoek, 2011)

Problematic but promising ponds? Palaeoenvironmental evidence from the Norse Eastern Settlement of Greenland - Kevin J. Edwards; J. Edward Schofield; Jason R. Kirby; Gordon T. Cook (Journal of Quaternary Science, 2011)
Pollen‐ and related proxy‐based studies of human–environment interactions during the Norse and later periods within Greenland have primarily involved the investigation of peat, lake and soil deposits, all of which have taphonomic and sampling problems. Many small ponds exist, but they seem to have been relatively ignored in investigations of palaeoecologically based environmental history. To evaluate their usefulness for studies of ecologically related cultural history, especially where sites are in intimate association with the archaeology, a pond in the Norse Eastern Settlement has been examined to investigate three principal questions: (i) Does such a site contain a useful record of environmental history? (ii) Does it offer a record of sufficient resolution and sensitivity for the study of anthropogenic landscape impacts? (iii) Are there any apparent drawbacks to these sequences? Using data obtained from palynological, diatom, sedimentological and radiocarbon analyses, it is concluded that environmental data for each proxy – aside from 14 C dating – are clearly capable of being explained in a reasonably straightforward and compatible manner and fulfil the hopes for the sampling medium. Copyright © 2011 John Wiley & Sons, Ltd.

Transcriptome sequencing of an ecologically important graminivorous sawfly: a resource for marker development - N. Cook; N. Aziz; P. E. Hedley; J. Morris; L. Milne; A. J. Karley; S. F. Hubbard; J. R. Russell (Conservation Genetics Resources, 2011)

Forced and unforced variability of twentieth century North American droughts and pluvials - Benjamin I. Cook; Edward R. Cook; Kevin J. Anchukaitis; Richard Seager; Ron L. Miller (Climate Dynamics, 2011)

Tobacco withdrawal components and their relations with cessation success - Megan E. Piper; Tanya R. Schlam; Jessica W. Cook; Megan A. Sheffer; Stevens S. Smith; Wei-Yin Loh; Daniel M. Bolt; Su-Young Kim; Jesse T. Kaye; Kathryn R. Hefner; Timothy B. Baker (Psychopharmacology, 2011)

Repurposing climate reconstructions for drought prediction in Southeast Asia - Andrew R. Bell; Benjamin I. Cook; Kevin J. Anchukaitis; Brendan M. Buckley; Edward R. Cook (Climatic Change, 2011)

Development and use of genic molecular markers (GMMs) for construction of a transcript map of chickpea (Cicer arietinum L.) - Neha Gujaria; Ashish Kumar; Preeti Dauthal; Anuja Dubey; Pavana Hiremath; A. Bhanu Prakash; Andrew Farmer; Mangla Bhide; Trushar Shah; Pooran M. Gaur; Hari D. Upadhyaya; Sabhyata Bhatia; et al. (Theoretical and Applied Genetics, 2011)

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

Factors limiting the health of semi-scavenging ducks in Bangladesh - M. A. Hoque; L. F. Skerratt; A. J. C. Cook; S. A. Khan; D. Grace; M. R. Alam; A. Vidal-Diez; N. C. Debnath (Tropical Animal Health and Production, 2011)

Characterization of zinc transport by divalent metal transporters of the ZIP family from the model legume Medicago truncatula - Brian W. Stephens; Douglas R. Cook; Michael A. Grusak (BioMetals, 2011)

Non-specific (entropic) forces as major determinants of the structure of mammalian chromosomes - Kieran Finan; Peter R. Cook; Davide Marenduzzo (Chromosome Research, 2011)

A Novel Shape Memory Alloy Annuloplasty Ring for Minimally Invasive Surgery: Design, Fabrication, and Evaluation - Molly F. Purser; Andrew L. Richards; Richard C. Cook; Jason A. Osborne; Denis R. Cormier; Gregory D. Buckner (Annals of Biomedical Engineering, 2011)

Wind speed and wind-associated leaf injury affect severity of citrus canker on Swingle citrumelo - C. H. Bock; James H. Graham; Tim R. Gottwald; Amanda Z. Cook; Paul E. Parker (European Journal of Plant Pathology, 2010)

Genetic variation in sex-steroid receptors and synthesizing enzymes and colorectal cancer risk in women - Jennifer Lin; Robert Y. L. Zee; Kuang-Yu Liu; Shumin M. Zhang; I-Min Lee; JoAnn E. Manson; Edward Giovannucci; Julie E. Buring; Nancy R. Cook (Cancer Causes & Control, 2010)

Integration of novel SSR and gene-based SNP marker loci in the chickpea genetic map and establishment of new anchor points with Medicago truncatula genome - Spurthi N. Nayak; Hongyan Zhu; Nicy Varghese; Subhojit Datta; Hong-Kyu Choi; Ralf Horres; Ruth Jüngling; Jagbir Singh; P. B. Kavi Kishor; S. Sivaramakrishnan; Dave A. Hoisington; Günter Kahl; et al. (Theoretical and Applied Genetics, 2010)

Effect of a flood event on the dynamics of phytoplankton and biogeochemistry in a large temperate Australian lagoon - Perran L. M. Cook; Daryl P. Holland; Andrew R. Longmore (Limnology and Oceanography, 2010)
In episodically driven estuaries, nutrient delivery is typically confined to sporadic flow events, followed by intense biogeochemical recycling of nutrients. We document the response of a temperate lagoon system with episodic winter‐ or spring‐dominated catchment inflows (Gippsland Lakes, southeast Australia) to a flood event. High winter inflows resulted in high surface‐water concentrations of inorganic nitrogen (IN; NO 2 − + NO 3 − + NH 4 + ) relative to reactive phosphorus (RP) with an IN :RP ratio > 100. This resulted in a rapid diatom and dinoflagellate bloom, which collapsed as water column nutrients were exhausted. Increased carbon delivery to the sediment stimulated benthic respiration and depleted bottom‐water oxygen, which led to a large release of RP from the sediments, decreasing the IN :RP ratio in the bottom water to ~6. Strong stratification of the water column allowed the accumulation of RP in the bottom water over spring and into summer. Mixing of RP from the bottom water over summer triggered the development of a Nodularia spumigena Mertens bloom. As such, the nutrient supply for the Nodularia bloom was through a biogeochemical filter that strongly favored N 2 ‐fixing cyanobacterial blooms by reducing IN :RP ratios through a combination of sediment denitrification and release of stored phosphorus from within the sediment. These observations lead us to the paradoxical conclusion that high nitrogen loading over winter contributed to severe nitrogen limitation over summer, and highlight the importance of controlling both nitrogen and phosphorus loading to estuaries.

Evaluation of a CXCR4 antagonist in a xenograft mouse model of inflammatory breast cancer - Balraj Singh; Kendra R. Cook; Cecilia Martin; Eugene H. Huang; Kailash Mosalpuria; Savitri Krishnamurthy; Massimo Cristofanilli; Anthony Lucci (Clinical & Experimental Metastasis, 2010)

A mark-recapture population estimate for invasive silver carp (Hypophthalmichthys molitrix) in the La Grange Reach, Illinois River - Greg G. Sass; Thad R. Cook; Kevin S. Irons; Michael A. McClelland; Nerissa N. Michaels; T. Matthew O’Hara; Matthew R. Stroub (Biological Invasions, 2010)

Biogeography of the Australian monsoon tropics - D. M. J. S. Bowman; G. K. Brown; M. F. Braby; J. R. Brown; L. G. Cook; M. D. Crisp; F. Ford; S. Haberle; J. Hughes; Y. Isagi; L. Joseph; J. McBride; et al. (Journal of Biogeography, 2010)
Aim This paper reviews the biogeography of the Australian monsoon tropical biome to highlight general patterns in the distribution of a range of organisms and their environmental correlates and evolutionary history, as well as to identify knowledge gaps. Location Northern Australia, Australian Monsoon Tropics (AMT). The AMT is defined by areas that receive more than 85% of rainfall between November and April. Methods Literature is summarized, including the origin of the monsoon climate, present‐day environment, biota and habitat types, and phylogenetic and geographical relationships of selected organisms. Results Some species are widespread throughout the AMT while others are narrow‐range endemics. Such contrasting distributions correspond to present‐day climates, hydrologies (particularly floodplains), geological features (such as sandstone plateaux), fire regimes, and vegetation types (ranging from rain forest to savanna). Biogeographical and phylogenetic studies of terrestrial plants (e.g. eucalypts) and animals (vertebrates and invertebrates) suggest that distinct bioregions within the AMT reflect the aggregated effects of landscape and environmental history, although more research is required to determine and refine the boundaries of biogeographical zones within the AMT. Phylogenetic analyses of aquatic organisms (fishes and prawns) suggest histories of associations with drainage systems, dispersal barriers, links to New Guinea, and the existence of Lake Carpentaria, now submerged by the Gulf of Carpentaria. Complex adaptations to the landscape and climate in the AMT are illustrated by a number of species. Main conclusions The Australian monsoon is a component of a single global climate system, characterized by a dominant equator‐spanning Hadley cell. Evidence of hot, seasonally moist climates dates back to the Late Eocene, implying that certain endemic elements of the AMT biota have a long history. Vicariant differentiation is inferred to have separated the Kimberley and Arnhem Land bioregions from Cape York Peninsula/northern Queensland. Such older patterns are overlaid by younger events, including dispersal from Southeast Asia, and range expansions and contractions. Future palaeoecological and phylogenetic investigations will illuminate the evolution of the AMT biome. Understanding the biogeography of the AMT is essential to provide a framework for ecological studies and the sustainable development of the region.

Megadroughts in North America: placing IPCC projections of hydroclimatic change in a long‐term palaeoclimate context - Edward R. Cook; Richard Seager; Richard R. Heim; Russell S. Vose; Celine Herweijer; Connie Woodhouse (Journal of Quaternary Science, 2010)
IPCC Assessment Report 4 model projections suggest that the subtropical dry zones of the world will both dry and expand poleward in the future due to greenhouse warming. The US Southwest is particularly vulnerable in this regard and model projections indicate a progressive drying there out to the end of the 21st century. At the same time, the USA has been in a state of drought over much of the West for about 10 years now. While severe, this turn of the century drought has not yet clearly exceeded the severity of two exceptional droughts in the 20th century. So while the coincidence between the turn of the century drought and projected drying in the Southwest is cause for concern, it is premature to claim that the model projections are correct. At the same time, great new insights into past drought variability over North America have been made through the development of the North American Drought Atlas from tree rings. Analyses of this drought atlas have revealed past megadroughts of unprecedented duration in the West, largely in the Medieval period about 1000 years ago. A vastly improved Living Blended Drought Atlas (LBDA) for North America now under development reveals these megadroughts in far greater detail. The LBDA indicates the occurrence of the same Medieval megadroughts in the West and similar‐scale megadroughts in the agriculturally and commercially important Mississippi Valley. Possible causes of these megadroughts and their implications for the future are discussed. Copyright © 2009 John Wiley & Sons, Ltd.

Amoebic gill disease resistance is not related to the systemic antibody response of Atlantic salmon, Salmo salar L. - R S Taylor; P B Crosbie; M T Cook (Journal of Fish Diseases, 2010)
Amoebic gill disease (AGD) is a proliferative gill tissue response caused by Neoparamoeba perurans and is the main disease affecting Australian marine farmed Atlantic salmon. We have previously proposed that macroscopic gill health (‘gill score’) trajectories and challenge survival provide evidence of a change in the nature of resistance to AGD. In order to examine whether the apparent development of resistance was because of an adaptive response, serum was sequentially sampled from the same individuals over the first three rounds of natural AGD infection and from survivors of a subsequent non‐intervention AGD survival challenge. The systemic immune reaction to ‘wildtype’ Neoparamoeba sp. was characterized by Western blot analysis and differentiated to putative carbohydrate or peptide epitopes by periodate oxidation reactions. The proportion of seropositive fish increased from 46% to 77% with each AGD round. Antibody response to carbohydrate epitope(s) was immunodominant, occurring in 43–64% of samples. Antibodies that bound peptide epitope were identified in 16% of the challenge survivors. A 1:50 (single‐dilution) enzyme‐linked immunosorbent assay confirmed a measurable immune titre in 13% of the survivors. There was no evidence that antibodies recognizing wildtype Neoparamoeba provided significant protection against AGD.

Validation of yellowedge grouper, Epinephelus flavolimbatus, age using nuclear bomb-produced radiocarbon - Melissa Cook; Gary R. Fitzhugh; James S. Franks (Environmental Biology of Fishes, 2009)

The petrogenesis of sodic island arc magmas at Savo volcano, Solomon Islands - D. J. Smith; M. G. Petterson; A. D. Saunders; I. L. Millar; G. R. T. Jenkin; T. Toba; J. Naden; J. M. Cook (Contributions to Mineralogy and Petrology, 2009)

Swainsoninine Concentrations and Endophyte Amounts of Undifilum oxytropis in Different Plant Parts of Oxytropis sericea - Daniel Cook; Dale R. Gardner; Michael H. Ralphs; James A. Pfister; Kevin D. Welch; Benedict T. Green (Journal of Chemical Ecology, 2009)

The Horsfall-Barratt scale and severity estimates of citrus canker - C. H. Bock; T. R. Gottwald; P. E. Parker; A. Z. Cook; F. Ferrandino; S. Parnell; F. van den Bosch (European Journal of Plant Pathology, 2009)

Physical activity, adiposity, and risk of endometrial cancer - Molly B. Conroy; Jacob R. Sattelmair; Nancy R. Cook; JoAnn E. Manson; Julie E. Buring; I-Min Lee (Cancer Causes & Control, 2009)

Accountability, Reporting, or Management Improvement? Development of a State of the Parks Assessment System in New South Wales, Australia - Marc Hockings; Carly N. Cook; R. W. Carter; Robyn James (Environmental Management, 2009)

Moisture variability across China and Mongolia: 1951–2005 - Jinbao Li; Edward R. Cook; Rosanne D’arrigo; Fahu Chen; Xiaohua Gou (Climate Dynamics, 2009)

The Biogeographical Distribution of Duncecap Larkspur (Delphinium occidentale) Chemotypes and Their Potential Toxicity - Daniel Cook; Dale R. Gardner; James A. Pfister; Kevin D. Welch; Benedict T. Green; Stephen T. Lee (Journal of Chemical Ecology, 2009)

An Investigation into the Rheology of Pharmaceutical Inter-granular Material Bridges at High Shear Rates - Barry Crean; Xinyong Chen; Simon R. Banks; Walter G. Cook; Colin D. Melia; Clive J. Roberts (Pharmaceutical Research, 2009)

Steady Groundwater Flow to Drains on a Sloping Bed: Comparison of Solutions Based on Boussinesq Equation and Richards Equation - F. J. Cook; J. H. Knight; R. A. Wooding (Transport in Porous Media, 2009)

Electronic tags reveal behaviour of captured and discarded fish - F. C. Neat; M. Breen; R. M. Cook; I. M. Gibb; P. J. Wright (Journal of Fish Biology, 2009)
Internally implanted data storage tags (DST) recording hydrostatic pressure (depth) and temperature in Atlantic cod Gadus morhua were used to track the behaviour of nine individuals during fishing operations. Gadus morhua showed identifiable and characteristic behavioural responses to different capture processes. In a unique observation, one fish survived being discarded and upon return to the seabed exhibited a cessation of activity comparable to observations on stressed fish under laboratory conditions.

Cryptic seedling herbivory by nocturnal introduced generalists impacts survival, performance of native and exotic plants - Sharon Y. Strauss; Maureen L. Stanton; Nancy C. Emery; Carrie A. Bradley; Alexandra Carleton; Dylan R. Dittrich-Reed; Olivia A. Ervin; Levi N. Gray; Andrew M. Hamilton; Jennifer Harrington Rogge; Skye D. Harper; Kimberley Cook Law; et al. (Ecology, 2009)
Although much of the theory on the success of invasive species has been geared at escape from specialist enemies, the impact of introduced generalist invertebrate herbivores on both native and introduced plant species has been underappreciated. The role of nocturnal invertebrate herbivores in structuring plant communities has been examined extensively in Europe, but less so in North America. Many nocturnal generalists (slugs, snails, and earwigs) have been introduced to North America, and 96% of herbivores found during a night census at our California Central Valley site were introduced generalists. We explored the role of these herbivores in the distribution, survivorship, and growth of 12 native and introduced plant species from six families. We predicted that introduced species sharing an evolutionary history with these generalists might be less vulnerable than native plant species. We quantified plant and herbivore abundances within our heterogeneous site and also established herbivore removal experiments in 160 plots spanning the gamut of microhabitats. As 18 collaborators, we checked 2000 seedling sites every day for three weeks to assess nocturnal seedling predation. Laboratory feeding trials allowed us to quantify the palatability of plant species to the two dominant nocturnal herbivores at the site (slugs and earwigs) and allowed us to account for herbivore microhabitat preferences when analyzing attack rates on seedlings. The relationship between local slug abundance and percent cover of five common plant taxa at the field site was significantly negatively associated with the mean palatability of these taxa to slugs in laboratory trials. Moreover, seedling mortality of 12 species in open‐field plots was positively correlated with mean palatability of these taxa to both slugs and earwigs in laboratory trials. Counter to expectations, seedlings of native species were neither more vulnerable nor more palatable to nocturnal generalists than those of introduced species. Growth comparison of plants within and outside herbivore exclosures also revealed no differences between native and introduced plant species, despite large impacts of herbivores on growth. Cryptic nocturnal predation on seedlings was common and had large effects on plant establishment at our site. Without intensive monitoring, such predation could easily be misconstrued as poor seedling emergence.

The long road of pain: chronic pain increases perceived distance - Jessica K. Witt; Sally A. Linkenauger; Jonathan Z. Bakdash; Jason S. Augustyn; Andrew Cook; Dennis R. Proffitt (Experimental Brain Research, 2009)

Resolving relationships in some African fungus-growing termites (Termitidae, Macrotermitinae) using molecular phylogeny, morphology, and field parameters - J. P. E. C. Darlington; R. B. Benson; C. E. Cook; G. Walker (Insectes Sociaux, 2008)

Common tree growth anomalies over the northeastern Tibetan Plateau during the last six centuries: implications for regional moisture change - JINBAO LI; EDWARD R. COOK; ROSANNE D'ARRIGO; FAHU CHEN; XIAOHUA GOU; JIANFENG PENG; JIANGUO HUANG (Global Change Biology, 2008)
The world's hydrological cycle is believed to intensify with global warming, yet current climate models have only a limited ability to assess moisture responses at regional scales. Tree‐ring records are a valuable source of information for understanding long‐term, regional‐scale moisture changes, particularly for large regions such as the Tibetan Plateau (TP), where the observational data are short and sparse. Here, we present a new ring‐width chronology developed from Qilian Juniper ( Sabina przewalskii ) wood at two sites on the northeastern TP. This chronology, combined with others from the same region, demonstrates that tree growth anomalies are linked to regional late spring to early summer moisture availability. Although late monsoon season precipitation in the study area decreased during recent decades, tree growth continued to increase due to persistent moisture availability in the early monsoon season. Comparison with global sea surface temperatures (SSTs) indicates that early (late) monsoon season precipitation is closely related to tropical Pacific (Indian Ocean) SSTs, suggesting a possible seasonal shift in the dominant moisture source area for monsoonal precipitation over the northeastern TP. It is further shown that there is a very high degree of coherency regarding low‐frequency tree growth anomalies over the northeastern TP during the last six centuries. The most prominent drought epoch occurred during ca. 1450–1500, which may have been caused by a significant decrease in the thermal gradient between the Eurasian continent and the tropical oceans. A persistent tree growth increase since the 1880s is coincident with global warming, suggesting an intensified early monsoon season moisture regime in the study area.

A cross‐taxa phenological dataset from Mohonk Lake, NY and its relationship to climate - Benjamin I. Cook; Edward R. Cook; Paul C. Huth; John E. Thompson; Anna Forster; Daniel Smiley (International Journal of Climatology, 2008)
We present a detailed analysis of a rare cross‐taxa native species phenology dataset (plant flowering, insect first sighting, and amphibian first sighting) from Mohonk Lake, NY. This dataset is highly unusual in North America for its longevity of record, consistency of methodology and location, diversity of species available, and availability of local daily meteorological data. For each phenology series, we examined the flowering and first sighting Julian calendar dates for the existence of temporal trends. Only one of the five animal species (katydid) showed any evidence for a significant trend in first sighting. In contrast, the plant species showed a rich mixture of temporal trends in flowering that could be divided into four classes: woody plant–no trend, woody plant–negative trend, herbaceous plant–negative trend, and herbaceous plant–positive trend. Many of the trends were found to be statistically significant and robust to the method of trend estimation. The data within each of the four plant classes were also pooled as anomalies to provide more complete temporal coverage for tests of trend robustness. The results were strongly consistent with the trends of the individual species within each class and highly significant statistically. We next correlated the flowering and first sighting dates against growing degree‐day (GDD) summations for each day of the year to measure the sensitivity of each species to this common form of climatic forcing on phenology. All species showed a significant sensitivity to GDD summations, with peak correlations falling on or near the varying median flowering or first sighting dates. These results were robust whether the GDD analyses were conducted over the complete set of observations for each species (beginning on or after 1928) or over a latter period with a more serially complete set of cross‐taxa observations (1970–2002). The GDD correlations indicate significant climate sensitivity in all species, but the different magnitudes of correlation and timing of maximum correlation imply that plant and animal responses to climate changes in the future will not be homogeneous for the tested species at Mohonk Lake. Copyright © 2007 Royal Meteorological Society

Characterization and comparison of intron structure and alternative splicing between Medicago truncatula, Populus trichocarpa, Arabidopsis and rice - Jong-Min Baek; Paul Han; Alberto Iandolino; Douglas R. Cook (Plant Molecular Biology, 2008)

Transcriptome Analyses of Amoebic Gill Disease-affected Atlantic Salmon (Salmo salar) Tissues Reveal Localized Host Gene Suppression - James W. Wynne; Maree G. O’Sullivan; Mathew T. Cook; Glenn Stone; Barbara F. Nowak; David R. Lovell; Nicholas G. Elliott (Marine Biotechnology, 2008)

Brian MacMahon (1923–2007): founder of modern epidemiology - D. Trichopoulos; P. Cole; E. F. Cook; M. Feinleib; R. Hoover; C.-C. Hsieh; D. Hunter; R. Monson; N. Mueller; M. Rahu; E. Rimm; K. Rothman; et al. (Cancer Causes & Control, 2008)

Using Light-Use and Production Efficiency Models to Predict Photosynthesis and Net Carbon Exchange During Forest Canopy Disturbance - Bruce D. Cook; Paul V. Bolstad; Jonathan G. Martin; Faith Ann Heinsch; Kenneth J. Davis; Weiguo Wang; Ankur R. Desai; Ron M. Teclaw (Ecosystems, 2008)

Relationship Between the Endophyte Embellisia spp. and the Toxic Alkaloid Swainsonine in Major Locoweed Species (Astragalus and Oxytropis) - M. H. Ralphs; R. Creamer; D. Baucom; D. R. Gardner; S. L. Welsh; J. D. Graham; C. Hart; D. Cook; B. L. Stegelmeier (Journal of Chemical Ecology, 2008)

Len Muscatine (1932–2007) and his contributions to the understanding of algal-invertebrate endosymbiosis - O. Hoegh-Guldberg; G. Muller-Parker; C. B. Cook; R. D. Gates; E. Gladfelter; R. K. Trench; V. M. Weis (Coral Reefs, 2007)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Management of resident plant growth-promoting rhizobacteria with the cropping system: a review of experience in the US Pacific Northwest - R. James Cook (European Journal of Plant Pathology, 2007)

Neurobehavioral mutants identified in an ENU-mutagenesis project - Melloni N. Cook; Jonathan P. Dunning; Ronald G. Wiley; Elissa J. Chesler; Dabney K. Johnson; Darla R. Miller; Dan Goldowitz (Mammalian Genome, 2007)

Soil–water and solute movement under precision irrigation: knowledge gaps for managing sustainable root zones - S. R. Raine; W. S. Meyer; D. W. Rassam; J. L. Hutson; F. J. Cook (Irrigation Science, 2007)

Tree-ring reconstructed megadroughts over North America since a.d. 1300 - David W. Stahle; Falko K. Fye; Edward R. Cook; R. Daniel Griffin (Climatic Change, 2007)

Drought reconstruction for North Central China from tree rings: the value of the Palmer drought severity index - Jinbao Li; Fahu Chen; Edward R. Cook; Xiaohua Gou; Yongxiang Zhang (International Journal of Climatology, 2007)
We present a drought reconstruction for north central China based on a tree ring‐width chronology developed from two sites of the Chinese pine ( Pinus tabulaeformis ) in the northern Helan Mountains. The drought reconstruction, spanning 1788–1999 A.D. , was developed by calibrating tree‐ring data with the Palmer drought severity index (PDSI), an index that describes the regional moisture condition properly. The reconstruction was verified with independent data, and accounts for 45.7% of the actual PDSI variance during their common period (1941–1999). The full reconstruction indicates that the regional drought variability was relatively stable during the nineteenth century, but became more variable and persistent during the twentieth century. The drought epoch in the late 1920s was the most severe one in our reconstruction. In contrast to a wetting trend in the western area of northwest China, a clear drying trend has occurred in north central China since mid‐1930s. The multitaper method (MTM) spectral analysis indicates the existence of some decadal (∼11.4 year) and interannual (9.1, 6.8, 4.0, 2.7 and 2.1–2.0 year) cycles, which may potentially be the fingerprints of some proposed climate change forcings. Copyright © 2006 Royal Meteorological Society

Genotyping of phenotypically defined cells in neoplasia: enhanced immunoFISH via tyramide signal amplification (TSA) segregates immunophenotypically—defined cell populations for gated genotyping - Raymond R. Tubbs; Kingshuk Das; James R. Cook; James D. Pettay; Patrick C. Roche; Thomas Grogan (Journal of Molecular Histology, 2007)

The specificity of interphase FISH translocation probes in formalin fixed paraffin embedded tissue sections is readily assessed using automated staining and scoring of tissue microarrays constructed from murine xenografts - Raymond R. Tubbs; James Pettay; Todd S. Barry; Eric Swain; Margaret Loftus; James R. Cook; Marek Skacel; Gillian Paine; Patrick Roche; Thomas Grogan (Journal of Molecular Histology, 2007)

Alkaloid Profiles, Concentration, and Pools in Velvet Lupine (Lupinus leucophyllus) Over the Growing Season - Stephen T. Lee; Michael H. Ralphs; Kip E. Panter; Daniel Cook; Dale R. Gardner (Journal of Chemical Ecology, 2007)

Thermal tolerance of a northern population of striped bass Morone saxatilis - A. M. Cook; J. Duston; R. G. Bradford (Journal of Fish Biology, 2006)
Thermal tolerance of age 0+ year Shubenacadie River (Nova Scotia, Canada) striped bass Morone saxatilis juveniles (mean ± s . e . fork length, L F , 19·2 ± 0·2 cm) acclimated in fresh water to six temperatures from 5 to 30° C was measured by both the incipient lethal technique (72 h assay), and the critical thermal method ( C m ). The lower incipient lethal temperature ranged from 2·4 to 11·3° C, and the upper incipient lethal temperature ( I U ) from 24·4 to 33·9° C. The area of thermal tolerance was 618° C 2 . In a separate experiment, the I U of large age 2+ year fish (34·4 ± 0·5 cm L F ) was 1·2 and 0·6° C lower ( P L F ) at acclimation temperatures of 16 and 23° C. Using the C m , loss of equilibrium occurred at 27·4–37·7° C, loss of righting response at 28·1–38·4° C and onset of spasms at 28·5–38·8° C, depending on acclimation temperature. The linear regression slopes for these three responses were statistically similar (0·41; P > 0·05), but the intercepts differed (25·3, 26·0 and 26·5° C; P

Millennia‐long tree‐ring records from Tasmania and New Zealand: a basis for modelling climate variability and forcing, past, present and future - Edward R. Cook; Brendan M. Buckley; Jonathan G. Palmer; Pavla Fenwick; Michael J. Peterson; Gretel Boswijk; Anthony Fowler (Journal of Quaternary Science, 2006)
Progress in the development of millennia‐long tree‐ring chronologies from Australia and New Zealand is reviewed from the perspective of modelling long‐term climate variability there. Three tree species have proved successful in this regard: Huon pine ( Lagarostrobos franklinii ) from Tasmania, silver pine ( L. colensoi ) from the South Island of New Zealand, and kauri ( Agathis australis ) from the North Island of New Zealand. Each of these species is very long‐lived and produces abundant quantities of well‐preserved wood for extending their tree‐ring chronologies back several millennia into the past. The growth patterns on these chronologies strongly correlate with both local and regional warm‐season temperature changes over significant areas of the Southern Hemisphere (especially Huon and silver pine) and to ENSO variability emanating from the equatorial Pacific region (especially kauri). In addition, there is evidence for significant, band‐limited, multi‐decadal and centennial timescale variability in the warm‐season temperature reconstruction based on Huon pine tree rings that may be related to slowly varying changes in ocean circulation dynamics in the southern Indian Ocean. This suggests the possibility of long‐term climate predictability there. Copyright © 2006 John Wiley & Sons, Ltd.

Development of nuclear gene-derived molecular markers linked to legume genetic maps - Hong-Kyu Choi; Melissa A. Luckow; Jeff Doyle; Douglas R. Cook (Molecular Genetics and Genomics, 2006)

Evidence of an oscillating peripheral clock in an equine fibroblast cell line and adipose tissue but not in peripheral blood - Barbara A. Murphy; Mandi M. Vick; Dawn R. Sessions; R. Frank Cook; Barry P. Fitzgerald (Journal of Comparative Physiology A, 2006)

Foraging tactics of chick-rearing Crozet shags: individuals display repetitive activity and diving patterns over time - Timothée R. Cook; Yves Cherel; Yann Tremblay (Polar Biology, 2006)

Rapid development of polyclonal antisera against infectious salmon anaemia virus and its optimization and application as a diagnostic tool - S J McBeath; L M Ellis; P F Cook; L Wilson; K L Urquhart; I R Bricknell (Journal of Fish Diseases, 2006)
Infectious salmon anaemia is an important disease of Atlantic salmon. One of the current methods of diagnosis is the indirect fluorescent antibody test (IFAT), using a monoclonal antibody specific to the haemagglutinin of the virus. The conformationally dependent nature of this antibody could be a drawback in its usefulness in other tests. This study describes the development and optimization of a polyclonal antiserum against infectious salmon anaemia virus, including a method of separating virus from cell culture components within culture supernatant. The antiserum was subsequently optimized for use in a variety of immunological diagnostic tests, including IFAT and an alkaline phosphatase‐based immunoassay, and Western blot.

Sequential extraction and single-step cold-acid extraction: A feasibility study for use with freshwater-canal sediments - Samantha R. Cook; Andrew Parker (Water, Air, & Soil Pollution, 2006)

Phylogenetics of New World Astragalus: Screening of novel nuclear loci for the reconstruction of phylogenies at low taxonomic levels - Rosa A. Scherson; Hong-Kyu Choi; Douglas R. Cook; Michael J. Sanderson (Brittonia, 2005)

Interaction between inflammation-related gene polymorphisms and cigarette smoking on the risk of myocardial infarction in the Physician’s Health Study - Sarah A. Rosner; Paul M. Ridker; Robert Y. L. Zee; Nancy R. Cook (Human Genetics, 2005)

Bidirectional effects of benzodiazepine binding site ligands on active avoidance acquisition and retention: differential antagonism by flumazenil and β-CCt - Miroslav M. Savić; Dragan I. Obradović; Nenad D. Ugrešić; James M. Cook; P. V. V. S. Sarma; Dubravko R. Bokonjić (Psychopharmacology, 2005)

Use of Simulated Annealing for Identifying Essential Fish Habitat in a Multispecies Context - ROSAMONDE R. COOK; PETER J. AUSTER (Conservation Biology, 2005)
Essential fish habitat (EFH) is defined under U.S. federal law, which mandates its protection. Current single‐species approaches to identifying EFH for suites of managed species have resulted in areas designated for protection that are so large that protecting fish habitat has been difficult in the context of fishery management. We evaluated the potential for simulated annealing, a type of mathematical optimization, as a tool for simultaneously identifying EFH for multiple species in four ecological regions of the eastern continental shelf of the United States. Data were obtained from a shelf‐wide trawl survey with site‐specific abundance information spanning 37 years. The data were averaged within units of a sampling grid with 10‐minute squares. We used computer software with an objective function that includes a term for weighting the boundary length of selected sampling units and thereby identifies solutions that meet specific targets for representation under varying degrees of spatial aggregation. We defined representation as a percentage of the cumulative sampled abundance of individual species and examined the effects of these target values and spatial constraints on total (sea‐surface) area and boundary length of solution sets. We also evaluated the algorithm for its ability to select areas where juveniles occurred at high densities as a proxy for habitat value. Annealing solutions covered less total area than would the combined habitats of individual species that capture the same proportion of population abundance. For most species in most solutions, high‐density areas were selected in higher proportions to their relative abundance in a region and solutions contained less total habitat area and smaller boundary lengths. Additionally, sampling units were distributed among two or more discrete localities versus a single location for the same target level of representation. We suggest that simulated annealing is a viable tool for EFH planning with the potential for identifying more spatially conservative habitat areas for protection than a single‐species approach.

Incubation reduces microbial growth on eggshells and the opportunity for trans‐shell infection - Mark I. Cook; Steven R. Beissinger; Gary A. Toranzos; Wayne J. Arendt (Ecology Letters, 2005)
Avian eggshells harbour microbes shortly after laying, and under appropriate ambient conditions they can multiply rapidly, penetrate through shell pores, infect egg contents and cause embryo mortality. We experimentally examined how incubation affects bacterial processes on the eggshells of pearl‐eyed thrashers Margarops fuscatus nesting in tropical montane and lowland forests in Puerto Rico. Bacteria and fungi grew rapidly on shells of newly laid, unincubated eggs exposed to ambient conditions, but declined to low levels on shells of eggs incubated by thrashers. Divergence in bacterial growth between incubated and exposed eggs was more marked at the montane forest than at the lowland site. Pathogenic microorganisms became increasingly dominant on shells of exposed eggs, but these groups were relatively rare on incubated eggs, where more benign, less invasive groups prevailed. Some incubation during laying may be necessary to decrease the probability of trans‐shell infection by reducing the growth of harmful bacteria and fungi on eggshells, although it may increase hatching asynchrony and the likelihood of brood reduction.

Dietary intakes of fruit, vegetables, and fiber, and risk of colorectal cancer in a prospective cohort of women (United States) - Jennifer Lin; Shumin M. Zhang; Nancy R. Cook; Kathryn M. Rexrode; Simin Liu; JoAnn E. Manson; I-Min Lee; Julie E. Buring (Cancer Causes & Control, 2005)

Liquid-feeding performances of ants (Formicidae): ecological and evolutionary implications - Diane W. Davidson; Steven C. Cook; Roy R. Snelling (Oecologia, 2005)

Iodine toxicity in a plant-solution system with and without humic acid - C. L. Mackowiak; P. R. Grossl; K. L. Cook (Plant and Soil, 2005)

Different populations of RNA polymerase II in living mammalian cells - Miki Hieda; Henry Winstanley; Philip Maini; Francisco J. Iborra; Peter R. Cook (Chromosome Research, 2005)

Development of a micro-sward technique for determining intake characteristics of perennial ryegrass varieties - R. J. Orr; K. L. Young; J. E. Cook; R. A. Champion (Euphytica, 2005)

TP53 haplotype-based analysis and incidence of post-angioplasty restenosis - Robert Y. L. Zee; Nancy R. Cook; Chung-Ah Kim; Arturo Fernandez-Cruz; Klaus Lindpaintner (Human Genetics, 2004)

High-quality RNA, cDNA, and derived EST libraries from grapevine (Vitis vinifera L.) - A. B. Iandolino; F. Goes da Silva; H. Lim; H. Choi; L. E. Williams; D. R. Cook (Plant Molecular Biology Reporter, 2004)

Geographic variation in patterns of nestedness among local stream fish assemblages in Virginia - Rosamonde R. Cook; Paul L. Angermeier; Debra S. Finn; N. LeRoy Poff; Kirk L. Krueger (Oecologia, 2004)

Body Mass Index and Risk of Colorectal Cancer in Women (United States) - Jennifer Lin; Shumin M. Zhang; Nancy R. Cook; Kathryn M. Rexrode; I-Min Lee; Julie E. Buring (Cancer Causes & Control, 2004)

West Nile virus: pending crisis for greater sage‐grouse - David E. Naugle; Cameron L. Aldridge; Brett L. Walker; Todd E. Cornish; Brendan J. Moynahan; Matt J. Holloran; Kimberly Brown; Gregory D. Johnson; Edward T. Schmidtmann; Richard T. Mayer; Cecilia Y. Kato; Marc R. Matchett; et al. (Ecology Letters, 2004)
Scientists have feared that emerging infectious diseases could complicate efforts to conserve rare and endangered species, but quantifying impacts has proven difficult until now. We report unexpected impacts of West Nile virus (WNv) on radio‐marked greater sage‐grouse ( Centrocercus urophasianus ), a species that has declined 45–80% and is endangered in Canada and under current consideration for federal listing in the US. We show that WNv reduced late‐summer survival an average of 25% in four radio‐marked populations in the western US and Canada. Serum from 112 sage‐grouse collected after the outbreak show that none had antibodies, suggesting that they lack resistance. The spread of WNv represents a significant new stressor on sage‐grouse and probably other at‐risk species. While managing habitat might lessen its impact on sage‐grouse populations, WNv has left wildlife and public health officials scrambling to address surface water and vector control issues in western North America.

Development of Selective Ligands for Benzodiazepine Receptor Subtypes by Manipulating the Substituents at Positions 3- and 7- of Optically Active BzR Ligands - Xiaoyan Li; Jianming Yu; John R. Atack; James M. Cook (Medicinal Chemistry Research, 2004)

Isolation and Characterization of Arsenate-Reducing Bacteria from Arsenic-Contaminated Sites in New Zealand - Craig R. Anderson; Gregory M. Cook (Current Microbiology, 2004)

Liquid-feeding performances of ants (Formicidae): ecological and evolutionary implications - Diane W. Davidson; Steven C. Cook; Roy R. Snelling (Oecologia, 2004)

TP53 haplotype-based analysis and incidence of post-angioplasty restenosis - Robert Y. L. Zee; Nancy R. Cook; Chung-Ah Kim; Arturo Fernandez-Cruz; Klaus Lindpaintner (Human Genetics, 2004)

AZT inhibits Visna/maedi virus -induced apoptosis - V. Bellet; R. Duval; S. Delebasse; J. Cook-Moreau; C. Bosgiraud (Archives of Virology, 2004)

The severe combined immunodeficient (SCID) mouse model of human immunodeficiency virus encephalitis: Deficits in cognitive function - William C Griffin; Lawrence D Middaugh; Jennifer E Cook; William R Tyor (Journal of NeuroVirology, 2004)

Genetic resistance to nematodes: where is it useful? - R. Cook (Australasian Plant Pathology, 2004)

Cotton rat Sihi- M3 is a minimally oligomorphic Mhc I-b molecule that binds the chemotactic peptide fMLF under stringent conditions - C. Kuyler Doyle; Richard G. Cook; Robert R. Rich; John R. Rodgers (Immunogenetics, 2003)

Amino acid transport by Sphingomonas sp. strain Ant 17 isolated from oil-contaminated Antarctic soil - Katherine Young; R. Brent Seale; Karen Olsson; Jackie Aislabie; Gregory M. Cook (Polar Biology, 2003)

Influence of pasture management (nitrogen and lime addition and insecticide treatment) on soil organisms and pasture root system dynamics in the field - L. A. Dawson; S. J. Grayston; P. J. Murray; R. Cook; A. C. Gange; J. M. Ross; S. M. Pratt; E. I. Duff; A. Treonis (Plant and Soil, 2003)

Dendroclimatic signals in long tree‐ring chronologies from the Himalayas of Nepal - Edward R. Cook; Paul J. Krusic; Philip D. Jones (International Journal of Climatology, 2003)
We describe the development of a tree‐ring chronology network in Nepal that is suitable for reconstructing temperature‐related climate forcing over the past few hundred years. The network is composed of 32 tree‐ring chronologies and is represented by five indigenous tree species. An empirical orthogonal function analysis of the chronologies over the common interval 1796–92 indicates the existence of coherent large‐scale signals among the tree‐ring chronologies that are hypothesized to reflect, in part, broad‐scale climate forcing related to temperatures. A long monthly temperature record for Kathmandu is developed and used to test this hypothesis. In so doing, significant monthly and seasonal temperature responses are identified that provide guidance for the formal reconstruction of two temperature seasons: February–June (1546–91) and October–February (1605–91). Each reconstruction indicates the occurrence of unusually cold temperatures in 1815–22, which coincides with the eruption of Tambora in Indonesia. A novel method is also used to add probable missing multi‐centennial temperature variance to each reconstruction. The resulting ‘adjusted’ reconstructions strongly reflect patterns of temperature variability associated with Little Ice Age cooling and warming into the 20th century, with the October–February season exhibiting the strongest increase in temperature over the past ∼400 years. Only the October–February season shows any evidence for late‐ 20th century warming, whereas February–June temperatures have actually cooled since 1960 (as with the observational series). Copyright © 2003 Royal Meteorological Society

Deep Natural Gas Resources - T. S. Dyman; R. E. Wyman; V. A. Kuuskraa; M. D. Lewan; T. A. Cook (Natural Resources Research, 2003)

Inheritance of superoxide dismutase (Sod-1) in a perennial × annual ryegrass cross and its allelic distribution among cultivars - S. Warnke; R. Barker; L. Brilman; W. Young; R. Cook (Theoretical and Applied Genetics, 2002)

An Integrated Pharmacodynamic Analysis of Erythropoietin, Reticulocyte, and Hemoglobin Responses in Acute Anemia - P. Veng-Pederson; S. Chapel; P. R. L. Schmidt; N. H. Al-Huniti; R. T. Cook; J. A. Widness (Pharmaceutical Research, 2002)

Estrogen–progestin replacement therapy and breast cancer risk: the Women's Health Study (United States) - Juliet V. Porch; I-Min Lee; Nancy R. Cook; Kathryn M. Rexrode; Julie E. Buring (Cancer Causes & Control, 2002)

An alkaline phosphatase‐based method for the detection of infectious salmon anaemia virus (ISAV) in tissue culture and tissue imprints - L Wilson; S J McBeath; K L Adamson; P F Cook; L M Ellis; I R Bricknell (Journal of Fish Diseases, 2002)
Currently, the presence of infectious salmon anaemia virus (ISAV) is often detected in Atlantic salmon by the use of an indirect fluorescent antibody test. This test is limited by the poor stability of fluorescein isothiocyanate which fades after about a week in storage, preventing the development of stained archive material as a reference source. One possible alternative would be the use of immunohistochemical staining methods to detect ISAV. An immunohistochemical method is presented that uses alkaline phosphatase‐conjugated antibodies and Vector ® Red as a substrate, to detect ISAV in kidney imprints. This paper also describes a procedure where Bouin's fluid is used to successfully inhibit endogenous alkaline phosphatase in tissue samples, prior to immunohistochemical processing. This method provides a stable stain that can be read for many weeks after staining or archived for future reference.

Microsynteny between pea and Medicago truncatula in the SYM2 region - Gustavo Gualtieri; Olga Kulikova; Erik Limpens; Dong-Jin Kim; Douglas R. Cook; Ton Bisseling; René Geurts (Plant Molecular Biology, 2002)

Physiological and performance effects of pyridostigmine bromide in healthy volunteers: a dose-response study - Mary R. Cook; Charles Graham; Antonio Sastre; Mary M. Gerkovich (Psychopharmacology, 2002)

Diversity, Distribution, and Ancient Taxonomic Relationships Within the TIR and Non-TIR NBS-LRR Resistance Gene Subfamilies - Steven B. Cannon; Hongyan Zhu; Andrew M. Baumgarten; Russell Spangler; Georgiana May *, , Douglas R. Cook (Journal of Molecular Evolution, 2002)

Choosing appropriate techniques for quantifying groundwater recharge - Bridget R. Scanlon; Richard W. Healy; Peter G. Cook (Hydrogeology Journal, 2002)

Theme issue on groundwater recharge - Bridget R. Scanlon; Peter G. Cook (Hydrogeology Journal, 2002)

Leachability and Toxicity of Hydrocarbons, Metals and Salt Contamination from Flare Pit Soil - S. V. Cook; A. Chu; R. H. Goodman (Water, Air, & Soil Pollution, 2002)

Congruent patterns of genetic variation in a burrowing freshwater crab revealed by allozymes and mt DNA sequence analysis - Savel R. Daniels; Barbara A. Stewart; Peter A. Cook (Hydrobiologia, 2002)

Isolation and growth of a cytopathic agent from multiple sclerosis brain tissue - Anthony R White; Nichole S Dutton; Robert D Cook (Journal of NeuroVirology, 2002)

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. VII. Overview and discussion - I. W. B. Thornton; S. Cook; J. S. Edwards; R. D. Harrison; C. Schipper; M. Shanahan; R. Singadan; R. Yamuna (Journal of Biogeography, 2001)
Location, aims Long Island's biota was destroyed by volcanic eruption in c. 1645, and Motmot, an emergent island in its caldera lake, was re‐created in 1968, providing a nested pair of natural colonization sequences. In 1999 we surveyed the plants and vertebrates of Long and the entire biota of Motmot for comparison with previous surveys of Long (1932, 1972, birds only) and Motmot (1969–88). Results The known flora of Long is 305 vascular plants (thirty‐two pteridophytes, 273 spermatophytes), including thirty‐one Ficus species, the sixteen fruiting all having pollinating wasps, and there were eleven species of effective fig dispersers. There were two frog species, a crocodile, a monitor, seven skinks, four geckos, a boid snake, fifty species non‐migrant land birds, seven bats, two rats, a cuscus (probably introduced) and feral pigs, dogs, cats and chickens. Most of Motmot's surface was barren or sparsely vegetated ash, cinder and lava fields. There were seven pteridophyte and thirty‐eight spermatophyte species, including eight Ficus , and the cumulative known flora comprises eleven pteridophytes and fifty‐one spermatophytes, mainly zoochorous and anemochorous, with sedges, grasses and herbs predominating. All Ficus individuals but one were small; three plants of two species bore syconia but had not been pollinated and had not set seed. Motmot's known invertebrate fauna comprises thirty‐five species, mainly predators and scavengers; two spider and one ant species dominating. An insectivorous bat and eight land bird species (three breeding) were the only vertebrates. Main conclusions Long's biota comprised mainly widely distributed species with broad ecological tolerances, well‐adapted for colonizing species‐poor islands. The mid‐level caldera plateau, as in 1932, was covered in fairly open forest of similar‐sized trees with a few much larger individuals and little or no understorey. Primary rain forest tree species from the region were under‐represented or absent but secondary forest species were common. There were few regional endemic Ficus species. The avifauna comprised species with good dispersal ability, lacked endemic subspecies and probably for at least the past seven decades has been held at a quasi‐equilibrium of fifty species, fourteen below the theoretical number. More than half the fifty‐four resident land birds known from Long (and three of the seven bats) are high class tramps in the sense of Diamond; only two birds are high‐S species. Turnover has been low and none of the bird super tramps has been replaced. The non‐avian fauna comprised mostly high‐category tramptype species with relatively broad habitat requirements and extensive geographical ranges. Non‐volant vertebrates comprised a number of highly vagile species associated with humans. Several groups, especially snakes and amphibians, were depauperate compared with the fauna of other islands in the area. Long's biota is evidently held at an arrested stage of development by some physical factor, possibly the extremely porous substratum and relatively dry climate. The allochthonous input of lake insects to Motmot evidently provides the major energy source for its animal communities, with a very minor contribution from organic flotsam. Reflecting Motmot's very isolated situation, plant colonization has been slow, but when more fig individuals mature and fig–wasp populations become established fruit production should attract frugivores and start a positive feedback process which will accelerate the growth of Motmot's community. Long's colonization shows similarities with that of Krakatau (Sunda Strait, Indonesia) after the 1883 eruption, and species shared by the two include a high proportion of pioneer species. Motmot's triple isolation (sea, land and fresh‐water barriers) means that its colonization differs markedly from those on two marine emergent islands of the region, Tuluman (Admiralty Group) and Anak Krakatau.

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. IV. Colonization by non‐avian vertebrates - S. Cook; R. Singidan; I. W. B. Thornton (Journal of Biogeography, 2001)
Aim In a 1999 expedition we surveyed the non‐avian vertebrates recolonizing a volcanic island off the north coast of Papua New Guinea, and the more recently emerged islet in its caldera lake. It is our intention with this research to document the reassembly of an ecosystem after a cataclysmic event at two temporal stages. Location Long Island, 55 km north of Papua New Guinea, erupted explosively in the seventeenth century. Its biota was destroyed and the island has been recolonized by animals and plants. From about 1953 to 1968, an island, Motmot, emerged from Long's freshwater caldera lake about 4 km from the nearest shore. Methods For 15 days in 1999 we surveyed the mammals, reptiles and amphibians of Motmot and the western parts of Long. Results We assess the present fauna as thirteen mammals, fourteen reptiles and two amphibians. Main conclusions Long appears to have a high proportion of tramp‐type species in its bat fauna, indicative of a developing biota. Several groups, especially snakes and amphibians, appear to be depauperate compared to the fauna of other islands in the area. On Motmot we recorded only one species of insectivorous bat; its vertebrate fauna is still in the very first stages of development.

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. VII. Overview and discussion - I. W. B. Thornton; S. Cook; J. S. Edwards; R. D. Harrison; C. Schipper; M. Shanahan; R. Singadan; R. Yamuna (Journal of Biogeography, 2001)

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. IV. Colonization by non-avian vertebrates - S. Cook; R. Singidan; I. W. B. Thornton (Journal of Biogeography, 2001)

A Riparian Wildlife Habitat Evaluation Scheme Developed Using GIS - DIANE L. SZAFONI; LOUIS R. IVERSON; SHARON E. BAUM; ELIZABETH A. COOK (Environmental Management, 2001)

Phylogeography of the dusky shrew, Sorex monticolus (Insectivora, Soricidae): insight into deep and shallow history in northwestern North America - John R. Demboski; Joseph A. Cook (Molecular Ecology, 2001)
Phylogenetic relationships among the dusky shrew ( Sorex monticolus ) and eight related species ( S . bairdi , S . bendirii , S . neomexicanus , S. ornatus , S . pacificus , S . palustris , S . sonomae and S. vagrans ) were assessed using sequences from the mitochondrial cytochrome b gene (801 bp). Analyses using parsimony and maximum likelihood revealed significant molecular variation not reflected in previous morphological studies of these species. Conversely, three morphologically defined species ( S. bairdi , S. neomexicanus and S. pacificus ) were poorly differentiated. Sorex ornatus and S. vagrans represented basal taxa for a more inclusive group that included: (i) a widespread Continental clade containing S. monticolus (Arizona to Alaska, including S . neomexicanus ); (ii) a Coastal clade containing S. monticolus (Oregon to south‐east Alaska, including S . bairdi and S . pacificus ); (iii) the semiaquatic species ( S. bendirii and S . palustris ); and (iv) S. sonomae . Additional subdivision was observed within the Continental clade corresponding to populations from the northern and southern Rocky Mountains. Average uncorrected sequence divergence between the Coastal and Continental clades was 5.3% (range 4.5–6.2%), which exceeds many interspecific comparisons within this species complex and within the genus Sorex . Lack of resolution of internal nodes within topologies suggests a deep history of rapid diversification within this group. Late Pleistocene/Holocene glacial perturbations are reflected in the shallow phylogeographic structure within these clades in western North America. Our results suggest also that S. monticolus is not monophyletic under current taxonomic nomenclature. This perspective on phylogeographic history was developed within a growing comparative framework for other organisms in western North America.

New species of Spongia (Porifera: Demospongiae: Dictyoceratida) from New Zealand, and a proposed subgeneric structure - Steve de C. Cook; Patricia R. Bergquist (New Zealand Journal of Marine and Freshwater Research, 2001)
This paper is the fifth in a series revising the taxonomy of New Zealand dictyoceratid sponges (phylum Porifera, subclass Ceractinomorpha, order Dictyoceratida). Six new species of the genus Spongia are added to New Zealand's known fauna. The use of subgenera within the genus Spongia is discussed, and two new subgenera are proposed. The genus Hippospongia is revised, and an emended generic diagnosis is proposed.

The climatic response of Phyllocladus aspleniifolius (Labill.) Hook. f in Tasmania - K. J. Allen; E. R. Cook; R. J. Francey; K. Michael (Journal of Biogeography, 2001)
Aim To examine the response of ring widths of Phyllocladus aspleniifolius to maximum and minimum temperatures and to a zonal index (ZI). Location Tasmania, Australia. Methods Between two and four increment cores were obtained from approximately 20 trees at each of 16 sites of P. aspleniifolius across Tasmania. Four regions were defined and temperature data for climate stations from each of these regions were transformed into dimensionless time series appropriate for each region. The ZI was constructed from Melbourne and Hobart mean sea level pressure (MSLP). Correlations were calculated between climate data and ring widths over most of the 20th century. Data were then segregated into two subperiods to assess whether or not temporal changes in ring width response have occurred over the 20th century. Results The dominant feature of the correlation functions was a negative correlation with temperatures of the previous growing season. Correlation between the ZI and ring width is most significant, and positive, in November and March of the previous growing season. Differences in the shape of the correlation functions, and their strength is apparent over the course of the century. In general, correlations have become weaker and less consistent among the 16 sites for the latter part of the century. Temperatures have generally increased during the 1900s over which time period correlations have been calculated. Main conclusions The temporally changing climatic response in ring widths is consistent with a hypothesis of competition for resources between different parts of a plant. A nonlinear response to climate over a short‐time period violates one of the basic assumptions of dendroclimatology, therefore suggesting further investigation of both the physiology of trees used for dendroclimatological purposes and the statistical methods used for climatic reconstruction.

Physical activity and breast cancer risk: the Women's Health Study (United States) - I-Min Lee; Kathryn M. Rexrode; Nancy R. Cook; Charles H. Hennekens; Julie E. Buring (Cancer Causes & Control, 2001)

Grey intense: a new mouse mutation affecting pigmentation - Muriel T. Davisson; Kenneth R. Johnson; Roderick T. Bronson; Patricia F. Ward-Bailey; Susan A. Cook; Belinda S. Harris; Leah Rae Donahue (Mammalian Genome, 2000)

A rough guide to population change in exploited fish stocks - R. Cook (Ecology Letters, 2000)
Interpreting how populations will change in response to exploitation is essential to the sound management of fish stocks. While deterministic models can be of use in evaluating sustainable fishing rates, the inherent variability of fish populations limits their value. In this paper a probabilistic approach is investigated which avoids having to make strong assumptions about the functional relationship between spawning stock size and the annual number of young fish (recruits) produced. Empirical probability distributions for recruits are derived, conditioned on stock size, and used to indicate likely stock changes under different fishing mortality rates. The method is applied to cod ( Gadus morhua ) in the North Sea to illustrate how population change can be inferred and used by fishery managers to choose fishing mortality rates which are likely to achieve sustainable exploitation.

Trans-Tasman Sea climate variability since ad 1740 inferred from middle to high latitude tree-ring data - R. D'Arrigo; E. Cook; R. Villalba; B. Buckley; J. Salinger; J. Palmer; K. Allen (Climate Dynamics, 2000)

Sex-related differences in the antinociceptive effects of opioids: importance of rat genotype, nociceptive stimulus intensity, and efficacy at the µ opioid receptor - Charles D. Cook; Andrew C. Barrett; Emily L. Roach; Joseph R. Bowman; Mitchell J. Picker (Psychopharmacology, 2000)

Effects of beta-carotene supplementation on cancer incidence by baseline characteristics in the Physicians' Health Study (United States) - Nancy R. Cook; I-Min Lee; JoAnn E. Manson; Julie E. Buring; Charles H. Hennekens (Cancer Causes & Control, 2000)

Urban forest cover of the Chicago region and its relation to household density and income - Louis R. Iverson; Elizabeth A. Cook (Urban Ecosystems, 2000)

Warm-season temperatures since 1600 BC reconstructed from Tasmanian tree rings and their relationship to large-scale sea surface temperature anomalies - E. R. Cook; B. M. Buckley; R. D. D'Arrigo; M. J. Peterson (Climate Dynamics, 2000)

Bay‐scale population structure in coastal Atlantic cod in Labrador and Newfoundland, Canada - D. E. Ruzzante; J. S. Wroblewski; C. T. Taggart; R. K. Smedbol; D. Cook; S. V. Goddaard (Journal of Fish Biology, 2000)
Polymorphisms at five microsatellite DNA loci provide evidence that Atlantic cod Gadus morhua inhabiting Gilbert Bay, Labrador are genetically distinguishable from offshore cod on the north‐east Newfoundland shelf and from inshore cod in Trinity Bay, Newfoundland. Antifreeze activity in the blood suggests that Gilbert Bay cod overwinter within the Bay. Gilbert Bay cod are also smaller (weight and length) for their age and consequently less fecund for their age, than cod elsewhere within the northern cod complex. The productivity and recruitment potential of coastal cod off Labrador may thus be much lower than that of offshore northern cod or of inshore cod farther south, implying that a more conservative management strategy may be required for cod from coastal Labrador than traditionally practised for northern cod inhabiting less harsh environments. Relatively high F ST and R ST measures of population structure suggest that important barriers to gene flow exist among five components that include two inshore (Gilbert and Trinity Bay) and three offshore cod aggregations on the north‐east Newfoundland Shelf and the Grand Bank. D A and D SW estimates of genetic distance that involve Gilbert Bay cod are approximately three‐ and 10–fold larger, respectively, than estimates not involving Gilbert Bay cod. The differences between inshore cod from Gilbert Bay and Trinity Bay raise the possibility that other genetically distinguishable coastal populations may exist, or may have existed prior to the northern cod fishery collapse. Harvesting strategies for northern cod should recognize the existence of genetic diversity between inshore and offshore components as well as among coastal components.

Hair product use and the risk of breast cancer in young women - Linda S. Cook; Kathleen E. Malone; Janet R. Daling; Lynda F. Voigt; Noel S. Weiss (Cancer Causes & Control, 1999)

New species of dictyoceratid sponges from New Zealand: Genus Ircinia (Porifera: Demospongiae: Dictyoceratida) - Steve de C. Cook; Patricia R. Bergquist (New Zealand Journal of Marine and Freshwater Research, 1999)
This paper is the third in a series revising the taxonomy of New Zealand dictyoceratid sponges (phylum Porifera, class Ceractinomorpha, order Dictyoceratida). Only one species of Ircinia has previously been described from New Zealand, Ircinia novaezealandiae Bergquist, 1961. Six new species of Ircinia are added to New Zealand's known fauna. The genus Ircinia contains in excess of 40 published species worldwide, although the integrity of some of these is uncertain, often because of poor diagnoses. The diagnoses of new species reported here provide a model for the morphological descriptions of future species. The subdivision of Ircinia is also considered.

Identification of three genes expressed primarily during development in Physarum polycephalum - J. Bailey; L. J. Cook; R. Kilmer-Barber; E. Swanson; L. Solnica-Krezel; K. Lohman; W. F. Dove; J. Dee; R. W. Anderson (Archives of Microbiology, 1999)

Cloning and sequence analysis of the H2-K2 b gene reveals that it is a pseudogene - Rajneesh P. Uzgare; R. G. Cook (Immunogenetics, 1999)

Construction of a bacterial artificial chromosome library of Medicago truncatula and identification of clones containing ethylene-response genes - Y.-W. Nam; R. V. Penmetsa; G. Endre; P. Uribe; D. Kim; D. R. Cook (Theoretical and Applied Genetics, 1999)

Three new species of Apheviderulix gen. nov. and proposal of Apheviderulicidae fam. nov. (Acari: Hydrachnidia: Eylaoidea) - Reinhard Gerecke; Ian M. Smith; David R. Cook (Hydrobiologia, 1999)

Mammalian biogeography of the Alexander Archipelago of Alaska: a north temperate nested fauna - Chris J. Conroy; John R. Demboski; Joseph A. Cook (Journal of Biogeography, 1999)
Summary Aim A large number of studies have analysed the distribution of mammals within archipelagos, yet few have focused on islands that were heavily glaciated and subsequently colonized following deglaciation. Location We explored the relative effects of island area and isolation on faunal composition based on twenty‐three mammalian taxa of twenty‐four islands of the Alexander Archipelago, Southeast Alaska. Methods We used regression of log‐transformed variables and several indices of nestedness. Results These faunas showed significant nested structure using tests of nestedness and regression models. Unlike most landbridge and mainland archipelagos studied previously, isolation appears to be the primary factor determining patterns of species richness. Main conclusions Colonization ability of particular taxa, rather than extinction, has determined this nested structure. We suggest that other higher latitude archipelagos may show similar historical patterns.

The original shaker-with-syndactylism mutation ( sy ) is a contiguous gene deletion syndrome - Kenneth R. Johnson; Susan A. Cook; Qing Yin Zheng (Mammalian Genome, 1998)

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

Revision of the genus Psammocinia (Porifera: Demospongiae: Dictyoceratida), with six new species from New Zealand - Steve de C. Cook; Patricia R. Bergquist (New Zealand Journal of Marine and Freshwater Research, 1998)
The status of species within the dictyo‐ceratid sponge genus Psammocinia is reviewed. The separation of Psammocinia species from the closely related Ircinia species, which has been the subject of some dispute, is clarified. This distinction made on the basis of morphological evidence is supported by the limited chemotaxonomic and molecular phylogenetic data available. Six new species of Psammocinia are described from the New Zealand region.

Comparison of Ceralure and Trimedlure Controlled-Release Formulations for Male Mediterranean Fruit Flies in C&C Traps - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1998)

Linkage mapping of two mutations that reduce phytic acid content of barley grain - S. R. Larson; K. A. Young; A. Cook; T. K. Blake; V. Raboy (Theoretical and Applied Genetics, 1998)

Tree-ring records from New Zealand: long-term context for recent warming trend - R. D. D'Arrigo; E. R. Cook; M. J. Salinger; J. Palmer; P. J. Krusic; B. M. Buckley; R. Villalba (Climate Dynamics, 1998)

An evaluation of randomization models for nested species subsets analysis - Rosamonde R. Cook; James F. Quinn (Oecologia, 1998)

Adult height and incidence of cancer in male physicians (United States) - Patricia R. Hebert; Umed Ajani; Nancy R. Cook; I-Min Lee; Ki Sau Chan; Charles H. Hennekens (Cancer Causes & Control, 1997)

Unusually low carbon isotope ratios in plants from hanging gardens in southern Utah - Lawrence B. Flanagan; Craig S. Cook; James R. Ehleringer (Oecologia, 1997)

Sea-level pressure variability around Antarctica since A.D. 1750 inferred from subantarctic tree-ring records - R. Villalba; E. R. Cook; R. D. D'Arrigo; G. C. Jacoby; P. D. Jones; M. J. Salinger; J. Palmer (Climate Dynamics, 1997)

A CHANGING TEMPERATURE RESPONSE WITH ELEVATION FOR LAGAROSTROBOS FRANKLINII IN TASMANIA, AUSTRALIA - B. M. BUCKLEY; E. R. COOK; M. J. PETERSON; M. BARBETTI (Climatic Change, 1997)

Improved Controlled-Release Formulations for a New Trap Design for Male Mediterranean Fruit Flies: The C&C Trap - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1997)

Migration between nests in the Australian arid‐zone ant Rhytidoponera sp. 12 revealed by DGGE analyses of mitochondrial DNA - W. Tek Tay; J. M. Cook; D. J. Rowe; R. H. Crozier (Molecular Ecology, 1997)
Denaturing gradient gel electrophoresis (DGGE) of a PCR‐amplified region of the mitochondrial DNA (mtDNA) including a large part of the cytochrome b gene revealed four haplotypes among worker ants from 75 colonies of the queenless ant Rhytidoponera sp. 12. The DGGE results were checked by sequencing examples of the haplotypes; all changes were transitions and two haplotypes differed by only a single substitution. Previous work (e.g. Crozier et al. 1984) showed that intranest relatedness is low for nuclear genes yet neighbouring nests are related; gene flow via winged males appeared the best explanation for this phenomenon. Two mtDNA haplotypes were found in 34.7% of the colonies studied, showing that female movement also occurs between nests. Migration of mated individuals on such a large scale when the number of reproductives is relatively small is unexpected (Crozier & Pamilo 1996). An observed tendency to clumping of the haplotypes is in accordance with the wingless nature of the female dispersers.

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

A recombinant fowlpox virus that expresses the VP2 antigen of infectious bursal disease virus induces protection against mortality caused by the virus - C. D. Bayliss; R. W. Peters; Jane K. A. Cook; R. L. Reece; K. Howes; M. M. Binns; M. E. G. Boursnell (Archives of Virology, 1991)

Detection and prevalence of serotypes of feline syncytial spumaviruses - R. L. P. Flower; G. E. Wilcox; R. D. Cook; T. M. Ellis (Archives of Virology, 1985)

Respiratory nitrate reduction by Desulfovibrio sp. - R. G. L. McCready; W. D. Gould; F. D. Cook (Archives of Microbiology, 1983)

Complementation with an avian influenza virus is required for synthesis of M protein of a human strain in chicken erythrocytes - R. F. Cook; R. J. Avery; N. J. Dimmock (Archives of Virology, 1980)

Taxonomic studies on strains of avian infectious bronchitis virus using neutralisation tests in tracheal organ cultures - J. H. Darbyshire; J. G. Rowell; Jane K. A. Cook; R. W. Peters (Archives of Virology, 1979)

Growth comparisons of avian infectious bronchitis virus strains in organ cultures of chicken tissues - J. H. Darbyshire; Jane K. A. Cook; R. W. Peters (Archives of Virology, 1978)

The use of chicken tracheal organ cultures for the isolation and assay of avian infectious bronchitis virus - Jane K. A. Cook; J. H. Darbyshire; R. W. Peters (Archives of Virology, 1976)

Aromatic metabolism in the fungi. Growth of Rhodotorula mucilaginosa in p-hydroxybenzoate-limited chemostats and the effect of growth rate on the synthesis of enzymes of the 3-oxoadipate pathway - Timothy J. Huber; John R. Street; Alan T. Bull; Keith A. Cook; Ronald B. Cain (Archives of Microbiology, 1975)

Characterization of hypoxanthine-guanine phosphoribosyl transferase in man-mouse somatic cell hybrids by an improved electrophoretic method - Seung-il Shin; P. Meera Khan; Peter R. Cook (Biochemical Genetics, 1971)

On the uniqueness of the flagellum ofThiobacillus thiooxidans - R. N. Doetsch; T. M. Cook; Z. Vaituzis (Antonie van Leeuwenhoek, 1967)

Sectional notes - W. B. Ward; Allan Purdy; Marx Koeiinke; H. J. Evans; Harrold Mattson; E. B. Tussing; Harold T. Cook; M. R. Harris; R. E. Goodwin; W. N. Keenan (American Journal of Potato Research, 1947)